Separator for power storage device and power storage device comprising same
By using polyolefin microporous film as a substrate in the lithium-ion secondary battery separator and forming a cover layer of thermoplastic polymer particulate polymer and inorganic filler on its surface, the uneven adhesion and resistance of the separator are solved. The problem of insufficient thermal properties significantly improves the cycle characteristics and output characteristics of the battery.
Patent Information
- Application Number
- CN202380036350.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-26
- Filing Date
- 2023-04-20
- Publication Date
- 2024-12-17
AI Technical Summary
The existing separators for lithium-ion secondary batteries have problems such as uneven adhesion, insufficient heat resistance, and low circulation characteristics and output characteristics, especially in high-capacity electrodes and high-temperature conditions.
Using a polyolefin microporous film as the substrate, the cover layer is equipped with thermoplastic polymer particulate polymer and inorganic filler. By adjusting the structure and composition of the cover layer, the adhesion and thermal stability with the electrode are improved, and the Cycle characteristics and output characteristics of the battery.
High adhesion to the electrode and low heat shrinkage rate are achieved, the cycle characteristics and output characteristics of the battery are improved, and the stability and safety of the battery under high temperature and high pressure conditions are ensured.
Smart Images

Figure CN119156739A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a separator for an electric storage device and an electric storage device including the separator. Background Art
[0002] The development of power storage devices represented by lithium-ion secondary batteries is being actively carried out. Generally speaking, power storage devices include a positive electrode and a negative electrode, and a separator including a microporous membrane between them. The separator has the function of preventing the positive electrode from directly contacting the negative electrode and allowing ions to pass through the electrolyte retained in the micropores. The separator is required to have safety properties such as the property of quickly stopping the battery reaction in the event of abnormal heating (fusing property), and the performance of maintaining the shape even at high temperatures to prevent the dangerous situation of direct reaction between the positive electrode and the negative electrode (short circuit resistance property).
[0003] On the other hand, non-aqueous secondary batteries such as lithium-ion secondary batteries are developed into various shapes such as cylindrical, square, and soft-bag depending on their use. The manufacturing method of the battery also varies depending on the shape of the battery. For example, in the manufacture of square batteries, there is a process of pressurizing a wound body or a laminate of electrodes and polyolefin microporous membranes and inserting it into a rectangular outer packaging can.
[0004] In recent years, in order to increase the capacity of an electrical storage device, the following operations have been performed: a stack of electrodes and separators is subjected to heat pressing, or a wound body obtained by winding the stack of electrodes and separators is subjected to heat pressing, thereby reducing the volume of the electrical storage device. At this time, the following technology is known: in order to keep the electrode and the separator fixed after the heat pressing and maintain the volume during the pressing, a covering layer containing a thermoplastic polymer that exhibits an adhesive function under predetermined conditions is arranged on the separator serving as a base material, thereby improving the adhesion between the separator as a whole and the electrode.
[0005] Furthermore, with the improvement of electrode materials, high-density modularization of multiple non-aqueous secondary batteries (single battery cells) (increasing the volume energy density of the module), etc., it is also sought to ensure the ion permeability of the microporous membrane serving as a separator and the output characteristics or cycle characteristics of the battery containing the same even when the battery cells and separators are subjected to external pressure.
[0006] For example, Patent Document 1 describes a separator having a porous coating layer containing organic polymer particles for the purpose of improving the bonding force between the separator and the electrode even without the humidification phase separation process of the organic binder polymer and the secondary coating of the adhesive layer, and improving safety by firmly integrating the separator and the electrode. In the separator, the organic polymer particles protrude from the surface of the porous coating layer by a height of 0.1 μm to 3 μm.
[0007] Patent Document 2 describes a separator having a surface coating containing polymer binder particles of different particle sizes for the purpose of suppressing deformation of the storage device caused by volume expansion of the electrode during charging. The polymer binder particles of different particle sizes form a gap between the separator and the electrode that can accommodate the internal expansion of the storage device.
[0008] Patent document 3 describes a separator, wherein, in order to further improve the existing separator and its manufacturing method, the separator has a composite material coating including inorganic particles, polymer particles and a binder for the purpose of having good thermal stability and good adhesion to the electrode, thereby ensuring the safety and flatness of the storage device. The polymer particles are dispersed in the inorganic particles and protrude from the surface of the inorganic particles.
[0009] Patent document 4 describes a separator having excellent adhesion and heat resistance, and having a functional layer containing inorganic particles and a granular polymer for the purpose of improving electrolyte injection properties. When the surface of the functional layer is viewed from above, the area ratio of the inorganic particles per unit area of the functional layer exceeds 90%, the volume average particle size of the granular polymer is within a specific range, and the volume average particle size of the granular polymer is greater than the thickness of the inorganic particle layer.
[0010] Patent document 5 describes a separator, which has a functional layer containing inorganic particles and a granular polymer for the purpose of providing a functional layer for an electrochemical element with excellent process adhesion and capable of exerting excellent cycle characteristics of the electrochemical element. The functional layer has a particle shedding portion, and when the surface of the functional layer for the electrochemical element is viewed from above, the area of the particle shedding portion accounts for a proportion of 0.1% or more and 40.0% or less of the total area of the granular polymer and the particle shedding portion, and the volume average particle diameter of the granular polymer is greater than the thickness of the inorganic particle layer containing the inorganic particles.
[0011] In addition, from the perspectives of heat resistance or rigidity of the separator serving as the substrate, cycle characteristics of lithium-ion secondary batteries, etc., the crystallinity of polyolefin contained in the separator or the pressure test characteristics of the polyolefin microporous membrane used as the separator are being studied (Patent Documents 6 to 9).
[0012] Patent Document 6 describes the long period of the lamellae measured by small angle X-ray scattering (SAXS) of a polyolefin microporous film made porous by dry stretching from the viewpoint of excellent lithium ion permeability and heat resistance.
[0013] Patent Document 7 describes the long period of polymer crystals measured by the SAXS method of a stretched polypropylene film from the viewpoint of achieving both low heat shrinkage and high rigidity.
[0014] In Patent Documents 8 and 9, from the perspectives of the compression resistance of separators for lithium-ion secondary batteries and the cycle characteristics of lithium-ion secondary batteries, the film thickness change rate of a polyolefin microporous membrane before and after a heating compression test (Patent Document 8) for 60 minutes at a temperature of 80°C and a pressure of 1 MPa is recorded, or the air permeability change rate and film thickness change rate of a polyolefin microporous membrane before and after a heating compression test (Patent Document 9) for 5 minutes at a temperature of 90°C and a pressure of 5.0 MPa are recorded.
[0015] Prior art literature
[0016] Patent Literature
[0017] Patent Document 1: Korean Patent Publication No. 10-2016-0118979
[0018] Patent Document 2: International Publication No. 2019 / 089492
[0019] Patent Document 3: Chinese Patent No. 105958000
[0020] Patent Document 4: International Publication No. 2020 / 175079
[0021] Patent Document 5: International Publication No. 2021 / 085144
[0022] Patent Document 6: International Publication No. 2014 / 175252
[0023] Patent Document 7: International Publication No. 2015 / 012324
[0024] Patent Document 8: International Publication No. 2018 / 164056
[0025] Patent Document 9: International Publication No. 2015 / 194504 Summary of the invention
[0026] Problem that the invention aims to solve
[0027] However, these conventional separators for lithium ion secondary batteries, which are formed of a polyolefin microporous film and serve as a base material, have the following problems.
[0028] For example, in Patent Document 1 and Patent Document 3, secondary particulate adhesive polymers are used, and there is a problem of uneven distribution of separator thickness. Furthermore, due to the poor dispersibility of the adhesive polymer in the coating state, there are the following problems: the adhesive polymer aggregates on the separator, resulting in uneven adhesion to the electrode, which leads to a decrease in the overall adhesion; and the problem of deterioration of heat resistance. In Patent Document 2, there is no heat-resistant layer containing inorganic fillers, and there is a problem that the separator cannot be given sufficient heat resistance. In Patent Documents 4 and 5, the adhesive force of the covering layer is insufficient, and there is still room for improvement in the control of powder loss in the manufacturing process and the adhesion to the electrode.
[0029] On the other hand, the cycle characteristics and output characteristics of the battery may be reduced due to the pressurization process of making batteries using conventional polyolefin microporous membranes as described in Patent Documents 6 to 9. In addition, the same phenomenon also occurs significantly when using high-capacity and easily swellable electrodes.
[0030] In view of the above circumstances, an object of the present application is to provide a separator for an electrical storage device having high adhesive force with an electrode, low thermal shrinkage, and capable of improving the cycle characteristics and output characteristics of the electrical storage device, and an electrical storage device having the same.
[0031] Solutions for solving problems
[0032] Examples of implementations of the present application are listed below.
[0033] [1] A separator for an electrical storage device, comprising a substrate and a covering layer, wherein the substrate is a polyolefin microporous membrane containing a polyolefin as a main component, and the covering layer is disposed on at least one surface of the substrate.
[0034] The film thickness of the substrate is 1 μm to 30 μm, and the air permeability is 500 sec / 100 cm 3 The following, and the porosity of the substrate after compression measured under the conditions of a temperature of 70° C., a pressure of 8 MPa and a compression time of 3 minutes is 30% or more,
[0035] The above-mentioned covering layer comprises a granular polymer of a thermoplastic polymer and an inorganic filler,
[0036] The particulate polymer includes a protruding particulate polymer, wherein the protruding particulate polymer protrudes from the covering layer by 0.1 times or more the thickness of the inorganic filler portion of the covering layer.
[0037] [2] A separator for an electrical storage device, comprising a substrate and a covering layer, wherein the substrate is a polyolefin microporous membrane containing a polyolefin as a main component, and the covering layer is disposed on at least one surface of the substrate.
[0038] The polyolefin microporous membrane has a crystal long period of 37.0 nm or more as measured by a small angle X-ray scattering (SAXS) method.
[0039] The above-mentioned covering layer comprises a granular polymer of a thermoplastic polymer and an inorganic filler,
[0040] The particulate polymer includes a protruding particulate polymer, wherein the protruding particulate polymer protrudes from the covering layer by 0.1 times or more the thickness of the inorganic filler portion of the covering layer.
[0041] [3] The electrical storage device separator according to item [2], wherein the substrate has a film thickness of 1 μm to 30 μm and an air permeability of 500 sec / 100 cm 3 The substrate is compressed under the conditions of a temperature of 70° C., a pressure of 8 MPa, and a compression time of 3 minutes, and the porosity after compression measured is 30% or more.
[0042] [4] The electrical storage device separator according to any one of items [1] to [3], wherein in the covering layer, the amount of the particulate polymer is 1 part by mass or more and 50 parts by mass or less relative to 100 parts by mass of the inorganic filler contained in the covering layer,
[0043] The cover layer is formed in an inclined shape so as to become thicker toward the protruding particulate polymer.
[0044] [5] A separator for a storage device according to item [4], wherein, when the thickness of the inorganic filler portion of the covering layer is set to L1, and the maximum distance from the boundary line between the substrate and the covering layer to the outer surface of the inorganic filler of the covering layer formed into the inclined shape is set to L2, the average value of the inclination rate L2 / L1 of the covering layer is greater than 1.2.
[0045] [6] A separator for a storage device according to item [4] or [5], wherein when the thickness of the inorganic filler portion of the above-mentioned covering layer is set to L1, the maximum distance from the boundary line between the substrate and the covering layer to the outer surface of the inorganic filler of the above-mentioned covering layer formed into the above-mentioned inclined shape is set to L2, and the maximum distance from the boundary line between the substrate and the covering layer to the outline of the above-mentioned protruding granular polymer is set to L3, the average value of the coverage rate of the protruding portion of the above-mentioned protruding granular polymer (L2-L1) / (L3-L1) is greater than 0.4.
[0046] [7] The electrical storage device separator according to any one of items [1] to [6], wherein the particulate polymer includes at least one selected from the group consisting of a (meth)acrylic polymer, a styrene-butadiene copolymer, and a copolymer containing fluorine atoms.
[0047] [8] The electrical storage device separator according to any one of items [1] to [6], wherein the particulate polymer comprises a copolymer containing (meth)acrylic acid, butyl (meth)acrylate, and ethylhexyl (meth)acrylate as monomers.
[0048] [9] The electrical storage device separator according to any one of items [1] to [6], wherein the particulate polymer comprises a copolymer containing a polyfunctional (meth)acrylate as a monomer.
[0049]
[10] An electric storage device comprising the electric storage device separator according to any one of items [1] to [9].
[0050] Other examples of implementation of the present application are listed below.
[0051]
[11] A separator for an electrical storage device, comprising a substrate and a covering layer, wherein the substrate is a polyolefin microporous membrane containing polyolefin as a main component, and the covering layer is disposed on at least one surface of the substrate.
[0052] The above-mentioned covering layer comprises a granular polymer of a thermoplastic polymer and an inorganic filler,
[0053] The particulate polymer includes a protruding particulate polymer, wherein the protruding particulate polymer protrudes from the covering layer by 0.1 times or more the thickness of the inorganic filler portion of the covering layer.
[0054]
[12] The electrical storage device separator according to item
[11] , wherein the film thickness of the substrate is 1 μm to 30 μm, and the air permeability is 500 sec / 100 cm 3 The porosity after compression measured in a compression test under the conditions of a temperature of 70° C., a pressure of 8 MPa and a compression time of 3 minutes is 30% or more.
[0055]
[13] The electrical storage device separator according to item
[11] or
[12] , wherein the polyolefin microporous membrane has a crystal long period of 37.0 nm or more as measured by a small-angle X-ray scattering (SAXS) method.
[0056]
[14] The electrical storage device separator according to any one of items
[11] to
[13] , wherein in the covering layer, the amount of the granular polymer is 1 part by mass or more and 50 parts by mass or less relative to 100 parts by mass of the inorganic filler contained in the covering layer.
[0057]
[15] The electrical storage device separator according to any one of items
[11] to
[14] , wherein the cover layer is formed in an inclined shape so as to become thicker toward the protruding particulate polymer.
[0058]
[16] The electrical storage device separator according to any one of items
[11] to
[15] , wherein 20% or more of the protruding particulate polymer is in contact with the surface of the substrate.
[0059]
[17] The electrical storage device separator according to any one of items
[11] to
[16] , wherein the 180° peel strength of the cover layer from the substrate is 200 gf / cm or more.
[0060]
[18] The electrical storage device separator according to any one of items
[11] to
[17] , wherein the average number of the protruding particulate polymers adjacent to any one of the protruding particulate polymers is less than 2.
[0061]
[19] The electrical storage device separator according to any one of items
[11] to
[18] , wherein the ratio of the average particle size of the protruding granular polymer to the average particle size of the inorganic filler is greater than 10.
[0062]
[20] A separator for a storage device according to any one of items
[11] to
[19] , wherein when the thickness of the inorganic filler portion of the covering layer is set to L1, and the maximum distance from the boundary line between the substrate and the covering layer to the outer surface of the inorganic filler of the covering layer formed into the inclined shape is set to L2, the average value of the inclination rate L2 / L1 of the covering layer is greater than 1.2.
[0063]
[21] A separator for a storage device according to any one of items
[11] to
[20] , wherein when the thickness of the inorganic filler portion of the above-mentioned covering layer is set to L1, the maximum distance from the boundary line between the substrate and the covering layer to the outer surface of the inorganic filler of the above-mentioned covering layer formed into the above-mentioned inclined shape is set to L2, and the maximum distance from the boundary line between the substrate and the covering layer to the outline of the above-mentioned protruding granular polymer is set to L3, the average value of the coverage rate of the protruding portion of the above-mentioned protruding granular polymer (L2-L1) / (L3-L1) is greater than 0.4.
[0064]
[22] The electrical storage device separator according to any one of items
[11] to
[21] , wherein the number of the protruding granular polymers is 50% or more of the total number of the granular polymers contained in the covering layer.
[0065]
[23] A separator for a storage battery device according to any one of items
[11] to
[22] , wherein the number of other protruding granular polymers present within a radius of 10 μm from any one of the protruding granular polymers is less than 60.
[0066]
[24] The electrical storage device separator according to any one of items
[11] to
[23] , wherein the dichloromethane soluble component in the electrical storage device separator is 0.05 mass % or more and 0.80 mass % or less relative to the total mass of the electrical storage device separator.
[0067]
[25] The electrical storage device separator according to any one of items
[11] to
[24] , wherein the total amount of metal cations contained in the covering layer is greater than or equal to 0.1 ppm and less than or equal to 100 ppm based on the total mass of the covering layer.
[0068]
[26] The electrical storage device separator according to any one of items
[11] to
[25] , wherein the cover layer contains a water-soluble polymer.
[0069]
[27] The electrical storage device separator according to item
[26] , wherein the content of the water-soluble polymer is 0.04 parts by mass or more and less than 2 parts by mass based on 100 parts by mass of the inorganic filler.
[0070]
[28] The electrical storage device separator according to any one of items
[11] to
[27] , wherein a thickness of any one of the covering layers disposed on at least one of the substrates is greater than or equal to 0.3 μm and less than or equal to 1.3 μm.
[0071]
[29] The electrical storage device separator according to any one of items
[11] to
[28] , wherein the particulate polymer comprises at least one selected from the group consisting of a (meth)acrylic polymer, a styrene-butadiene copolymer, and a copolymer containing fluorine atoms.
[0072]
[30] The electrical storage device separator according to any one of items
[11] to
[28] , wherein the particulate polymer comprises a copolymer containing (meth)acrylic acid, butyl (meth)acrylate, and ethylhexyl (meth)acrylate as monomers.
[0073]
[31] The electrical storage device separator according to any one of items
[11] to
[28] , wherein the particulate polymer comprises a copolymer containing a polyfunctional (meth)acrylate as a monomer.
[0074]
[32] The electrical storage device separator according to any one of items
[11] to
[31] , wherein the particulate polymer is a primary particle.
[0075]
[33] The electrical storage device separator according to item
[32] , wherein the average particle size of the primary particles is 1 μm or more and 10 μm or less.
[0076]
[34] The electrical storage device separator according to any one of items
[11] to
[33] , wherein the thermal shrinkage in the TD direction at 130° C. for 1 hour is 5% or less.
[0077]
[35] The electrical storage device separator according to any one of items
[11] to
[34] , wherein the thermal shrinkage in the TD direction at 150° C. for 1 hour is 5% or less.
[0078]
[36] An electric storage device comprising the electric storage device separator according to any one of
[11] to
[35] .
[0079] Effects of the Invention
[0080] According to the present application, a separator for an electrical storage device having high adhesive force with an electrode and low thermal shrinkage and capable of improving cycle characteristics and output characteristics of the electrical storage device, and an electrical storage device having the same can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0081] Figure 1 It is a schematic diagram of the surface of the covering layer of the electrical storage device separator according to the present embodiment.
[0082] Figure 2 yes Figure 1 Schematic diagram of the AA section.
[0083] Figure 3 is an example of an approximate power curve relating porosity after compression and air permeability after compression. DETAILED DESCRIPTION
[0084] Hereinafter, an exemplary embodiment of the present application (hereinafter abbreviated as “the present embodiment”) will be described in detail, but the present application is not limited to the present embodiment.
[0085] In this specification, the longitudinal direction (MD) refers to the machine direction in which the microporous membrane is continuously formed, and the transverse direction (TD) refers to the direction crossing the MD of the microporous membrane at an angle of 90°.
[0086] In this specification, the upper limit and lower limit of each numerical range can be combined arbitrarily. In addition, a certain component contains a specific component as a main component, which means that the content of the specific component occupies the most mass in the mass of the component. Unless otherwise specified, the physical properties or numerical values recorded in this specification are measured or calculated by the method described in the examples.
[0087] 《Separators for power storage equipment》
[0088] The electrical storage device separator of the present embodiment includes a substrate which is a polyolefin microporous membrane containing polyolefin as a main component and a covering layer disposed on at least one surface of the substrate. The covering layer includes a granular polymer of a thermoplastic polymer and an inorganic filler.
[0089] 〈Amount of granular polymer〉
[0090] The amount of the granular polymer is 1 mass part or more and 50 mass parts or less relative to 100 mass parts of the inorganic filler, preferably 3 mass parts or more and 50 mass parts or less, more preferably 5 mass parts or more and 30 mass parts or less, and further preferably 10 mass parts or more and 25 mass parts or less. By making the amount of the granular polymer 1 mass part or more and 50 mass parts or less, it is possible to maintain ion permeability and improve adhesion to the electrode. In addition, from the viewpoint of improving heat-resistant shrinkage, it is preferably 10 mass parts or less.
[0091] 〈Protrusion amount of granular polymer〉
[0092] The particulate polymer includes a protruding particulate polymer that protrudes from the covering layer by 0.1 times or more the thickness of the inorganic filler portion of the covering layer.
[0093] In the present application, the "thickness of the inorganic filler portion of the covering layer" refers to the distance (L1) between the surface of the polyolefin microporous membrane and the outermost surface of the layer (layer formed by the inorganic filler) stacked thereon, which is measured based on the SEM image of the cross section of the covering layer. It should be noted that the "inorganic filler portion" refers to the portion that does not contain granular polymers and deviates from the center of each protruding granular polymer in the horizontal direction (the surface direction of the covering layer) by more than 1.5D when the diameter of each protruding granular polymer is set to D. The measurement conditions are described in the Example column.
[0094] By making the protrusion of the granular polymer more than 0.1 times the thickness of the inorganic filler part of the covering layer, the adhesion to the electrode can be improved. In addition, by making the protrusion of the granular polymer more than 0.1 times the thickness of the inorganic filler part of the covering layer, a gap is formed between the separator and the electrode. The gap can be used to alleviate the influence of internal expansion accompanied by charging and discharging of the storage device, etc., and the deformation of the winding body can be suppressed, and the cycle characteristics can be improved. In particular, with respect to the substrate having the following characteristics (6) and / or (7), by combining a large-particle granular polymer with a protrusion of more than 0.1 times the thickness of the covering layer, not only the air permeability of the substrate part that does not contact the granular polymer when bonding with the electrode is well maintained, but also the air permeability of the substrate part (the part that bears the load) that contacts the electrode with the help of the granular polymer is well maintained. As a result, it is found that: excellent cycle characteristics and output characteristics can be achieved. From this point of view, the protrusion of the granular polymer is preferably more than 0.2 times and more than 0.3 times. From the viewpoint of suppressing the particulate polymer from falling off the separator, the protrusion of the particulate polymer is preferably 5 times or less, more preferably 4 times or less, 3 times or less, 2 times or less, 1 time or less, or 0.4 times or less.
[0095] In the present specification, "protrusion" means: exceeding the "thickness of the inorganic filler portion of the covering layer", and the granular polymer protrudes toward the surface side of the covering layer. In the portion where the granular polymer protrudes (hereinafter referred to as the "protruding portion"), the granular polymer does not necessarily have to be exposed to the surface of the covering layer, and at least a part or all of the protruding portion can be covered with an inorganic filler. From the viewpoint of preventing the granular polymer from sliding off the covering layer and obtaining a higher adhesion, it is preferred that at least a part of the periphery of the protruding portion is covered with an inorganic filler. In addition, from the viewpoint of ensuring the contact area between the granular polymer and the electrode and obtaining a higher adhesion, it is preferred that the central part of the protruding portion is exposed to the surface of the covering layer.
[0096] In the present application, "a state in which the granular polymer protrudes from the covering layer by more than 0.1 times the thickness of the inorganic filler portion of the covering layer" means that when the thickness of the inorganic filler portion of the covering layer measured from the SEM image of the cross section of the covering layer is set as L1 and the maximum distance from the boundary line between the substrate and the covering layer to the contour of the protruding granular polymer is set as L3, the average value of the ratio (L3-L1) / L1 is greater than 0.1. In the present application, "the maximum distance from the boundary line between the substrate and the covering layer to the contour of the protruding granular polymer" means the distance from the boundary line between the substrate and the covering layer to the farthest point in the contour of the protruding granular polymer.
[0097] In the present application, in other words, "a state in which the granular polymer protrudes from the covering layer by more than 0.1 times the thickness of the inorganic filler portion of the covering layer" means that the maximum distance (L3) from the boundary line between the substrate and the covering layer measured based on the SEM image of the cross-section of the covering layer to the contour of the protruding granular polymer is more than 1.1 times the thickness (L1) of the inorganic filler portion of the covering layer.
[0098] <Inclined morphology of the covering layer, contact ratio of the particulate polymer to the substrate, 180° peel strength, average number of adjacent particulate polymers and ratio of average particle size>
[0099] The separator for storage device of the present embodiment preferably has one or more of the following features (1) to (5). (1) The covering layer is formed in an inclined shape so as to become thicker toward the protruding granular polymer; (2) 20% or more of the protruding granular polymer contacts the surface of the substrate; (3) The 180° peel strength of the covering layer from the substrate (hereinafter also referred to as "180° peel strength") is 200 gf / cm (196 N / m) or more; (4) The average number of protruding granular polymers adjacent to any one protruding granular polymer (hereinafter also referred to as "the average number of adjacent granular polymers") is less than 2; (5) The ratio of the average particle size of the protruding granular polymer to the average particle size of the inorganic filler, that is, the ratio calculated as the average particle size of the granular polymer / the average particle size of the inorganic filler (hereinafter also referred to as "the average particle size ratio") is greater than 10. By having at least one of the above-mentioned features (1) to (5), it is possible to provide a separator for an electrical storage device having a higher adhesive force to an electrode and a smaller thermal shrinkage rate.
[0100] Features(1):
[0101] Regarding the separator for the storage device, the covering layer is preferably formed in an inclined shape in such a way that it becomes thicker toward the protruding granular polymer. This prevents the granular polymer from sliding off the covering layer, and improves the adhesion to the electrode. In the present application specification, "inclined" means: when the thickness of the inorganic filler part of the covering layer is set to L1, and the maximum distance from the boundary line between the substrate and the covering layer to the outer surface of the inorganic filler forming the inclined covering layer is set to L2, the average value of the inclination rate L2 / L1 of the covering layer is greater than 1.1. For an example of the relationship between L1 and L2, please refer to Figure 2Schematic diagram of the invention. The inclination is preferably that the thickness of the covering layer changes continuously in a manner that the covering layer gradually thickens toward the protruding granular polymer, and preferably does not include discontinuous changes in the defects of the covering layer. Due to the absence of defects in the covering layer, there is a tendency for heat resistance and cycle characteristics to improve. The inclination may be more gentle the farther away from the protruding granular polymer, and the steeper the protrusion closer to the protruding granular polymer. In addition, in the case where the inorganic filler covers at least a part or all of the protruding portion, the inclination on the protruding portion may become gentle again toward the center of the protruding portion. The average value of the inclination rate L2 / L1 of the covering layer is preferably greater than 1.2, greater than 1.3, greater than 1.4, greater than 1.5 or greater than 1.7.
[0102] By forming the covering layer in an inclined shape so as to become thicker toward the protruding granular polymer, the inorganic filler can exist along the contour of the granular polymer and cover at least a portion or all of the protruding portion. The inorganic filler preferably exists along the contour of the granular polymer and covers a portion of the periphery of the protruding portion. In addition, the vicinity of the center of the protruding portion is preferably exposed to the surface of the covering layer. If the maximum distance from the boundary line of the substrate-covering layer to the contour of the protruding granular polymer (the distance from the boundary line of the substrate-covering layer to the farthest point in the contour of the protruding granular polymer) is set to L3, the average value of the coverage of the protruding portion (L2-L1) / (L3-L1) is preferably greater than 0.4. As an example of the relationship between L1, L2 and L3, please refer to Figure 2 Schematic diagram. By making the average value of the inclination L2 / L1 be 1.1 or more or the average value of the coverage (L2-L1) / (L3-L1) be 0.4 or more, the granular polymer is prevented from sliding off the covering layer, and the adhesion to the electrode is improved. The upper limit of the average value of the inclination L2 / L1 is not particularly limited. From the viewpoint of ensuring the bonding area between the granular polymer and the electrode and improving the adhesion to the electrode, it can be 5.0 or less, 4.0 or less, 3.0 or less, 2.8 or less, 2.5 or less, 2.3 or less, 2.0 or less, or 1.8 or less. In addition, the upper limit of the coverage (L2-L1) / (L3-L1) is preferably less than 1.0, 0.9 or less, 0.8 or less, or 0.7 or less. The coverage being 1.0 or more means that the inorganic filler present in the protruding portion of the granular polymer reaches the uppermost portion of the contour of the protruding granular polymer (the point farthest from the boundary line of the substrate-covering layer). When the coverage is less than 1.0, the contact area between the particulate polymer and the electrode is ensured, and the adhesive force to the electrode is improved. When the coverage is less than 0.8, the contact area between the particulate polymer and the electrode is further increased, and the adhesive force to the electrode is further improved.
[0103] Features (2):
[0104] Regarding the separator for storage device, the contact rate between the granular polymer protruding from the covering layer and the surface of the substrate is preferably 20% or more, more preferably 50% or more, and further preferably 70% or more. The "contact rate" is calculated based on the image of the cross section of the covering layer of the separator for storage device using SEM. By increasing the granular polymer protruding from the covering layer and in contact with the substrate, the bonding force between the substrate and the granular polymer is further improved, the 180° peel strength is improved, and the bonding force with the electrode is improved. The upper limit of the contact rate between the granular polymer protruding from the covering layer and the surface of the substrate is not particularly limited, and can be less than 100% or 100%.
[0105] Features (3):
[0106] Regarding the separator for storage device, the 180° peel strength is preferably 200 gf / cm or more, more preferably 230 gf / cm or more, and further preferably 250 gf / cm or more. "180° peel strength" refers to the strength when the covering layer is peeled off in a manner that the surface of the covering layer facing the substrate is 180° relative to the substrate. By making the 180° peel strength 200 gf / cm or more, the adhesion to the electrode is improved and thermal shrinkage is suppressed. The upper limit of the 180° peel strength is not particularly limited and can be 500 gf / cm or less.
[0107] Features (4):
[0108] Regarding the separator for the storage device, the average number of adjacent granular polymers is preferably less than 2, and more preferably less than 1. "Adjacent" means that according to the image when the surface of the covering layer of the separator for the storage device is observed using SEM, the shortest distance between the outer edge of a granular polymer and the outer edge of other granular polymers is less than 0.2 μm. The average number of adjacent granular polymers is less than 2, which means that the granular polymers are uniformly dispersed in the covering layer, thereby improving the 180° peel strength, improving the adhesion to the electrode, suppressing thermal shrinkage, and ensuring the uniformity of the thickness of the covering layer. The lower limit of the average number of adjacent granular polymers is not particularly limited and can be greater than 0 or 0.
[0109] Features (5):
[0110] Regarding the separator for power storage devices, the ratio of the average particle size of the protruding granular polymer to the average particle size of the inorganic filler is preferably greater than 10. The respective "average particle size" is measured based on the image when the surface of the covering layer of the separator for power storage devices is observed using SEM. The measurement conditions are described in the first embodiment column. By making the ratio of the average particle size greater than 10, it is easy to form a structure in which the granular polymer protrudes from the surface of the covering layer, thereby improving the adhesion to the electrode and suppressing thermal shrinkage. From the viewpoint of both the permeability and adhesion of the separator, the upper limit of the ratio of the average particle size is preferably less than 50, more preferably less than 35, and further preferably less than 25, less than 22, and less than 20.
[0111] The separator for an electrical storage device of the present embodiment may have any combination of the above-mentioned features (1) to (5), namely: (1) and (2); (1) and (3); (1) and (4); (1) and (5); (2) and (3); (2) and (4); (2) and (5); (3) and (4); (3) and (5); (4) and (5); (1), (2) and (3); (1), (2) and (4); (1), (2) and (5); (1), (3) and (4); (1), (3) and (5); ) and (5); (1), (4) and (5); (2), (3) and (4); (2), (3) and (5); (2), (4) and (5); (3), (4) and (5); (1), (2), (3) and (4); (1), (2), (3) and (5); (1), (2), (4) and (5); (1), (3), (4) and (5); (2), (3), (4) and (5); or a combination of (1), (2), (3), (4) and (5). Among these, from the viewpoint of higher adhesive force and smaller thermal shrinkage rate, the combination of (1), (2) and (3) is preferred, that is, the covering layer is formed in an inclined shape so as to become thicker toward the protruding particulate polymer, the contact rate of the particulate polymer protruding from the covering layer with the substrate surface in the covering layer is 20% or more, and the 180° peel strength is 200 gf / cm or more.
[0112] 〈Number of granular polymers within a radius of 10 μm〉
[0113] In the separator for storage device of the present embodiment, the number of other protruding particulate polymers within a radius of 10 μm from any protruding particulate polymer is preferably less than 60, more preferably less than 40, further preferably less than 15, and further preferably less than 5. Thus, the deviation of the adhesive force can be suppressed. The lower limit of the number of particulate polymers within a radius of 10 μm is not particularly limited and can be 0. In order to make the particulate polymer appropriately dense and improve the adhesive force, it can be set to 1 or more.
[0114] 〈Dichloromethane soluble components〉
[0115] In the separator for storage device of the present embodiment, the dichloromethane soluble component is preferably 0.05 mass % or more and 0.80 mass % or less, based on the total mass of the separator for storage device, more preferably 0.10 mass % or more and 0.60 mass % or less, and further preferably 0.15 mass % or more and 0.50 mass % or less. The "soluble component" of dichloromethane refers to: when the separator is immersed in dichloromethane, the component extracted into dichloromethane. The plasticizer mixed when manufacturing the substrate is mainly extracted as the dichloromethane soluble component. By containing more than 0.10 mass % of dichloromethane soluble components, the bonding force between the substrate and the covering layer is further improved, and it is easier to adjust the 180° peel strength to more than 200gf / cm. By making the dichloromethane soluble component less than 0.60 mass %, the internal resistance of the battery can be reduced. As a method for adjusting the dichloromethane soluble component to 0.05 mass % or more and 0.80 mass % or less, in the plasticizer extraction step when manufacturing the substrate, if it is an intermittent method, the adjustment of the extraction time, the type of extraction solvent, the temperature of the extraction solvent, the number of extractions, etc. can be listed; if it is a continuous method, the adjustment of the extraction time, the type of extraction solvent, the temperature of the extraction solvent, the supply amount of the extraction solvent, etc. can be listed.
[0116] 〈Metal cations〉
[0117] In the separator for storage device of the present embodiment, the total amount of metal cations contained in the covering layer is preferably 0.1 ppm or more and 100 ppm or less, more preferably 0.1 ppm or more and 70 ppm or less, and further preferably 0.1 ppm or more and 50 ppm or less, based on the total mass of the covering layer. If the total amount of metal cations is adjusted to be less, the inorganic filler and the granular polymer will be evenly dispersed and easily coated in the formation of the covering layer. As metal cations, sodium ions (Na + ), calcium ions (Ca 2+ ) and magnesium ions (Mg 2+ ) etc. As a method for adjusting the total amount of metal cations to 0.1 ppm or more and 100 ppm or less, a method of washing the filler to be the raw material of the covering layer with water before use can be cited. The washing frequency may be once or twice or more, and the more the washing frequency increases, the less the total amount of metal cations contained in the filler becomes.
[0118] 〈Heat shrinkage ratio〉
[0119] The thermal shrinkage of TD of the separator for storage device of this embodiment at 130°C for 1 hour is preferably 5% or less, more preferably 0% or more and 3% or less, and further preferably 0% or more and 1% or less. The thermal shrinkage of TD at 150°C for 1 hour is preferably 5% or less, more preferably 0% or more and 3% or less, and further preferably 0% or more and 1% or less. Here, if the thermal shrinkage of TD is 5% or less, it can be more effectively suppressed that short circuit occurs in parts other than the part to which external force is applied when heat is released due to short circuit during impact test. Thus, it is possible to more reliably prevent the temperature rise of the entire battery and the smoke and fire that may occur therefrom. The thermal shrinkage of the separator can be adjusted by appropriately combining the stretching operation of the above-mentioned substrate with the heat treatment. While suppressing the thermal shrinkage of TD, the thermal shrinkage of MD is also preferably 5% or less, more preferably 0% or more and 3% or less, and further preferably 0% or more and 1% or less.
[0120] <Air permeability of separator>
[0121] The air permeability of the electric storage device separator is preferably 10 seconds / 100 cm 3 Above and 10000 sec / 100cm 3 Less than 10 seconds / 100 cm 3 Above and 1000 seconds / 100cm 3 Below, more preferably 50 seconds / 100cm 3 Above and 500 seconds / 100cm 3 Below, particularly preferably 80 seconds / 100cm 3 Above and 250 seconds / 100cm 3 Below. This results in high ion permeability. Air permeability is the air permeability resistance measured in accordance with JIS P-8117.
[0122] 〈Base Material〉
[0123] The substrate is a polyolefin microporous membrane containing polyolefin as a main component, preferably having the following characteristics (6), (7) or a combination thereof: (6) The membrane thickness is 1 μm to 30 μm, and the air permeability is 500 sec / 100 cm 3 The porosity after compression measured in a compression test under the conditions of 70°C, 8 MPa and 3 minutes is 30% or more. (7) The long crystal period of the polyolefin microporous membrane measured by small angle X-ray scattering (SAXS) is 37.0 nm or more.
[0124] Features (6):
[0125] Although not bound by theory, it is believed that the polyolefin microporous membrane has a film thickness of 500 sec / 100 cm in the range of 1 μm to 30 μm. 3 The following air permeability and porosity after compression of more than 30% can reduce the resistance of the polyolefin microporous membrane or suppress the resistance increase after the pressurization process when a non-aqueous secondary battery is made, for example, using a polyolefin microporous membrane as a separator, thereby achieving high output and high cycle characteristics of the non-aqueous secondary battery. The use of a polyolefin microporous membrane to suppress the increase in resistance is significant when electrodes that are easy to expand and shrink are used in the battery cells of non-aqueous secondary batteries, and when high-capacity electrodes or silicon (Si) negative electrodes used in automotive batteries are used. The method of performing a compression test under the conditions of a temperature of 70°C, a pressure of 8MPa and a compression time of 3 minutes is described in detail in the examples.
[0126] It can be considered that the porosity after compression is related to the structure of the main component of the polyolefin microporous membrane that is responsible for reducing resistance and / or suppressing resistance increase in the non-aqueous secondary battery. From the viewpoint of the above description, the porosity of the polyolefin microporous membrane after compression is preferably 31% or more, more preferably 32% or more, and further preferably 33% or more. The upper limit of the porosity of the polyolefin microporous membrane after compression can be determined based on the porosity before compression, for example, preferably 60% or less, and further preferably 50% or less.
[0127] The porosity after compression of the polyolefin microporous membrane can be adjusted within the numerical range described above by, for example, controlling the molecular weight of the polyolefin raw material, the molecular weight and content of the polyethylene raw material, the stretch ratio in the biaxial stretching process, the preheating coefficient in the biaxial stretching process, the stretching coefficient in the biaxial stretching process, the MD / TD stretching temperature in the biaxial stretching process, the heat fixing temperature, etc. in the manufacturing process of the polyolefin microporous membrane. Alternatively, the porosity after compression of the polyolefin microporous membrane can be adjusted within the numerical range described above by controlling the molecular weight of the polyolefin raw material, the molecular weight and content of the polyethylene raw material, the stretch ratio in the biaxial stretching process, the preheating coefficient in the biaxial stretching process, the stretching coefficient in the biaxial stretching process, the ratio of the preheating coefficient to the stretching coefficient, etc.
[0128] From the perspective of determining the structure of the main component of the membrane that reduces resistance and / or suppresses resistance increase and achieves high output and high cycle characteristics in a non-aqueous secondary battery, it is preferred to compare the porosity before and after the compression test for the polyolefin microporous membrane. The porosity of the polyolefin microporous membrane before the compression test or the porosity not provided for the compression test (hereinafter referred to as "porosity") is measured by the method described in the examples, and its preferred numerical range is as described below.
[0129] On the basis of reducing the resistance and suppressing the increase of resistance as described above, from the viewpoint of miniaturization, the thickness of the polyolefin microporous membrane is preferably 3 μm to 20 μm, more preferably 5 μm to 16 μm, and further preferably 6 μm to 13 μm. The thickness of the microporous membrane can be optimized by, for example, the distance between the casting rolls, the stretching ratio in the stretching process, etc.
[0130] The air permeability of the polyolefin microporous membrane before compression can be determined by the item "Air permeability before compression (sec / 100cm 3 )”. Based on the reduction of the resistance described above and the suppression of the resistance increase, from the perspective of the ion permeability of the microporous membrane and the high output of the non-aqueous secondary battery, the air permeability of the polyolefin microporous membrane is preferably 400sec / 100cm 3 Less than, more preferably 300sec / 100cm 3 Below, more preferably 200sec / 100cm 3 Below, particularly preferably 160sec / 100cm 3 From the viewpoint of the mechanical strength of the microporous membrane, 40 sec / 100 cm is preferred. 3 The air permeability of the microporous membrane can be optimized in the same manner as the control method of the porosity after compression described above.
[0131] Features (7):
[0132] Although not bound by theory, it can be considered that: by making the polyolefin microporous membrane have a crystal long period of more than 37.0nm, it is surprising that the structural uniformity and compression resistance of the polyolefin microporous membrane are improved, and the reaction uniformity in the non-aqueous secondary battery is also improved. Thus, after the pressurization process when, for example, a polyolefin microporous membrane is used as a separator to make a non-aqueous secondary battery, the high output and high cycle characteristics of the non-aqueous secondary battery can also be achieved. The improvement of the structural uniformity and compression resistance of the polyolefin microporous membrane is significant when an electrode that is prone to expansion and contraction is used in the battery cell of the non-aqueous secondary battery, and is more significant when a high-capacity electrode or a silicon (Si) negative electrode used in a vehicle-mounted battery is used.
[0133] The SAXS measurement of the polyolefin microporous membrane is described in detail in the examples. Although not bound by theory, it can be considered that the long crystal period obtained by SAXS measurement is related to the structure of polyethylene that improves the structural uniformity and compression resistance of the membrane and improves the reaction uniformity in the non-aqueous secondary battery. In addition, it can be considered that the long crystal period of the polyolefin microporous membrane is related to the porosity of the membrane after compression. From the viewpoint of the above description, the long crystal period of the polyolefin microporous membrane is preferably 37.0nm to 60.0nm, 38.0nm to 55.0nm, 40.0nm to 50.0nm or 42.0nm to 50.0nm.
[0134] The crystal long period of the polyolefin microporous membrane can be adjusted within the numerical range described above by controlling, for example, the molecular weight of the polyolefin raw material, the molecular weight and content of the polyethylene raw material, the stretching ratio during the biaxial stretching process, the preheating coefficient during the biaxial stretching process, the stretching coefficient during the biaxial stretching process, the MD / TD stretching temperature during the biaxial stretching process, the heat fixing temperature, etc. in the manufacturing process of the polyolefin microporous membrane.
[0135] Regarding the thickness of the polyolefin microporous membrane, in order to have mechanical strength and maintain insulation, the lower limit is 1 μm or more. By ensuring the amount of resin per unit area, in order to improve the safety of the battery, the film thickness is preferably 2 μm or more, more preferably 3 μm or more. In the case of lithium dendrite growth, in order to ensure insulation, the film thickness is preferably 6 μm or more, more preferably 10 μm or more. From the perspective of high capacity of non-aqueous secondary batteries, the film thickness of the polyolefin microporous membrane is preferably 16 μm or less. The thickness of the microporous membrane can be adjusted by controlling the distance between the rollers of the casting roll, the stretching ratio in the stretching process, and the like.
[0136] The air permeability of the polyolefin microporous membrane before compression is preferably 30 sec / 100 cm 3 Above and 250sec / 100cm 3 Less than, more preferably 40sec / 100cm 3 Above and 200sec / 100cm 3 Below, more preferably 50sec / 100cm 3 Above and 180sec / 100cm 3 Below, more preferably 60sec / 100cm 3 Above and 150sec / 100cm 3 From the viewpoint of ensuring puncture strength, the air permeability of the microporous membrane before compression is preferably 40 sec / 100 cm 3 From the viewpoint of output characteristics, 200 sec / 100 cm is preferred. 3 the following.
[0137] Features (6) and (7) have the following in common:
[0138] As polyolefin microporous membranes, for example, porous membranes containing polyolefin resins can be listed; porous membranes containing resins such as polyethylene terephthalate, polycycloolefins, polyethersulfones, polyamides, polyimides, polyimide amides, polyaramids, polycycloolefins, nylon, and polytetrafluoroethylene on the basis of containing polyolefin resins; cloth (woven fabric) woven from polyolefin-based fibers; non-woven fabrics of polyolefin-based fibers, etc. Among these, from the viewpoints of reducing the resistance of the membrane or suppressing its increase, the compression resistance and structural uniformity of the membrane, preferably a microporous membrane containing a polyolefin resin (hereinafter referred to as a polyolefin resin porous membrane), and more preferably a microporous membrane containing polyethylene as the main component.
[0139] From the viewpoint of improving the isolation performance when forming a polyolefin microporous membrane for a non-aqueous secondary battery, the polyolefin resin porous membrane is preferably a porous membrane formed from a polyolefin resin composition, wherein the polyolefin resin in the polyolefin resin composition accounts for more than 50% by mass and less than 100% by mass of the resin component constituting the porous membrane.
[0140] Polyolefins have excellent coating properties when coating a coating liquid on the film, so they are advantageous for further reducing the thickness of the separator, which can increase the ratio of active materials in the power storage device and increase the capacity per unit volume. The polyolefin microporous membrane can use a material that has been used as a separator substrate in the past, preferably a microporous membrane with a fine pore size that does not have electronic conductivity but has ion conductivity and high resistance to organic solvents.
[0141] (Material of base material)
[0142] The substrate is a polyolefin microporous membrane containing polyolefin as a main component. "Containing ... as a main component" means that the mass of the target component (polyolefin) occupies the largest mass in the entire substrate. The content of polyolefin in the polyolefin microporous membrane is based on the total mass of the substrate, for example, more than 50 parts by mass, preferably 75 parts by mass or more, more preferably 85 parts by mass or more, further preferably 90 parts by mass or more, further preferably 95 parts by mass or more, particularly preferably 98 parts by mass or more, and can be 100 parts by mass.
[0143] The polyolefin is not particularly limited, and may be a polyolefin that can be used in conventional extrusion, injection, inflation, and blow molding. Examples of the polyolefin include homopolymers using ethylene, propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, and 1-octene as monomers; and copolymers and multi-stage polymers of two or more of these monomers. These homopolymers, copolymers, and multi-stage polymers may be used alone or in combination of two or more.
[0144] As polyolefins, from the viewpoints of reducing the resistance of the film or suppressing its increase, the compression resistance and structural uniformity of the film, for example, polyethylene, polypropylene and polybutene can be listed. More specifically, low-density polyethylene, linear low-density polyethylene, medium-density polyethylene, high-density polyethylene, ultra-high molecular weight polyethylene, isotactic polypropylene, atactic polypropylene, ethylene-propylene random copolymer, polybutene and ethylene-propylene rubber can be listed.
[0145] These can be used alone or in combination of two or more. Among these, as polyolefin, from the viewpoint of the isolation property of the pores being blocked by heat melting, at least one selected from the group consisting of low-density polyethylene, linear low-density polyethylene, medium-density polyethylene, high-density polyethylene and ultra-high molecular weight polyethylene is preferred. In particular, from the viewpoint of low melting point and high strength, high-density polyethylene is preferred, and more preferably a density of 0.93 g / cm2 measured in accordance with JIS K 7112 is preferred. 3 The polymerization catalyst used to produce these polyethylenes is not particularly limited, and examples thereof include Ziegler-Natta catalysts, Phillips catalysts, and metallocene catalysts. The main component of the polyolefin is preferably polyethylene, and the content of polyethylene in the substrate relative to the total mass of the polyolefin is preferably 50 parts by mass or more.
[0146] In order to improve the heat resistance of the substrate, the polyolefin microporous membrane preferably contains polypropylene and polyolefins other than polypropylene. As polyolefin resins other than polypropylene, for example, homopolymers with ethylene, 1-butene, 4-methyl-1-pentene, 1-hexene and 1-octene as monomers can be listed; and copolymers and multi-stage polymers of two or more of these monomers.
[0147] The amount of polypropylene in the substrate relative to the total mass of polyolefin (polypropylene / polyolefin) is not particularly limited, and from the viewpoint of taking into account both heat resistance and good barrier function, it is preferably 1 to 35 parts by mass, more preferably 3 to 20 parts by mass, and further preferably 4 to 10 parts by mass. From the same viewpoint, the content ratio of olefin resins other than polypropylene, such as polyethylene, relative to the total mass of polyolefin (olefin resins other than polypropylene / polyolefin) in the polyolefin microporous membrane is preferably 65 to 99 parts by mass, more preferably 80 to 97 parts by mass, and further preferably 90 to 96 parts by mass.
[0148] From the viewpoints of crystallinity, high strength, and compression resistance when forming a polyolefin microporous membrane for a non-aqueous secondary battery, the polyolefin resin porous membrane is preferably a porous membrane formed by a polyethylene composition, wherein the polyethylene in the polyethylene composition occupies more than 50% by mass and less than 100% by mass of the resin component constituting the microporous membrane. The proportion of polyethylene in the resin component constituting the porous membrane is more preferably more than 60% by mass and less than 100% by mass, further preferably more than 70% by mass and less than 100% by mass, and further preferably more than 90% by mass and less than 100% by mass.
[0149] In the case where the microporous membrane is a polyolefin resin porous membrane, the viscosity average molecular weight (Mv) of the polyolefin resin used as a raw material is preferably 30,000 or more and 6,000,000 or less, more preferably 80,000 or more and 3,000,000 or less, and further preferably 150,000 or more and 2,000,000 or less. If the viscosity average molecular weight is 30,000 or more, there is a tendency to present high strength due to the entanglement of polymers, so it is preferred. On the other hand, if the viscosity average molecular weight is 6,000,000 or less, it is preferred from the viewpoint of improving the moldability in the extrusion and stretching process.
[0150] When the polyolefin resin porous film includes polyethylene as the main component, from the viewpoint of the orientation and rigidity of the film, the lower limit of the Mv of at least one polyethylene is preferably 600,000 or more, more preferably 700,000 or more, and the Mv upper limit of polyethylene can be, for example, 2,000,000 or less. From the same viewpoint, among the polyolefin resins constituting the polyolefin resin porous film, the proportion occupied by the polyethylene with Mv of 700,000 or more is preferably 50% by mass or more, more preferably 60% by mass or more, further preferably 70% by mass or more, and can be 100% by mass. From the viewpoint of the fluidity reduction during the film melting and the short circuit resistance during the nail puncture test, among the polyolefin resins constituting the polyolefin resin porous film, the proportion occupied by the polyethylene with Mv of 600,000 or more is preferably 30% by mass or more, more preferably 50% by mass or more, further preferably 60% by mass or more, further preferably 70% by mass or more, and can be 100% by mass.
[0151] The viscosity average molecular weight (Mv) was calculated by the following formula based on the intrinsic viscosity [η] obtained by measuring at a measurement temperature of 135° C. using decalin as a solvent in accordance with ASTM-D4020.
[0152] Polyethylene: [η] = 6.77 × 10 -4 Mv 0.67 (Chiang formula)
[0153] Polypropylene: [η] = 1.10 × 10 -4 Mv 0.80
[0154] For example, instead of using a polyolefin having a viscosity average molecular weight of less than 1 million alone, a mixture of a polyolefin having a viscosity average molecular weight of 2 million and a polyolefin having a viscosity average molecular weight of 270,000 may be used, and the viscosity average molecular weight of the mixture may be less than 1 million.
[0155] The substrate may contain other resins besides polyolefin, for example, polyethylene terephthalate, polycycloolefin, polyethersulfone, polyamide, polyimide, polyimideamide, polyaramid, polycycloolefin, nylon, polytetrafluoroethylene and the like.
[0156] The substrate may contain optional additives. Such additives are not particularly limited, and examples thereof include plasticizers, polymers other than polyolefins; inorganic particles; antioxidants such as phenolic, phosphorus, and sulfur; metal soaps such as calcium stearate and zinc stearate; ultraviolet absorbers; light stabilizers; antistatic agents; antifogging agents; and coloring pigments. The total content of these additives is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, and further preferably 5 parts by mass or less relative to 100 parts by mass of the polyolefin resin in the polyolefin microporous membrane.
[0157] The substrate preferably contains a plasticizer. When the substrate contains a plasticizer, the bonding force between the substrate and the covering layer is improved, and it is easier to control the 180° peel strength to be more than 200gf / cm. The amount of the plasticizer is based on the total mass of the substrate, preferably 0.1 parts by mass or more and 1.6 parts by mass or less, more preferably 0.2 parts by mass or more and 1.2 parts by mass or less, and further preferably 0.3 parts by mass or more and 1.0 parts by mass or less. By making the amount of the plasticizer within the above range, the internal resistance of the battery can be reduced, and the bonding force between the substrate and the covering layer can be increased. As a plasticizer, hydrocarbons such as liquid paraffin, esters such as dioctyl phthalate and dibutyl phthalate, and higher alcohols such as oleyl alcohol and stearyl alcohol can be listed. Among these, the plasticizer is preferably liquid paraffin.
[0158] When the polyolefin resin porous membrane contains polyethylene as the main component, the crystal MDND plane (110) crystallite size of the polyethylene is preferably less than 28 nm. As described in detail in the examples, the MDND plane (110) crystallite size of the polyethylene can be measured by X-ray diffraction (XRD) or wide angle X-ray scattering (WAXS).
[0159] Although not bound by theory, when the MDND surface (110) crystallite size of polyethylene is less than 28.0nm, the polyolefin microporous membrane containing the polyethylene becomes rigid, and there is a tendency for the compression resistance of the membrane to increase, thereby, even after the pressurization process when manufacturing non-aqueous secondary batteries, high output and high cycle characteristics can be taken into account. From this point of view, the MDND surface (110) crystallite size of polyethylene is more preferably less than 27.0nm, further preferably 10.0nm to 27.0nm, further preferably 15.0nm to 26.0nm, particularly preferably 15.0nm to 25.0nm, and particularly preferably 15.0nm to 22.0nm. In particular, if the MDND surface (110) crystallite size of polyethylene is less than 22.0nm, the rigidity of the membrane is enhanced and the compression resistance is improved. The MDND plane (110) crystallite size of polyethylene can be adjusted to the numerical range described above by controlling, for example, the molecular weight of the polyolefin raw material, the molecular weight of the polyethylene raw material, the stretching ratio during the biaxial stretching process, the preheating coefficient during the biaxial stretching process, the stretching coefficient during the biaxial stretching process, etc. in the manufacturing process of the polyolefin microporous membrane.
[0160] From the viewpoint of making the membrane rigid and improving compression resistance, the melting point of the polyolefin resin contained in the polyolefin resin porous membrane is preferably above 120°C and below 150°C, more preferably in the range of above 125°C and below 140°C, and / or the 1st peak temperature of DSC is preferably in the range of 136°C to 144°C.
[0161] From the perspective of crystallinity, high strength, compression resistance, and resistance suppression when forming a polyolefin microporous membrane as a separator for a non-aqueous secondary battery, the proportion of polyethylene in the polyolefin resin is based on the mass of the entire polyolefin resin, preferably 30% by mass or more, more preferably 50% by mass or more, further preferably 70% by mass or more, and further preferably 80% by mass or more, and 100% by mass or less, preferably 97% by mass or less, and more preferably 95% by mass or less. It should be noted that if the proportion of polyethylene (PE) in the polyolefin resin is 100% by mass, it is preferred from the perspective of showing strength. If the proportion of PE in the polyolefin resin is 50% by mass or more, it is also preferred from the perspective of showing a fusing behavior with high responsiveness.
[0162] The polyolefin resin composition may contain any additives. Examples of additives include polymers other than polyolefin resins; inorganic fillers; antioxidants such as phenolic, phosphorus, and sulfur; metal soaps such as calcium stearate and zinc stearate; ultraviolet absorbers; light stabilizers; antistatic agents; antifogging agents; coloring pigments, etc. From the perspective of improving the barrier performance, the total amount of these additives added is preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less relative to 100% by mass of the polyolefin resin.
[0163] The type, molecular weight and composition of the polyolefin resin constituting the polyolefin resin porous membrane can be adjusted by controlling the type, molecular weight and blending ratio of polymer raw materials such as polyolefins in the manufacturing process of the polyolefin microporous membrane. In addition, a multilayer polyolefin resin microporous membrane having a structure in which two or more layers of the same or different polyolefin resin microporous membranes are stacked can also be adjusted as described above.
[0164] (Structure of base material)
[0165] The polyolefin microporous membrane has a porous structure in which a large number of very small pores are aggregated to form dense interconnected pores, and therefore has the following characteristics: in a state containing an electrolyte, the membrane has extremely excellent ion permeability and high strength.
[0166] From the viewpoint of high ion permeability and good rate characteristics, and from the viewpoint of reducing the volume occupied by the separator in a high-capacity battery and increasing the battery capacity, the average film thickness of the polyolefin microporous membrane before compression is preferably 1 μm to 16 μm, more preferably 3 μm to 13 μm, and further preferably 5 μm to 12 μm. The average film thickness of the polyolefin microporous membrane can be adjusted within the above numerical range by controlling the distance between the casting rolls, the casting gap, the stretching ratio during the biaxial stretching process, the HS ratio, the HS temperature, etc.
[0167] For example, from the perspective of reducing the resistance of the membrane after the pressurization process when manufacturing a non-aqueous secondary battery with a microporous membrane as a separator, taking into account the high output and high cycle characteristics of the battery, and achieving a constant membrane strength and low air permeability, the porosity of the microporous membrane before compression is preferably 20% or more, more preferably 35% or more, further preferably 38% or more, further preferably 40% or more, and particularly preferably 45% or more. In addition, from the perspective of battery safety and achieving a constant membrane strength and low air permeability, it is preferably 70% or less, more preferably 65% or less, and further preferably 60% or less. The porosity of the microporous membrane can be adjusted by controlling the mixing ratio of the polyolefin resin composition and the plasticizer, the stretching temperature, the stretching ratio, the heat setting temperature, the stretching ratio during heat setting, the relaxation rate during heat setting, etc., or by combining them.
[0168] From the viewpoint of achieving high ion permeability, excellent withstand voltage and high strength, the pore size of the microporous membrane is preferably 30 nm to 70 nm, more preferably 35 nm to 60 nm when measured by a semi-dry method. The pore size of the microporous membrane can be adjusted by controlling, for example, the stretching temperature, the stretching ratio, the heat setting temperature, the stretching ratio during heat setting, the relaxation rate during heat setting, etc., or by combining them.
[0169] From the viewpoint of reducing the fluidity of the film when it is melted and suppressing the short circuit between electrodes by the flow of the separator in the exothermic state during the nail penetration test, the melt flow index (MI) of the polyolefin microporous membrane is preferably 1.0 or less, more preferably 0.001 or more and 1.0 or less, further preferably 0.005 or more and 0.8 or less, and further preferably 0.01 or more and 0.4 or less. The MI of the polyolefin microporous membrane can be adjusted within the above numerical range by, for example, controlling the molecular weight and compounding ratio of polymer raw materials such as polyolefins.
[0170] Regarding the molecular weight distribution of the polyolefin microporous membrane measured by GPC, from the viewpoint of reducing the fluidity of the film when it is melted and the short-circuit resistance during the nail penetration test, the polyethylene component with a Mw of 1,000,000 or more is 7% by mass or more of the total eluted component, more preferably 9% by mass or more, more preferably 12% by mass or more, and more preferably 15% by mass or more. In addition, from the viewpoint of suppressing excessive stress when the film shrinks in a high temperature environment, the polyethylene component with a Mw of 1,000,000 or more is preferably 57% by mass or less, more preferably 42% by mass or less, more preferably 33% by mass or less, and more preferably 27% by mass or less based on the total eluted component. The molecular weight distribution of the polyolefin microporous membrane can be adjusted to the above numerical range by, for example, controlling the type, molecular weight and blending ratio of the polyolefin raw material.
[0171] From the perspective of battery safety, the puncture strength of the microporous membrane not converted to a unit area weight (hereinafter referred to as the puncture strength) is preferably 250gf or more, and from the perspective of the porosity, crystallinity and resistance suppression of the polyolefin microporous membrane after compression, it is preferably 700gf or less. The puncture strength is more preferably 300gf to 690gf, and further preferably 310fg to 680gf. From the perspective of suppressing the breakage of the membrane caused by the detached active material when the separator is wound together with the electrode, and from the perspective of suppressing the suspense of short circuit caused by the expansion and contraction of the electrode associated with charging and discharging, the puncture strength is also preferably 200gf / 20μm or more. On the other hand, from the perspective of being able to reduce the width shrinkage caused by the orientation relaxation during heating, the puncture strength is preferably 2000gf / 20μm or less. The puncture strength is measured according to the method described in the embodiment. The puncture strength can be adjusted by adjusting the stretching ratio and / or stretching temperature of the substrate.
[0172] From the viewpoint of suppressing thermal runaway of the non-aqueous secondary battery, the weight per unit area of the polyolefin microporous membrane is preferably 3.0 g / m 2 From the viewpoint of increasing the capacity of the battery, 10 g / m 2 The weight per unit area of the polyolefin microporous membrane is more preferably 3.0 g / m 2 Above and 7.0g / m 2 Below, more preferably 3.0g / m 2 Above and 6.0g / m 2 By improving the compression resistance, the safety of the battery can be ensured even at a lower weight per unit area.
[0173] From the viewpoint of safety of a nonaqueous secondary battery including a microporous membrane, the withstand voltage per unit area weight of the microporous membrane is preferably 0.13 kV / (g / m 2 )above.
[0174] The tensile strength of the polyolefin microporous membrane is preferably 5000 kgf / cm2 in both MD and TD from the viewpoint of ensuring the membrane strength required for winding and stacking electrodes and separators in the manufacturing process of non-aqueous secondary batteries. 2 Below, more preferably 4500kgf / cm 2 Below, more preferably 4000kgf / cm 2 Below, more preferably 3500kgf / cm 2 Below, particularly preferably 3,000 kgf / cm 2 The lower limit is preferably 500 kgf / cm 2 More preferably, 700 kgf / cm 2More preferably, 1,000 kgf / cm 2 More preferably, 1500 kgf / cm 2 More than, particularly preferably 2000kgf / cm 2 More than, particularly preferably 2500kgf / cm 2 In addition, regarding the upper limit of the tensile strength at break of the polyolefin microporous membrane, from the viewpoint of suppressing the thermal shrinkage of the polyolefin microporous membrane, both MD and TD are preferably less than 5000 kgf / cm 2 .
[0175] The closer the values of the tensile strength at break of MD and TD of the polyolefin microporous membrane are, the more the short-circuit area is minimized due to the equal rupture of the membrane during the nail penetration test of the non-aqueous secondary battery, and then the safety of the nail penetration test becomes good. In addition, the closer the values of the tensile strength of MD and TD of the polyolefin microporous membrane are, the less likely the membrane will break in the direction of weak strength when mixed with foreign matter or when subjected to impact from the outside, the safety is improved, and the structure is isotropic, and the cycle characteristics of the battery are improved. From this point of view, the ratio of the tensile strength at break of MD of the polyolefin microporous membrane to the tensile strength at break of TD (MD / TD tensile strength at break ratio) is preferably 0.5 or more and 2.0 or less, more preferably 0.7 or more and 1.5 or less, further preferably 0.7 or more and 1.4 or less, further preferably 0.7 or more and 1.3 or less, particularly preferably 0.7 or more and 1.2 or less, particularly preferably 0.8 or more and 1.3 or less, particularly preferably 0.8 or more and 1.2 or less. The MD / TD tensile breaking strength ratio of the polyolefin microporous membrane can be adjusted within the numerical range described above by controlling the stretching ratio, HS ratio, and the like in the biaxial stretching step, for example.
[0176] Regarding the tensile elongation at break of the polyolefin microporous membrane, if both MD and TD are controlled within an appropriate numerical range, the membrane will be moderately elongated and ruptured during the nail puncture test of the non-aqueous secondary battery, thereby minimizing the short-circuit area, and thus the safety of the nail puncture test becomes good. In the case where the tensile elongation at break is too high, due to the excessive elongation of the nail puncture portion, the surrounding portion other than the nail punctured membrane portion is pulled, and the membrane thickness of the surrounding portion becomes thinner, resulting in a large area of short circuit. From this point of view, regarding the tensile elongation at break of the polyolefin microporous membrane, MD and TD are preferably 20% or more and 200% or less, more preferably 30% or more and 150% or less, further preferably 40% or more and 120% or less, and further preferably 50% or more and 110% or less. The tensile elongation at break of MD and / or TD of the polyolefin microporous membrane can be adjusted to the numerical range described above by, for example, controlling the stretching ratio, HS ratio, etc. during the biaxial stretching process.
[0177] The closer the values of the tensile elongation at break of the MD and TD of the polyolefin microporous membrane are, the more the membrane will be stretched and ruptured during the nail penetration test of the non-aqueous secondary battery, thereby minimizing the short-circuit area, and then the safety of the nail penetration test becomes good. From this point of view, the ratio of the MD tensile elongation at break to the TD tensile elongation at break of the polyolefin microporous membrane (MD / TD tensile elongation at break ratio) is preferably 0.3 or more and 2.0 or less, more preferably 0.35 or more and 1.5 or less, further preferably 0.4 or more and 1.3 or less, and further preferably 0.5 or more and 1.2 or less. The MD / TD tensile elongation at break ratio of the polyolefin microporous membrane can be adjusted to the numerical range described above by, for example, controlling the stretching ratio, HS ratio, etc. during the biaxial stretching process.
[0178] The tensile modulus of the polyolefin microporous membrane is preferably 1,000 kg / cm2 for both MD and TD, from the viewpoint of improving safety by preventing the separator from breaking when the nail penetrates the non-aqueous secondary battery and the separator and electrode are also penetrated and deformed during the nail penetration test, thereby preventing short circuit and improving safety. 2 ~10,000kg / cm 2 , more preferably 2,000 kg / cm 2 ~90,000kg / cm 2 .
[0179] The closer the values of the tensile modulus of MD and TD of the polyolefin microporous membrane are, the shorter the area is minimized due to the equal rupture of the membrane during the nail penetration test of the non-aqueous secondary battery, and the safety of the nail penetration test becomes good. From this point of view, the ratio of the tensile modulus of MD of the polyolefin microporous membrane to the tensile modulus of TD (MD / TD tensile modulus ratio) is preferably 0.3 or more and 3.0 or less, more preferably 0.35 or more and 2.0 or less, further preferably 0.4 or more and 1.5 or less, and further preferably 0.5 or more and 1.3 or less. The MD / TD tensile modulus ratio of the polyolefin microporous membrane can be adjusted to the numerical range described above by, for example, controlling the stretching ratio, HS ratio, etc. during the biaxial stretching process.
[0180] The cutoff (Fuse) temperature of the microporous membrane is preferably below 150°C, more preferably below 149°C. The upper limit of the cutoff temperature means that when a certain abnormal reaction occurs and the temperature in the battery rises, the pores of the separator are blocked until the temperature is reached. Therefore, the lower the cutoff temperature, the faster the flow of lithium ions between the electrodes is stopped at a lower temperature, and therefore, safety is improved. On the other hand, from the viewpoint that the battery performance will not be reduced even when exposed to a high temperature exceeding 100°C, the Fuse temperature of the microporous membrane is preferably above 130°C, more preferably above 135°C, further preferably above 138°C, and further preferably above 139°C.
[0181] The surface smoothness of the polyolefin microporous membrane is preferably 20,000 sec / 10 cm on one side and the other side from the viewpoint of cycle characteristics and rate characteristics under pressure. 3 Above and 200,000sec / 10cm 3 Less than, more preferably 30,000 sec / 10cm 3 Above and 180,000sec / 10cm 3 Below, more preferably 40,000 sec / 10cm 3 Above and 160,000sec / 10cm 3 Less than, particularly preferably 50,000 sec / 10cm 3 Above and 140,000sec / 10cm 3 Below. Surface smoothness is less than 20,000sec / 10cm 3 In the case of a surface smoothness of more than 200,000 sec / 10 cm, the physical distance between the polyolefin microporous membrane and the electrode material becomes non-uniform, so the battery reaction sometimes becomes non-uniform and the cycle characteristics deteriorate. 3 In the case of , the distance between the polyolefin microporous membrane and the electrode material becomes smaller, and the gap formed between the microporous membrane and the electrode material becomes smaller, so sometimes the uniform penetration of the electrolyte is hindered, and the cycle characteristics deteriorate. The surface smoothness of the polyolefin microporous membrane can be adjusted to the numerical range described above by, for example, controlling the molecular weight and blending ratio of polymer raw materials such as polyolefins, the distance between the rollers of the casting rolls, the stretching ratio during the biaxial stretching process, the MD / TD stretching temperature during the biaxial stretching process, the heating coefficient per unit resin of the resin composition during the biaxial stretching process, the HS ratio, the HS temperature, etc.
[0182] 〈Overlay〉
[0183] The separator for storage device of the present embodiment includes a covering layer, and the covering layer is arranged on at least one surface of the substrate. That is, the covering layer can be arranged only on one side of the substrate, or it can also be arranged on both sides. "Arranged on the surface" means: it can be arranged on the entire surface of the substrate, or it can also be arranged locally. It is intended that the covering layer is directly bonded to the electrode. It is preferably arranged in a manner that the substrate and the electrode are bonded via the covering layer so that the covering layer is directly bonded to the electrode. The covering layer is preferably a coating layer formed by a method of applying a coating liquid containing an inorganic filler and a granular polymer to the substrate.
[0184] The covering layer contains a particulate polymer of a thermoplastic polymer and an inorganic filler. The covering layer may contain a resin binder, a water-soluble polymer, other additives, and the like in addition to the particulate polymer of the thermoplastic polymer.
[0185] (Inorganic filler)
[0186] The inorganic filler is not particularly limited, but preferably has a melting point of 200°C or more, high electrical insulation, and is electrochemically stable within the use range of power storage devices such as lithium ion secondary batteries. As such inorganic fillers, inorganic oxides (oxide ceramics) such as aluminum oxide, silicon dioxide, titanium dioxide, zirconium oxide, magnesium oxide, cerium dioxide, yttrium oxide, zinc oxide, and iron oxide can be listed; inorganic nitrides (nitride ceramics) such as silicon nitride, titanium nitride, and boron nitride; ceramics such as silicon carbide, calcium carbonate, magnesium sulfate, aluminum sulfate, barium sulfate, aluminum hydroxide, aluminum hydroxide, potassium titanate, talc, kaolinite, dickite, pearl clay, halloysite, pyrophyllite, montmorillonite, sericite, mica, magnesia chlorite, bentonite, asbestos, zeolite, calcium silicate, magnesium silicate, diatomaceous earth, and silica sand; and glass fiber. They are used alone or in combination of two or more. Among these, the inorganic filler is preferably at least one selected from the group consisting of alumina, barium sulfate, and aluminum oxyhydroxide (boehmite).
[0187] The lower limit of the average particle size of the inorganic filler is preferably more than 50nm, more than 100nm, more than 150nm, more than 200nm, more than 250nm, more than 300nm, more than 350nm or more than 400nm, and the upper limit is preferably less than 2000nm, less than 1100nm, less than 800nm, less than 450nm, less than 400nm, less than 350nm or less than 300nm. From the viewpoint of maintaining the voids and rate characteristics for ion permeation through the covering layer, the average particle size of the inorganic filler is preferably more than 50nm. From the viewpoint of improving the filling rate of the inorganic filler in the covering layer and improving the heat shrinkage, the average particle size of the inorganic filler is preferably less than 2000nm. The average particle size of the inorganic filler is, for example, preferably more than 180nm and less than 300nm. The reason is that, especially when the thickness of the covering layer is small, a uniform covering layer thickness is formed, and heat shrinkage is improved. The average particle size of the inorganic filler is also preferably, for example, more than 250nm and less than 450nm. The reason is that it is possible to highly take into account both rate characteristics and heat shrinkage resistance. The "average particle size" of the inorganic filler is measured using the method described in the embodiment. As a method for adjusting the particle size and distribution of the inorganic filler, for example, a method for reducing the particle size by crushing the inorganic filler using a suitable pulverizing device such as a ball mill, a bead mill, a jet mill, etc. can be cited. Regarding the particle size distribution of the inorganic filler, in the frequency and particle size diagram, the peak can become one. However, it is also possible to present a trapezoidal spectrum in which the peak is two or no peak is formed. As the coefficient of variation of the particle size distribution of the inorganic filler, it is preferably less than 0.55, more preferably less than 0.50, and further preferably less than 0.45. From the viewpoint of suppressing deformation at a temperature exceeding the melting point of the substrate and improving the inclination of the covering layer and the adhesion to the electrode, the coefficient of variation of the particle size distribution is preferably less than 0.55.
[0188] As the shape of the inorganic filler, for example, plate-like, flaky, needle-like, columnar, spherical, polyhedral and block-like can be listed. Inorganic fillers with these shapes can be used in combination in a variety of ways. From the viewpoint of improving the inclination rate of the covering layer and the adhesion of the electrode, preferably block-like. Regardless of the aspect ratio, the filler shape is preferably block-like compared with the spherical shape. When the filler shape is similar to a spherical shape, the surface contact of the granular polymer to the substrate is hindered, so it is not preferred, accompanied by the surface tension and Newtonian fluidity of the coating.
[0189] The aspect ratio of the inorganic filler is preferably 1.0 or more and 2.5 or less, more preferably 1.1 or more and 2.0 or less. From the viewpoint of suppressing the moisture adsorption of the separator, suppressing the capacity degradation during repeated cycles, suppressing the deformation at a temperature exceeding the melting point of the substrate, and improving the inclination of the covering layer and the adhesion to the electrode, the aspect ratio is preferably 2.5 or less. It can be considered that the reason for increasing the inclination by making the aspect ratio of the inorganic filler 1.0 or more and 2.5 or less is that the particle orientation in the covering layer is small, so it is easy to form a stacked structure.
[0190] The particle size distribution of the inorganic filler obtained by dividing the standard deviation SD value of the volume average particle diameter of the inorganic filler by the D50 value is preferably 0.55 or less, more preferably 0.50 or less, and further preferably 0.45 or less. From the viewpoint of suppressing deformation at a temperature exceeding the melting point of the substrate, and improving the inclination rate of the covering layer, and the viewpoint of improving the bonding force of the electrode, it is preferred that the particle size distribution is 0.55 or less. It can be considered that the reason for increasing the inclination rate by making the particle size distribution of the inorganic filler 0.55 or less is that, because the uniformity of the particles becomes higher, the contact rate between the particles is improved, thereby easily forming a stacked structure.
[0191] The amount of the inorganic filler is, for example, 20 to 100 parts by mass, 30 to 80 parts by mass, 35 to 70 parts by mass, or 40 to 60 parts by mass, based on the total mass of the covering layer.
[0192] (Granular polymer)
[0193] The granular polymer is a particle of a thermoplastic polymer. From the viewpoint of improving the adhesion between the separator and the electrode, the granular polymer preferably contains a thermoplastic polymer having a glass transition temperature or a melting point of 20°C or more and 200°C or less. The glass transition temperature refers to the midpoint glass transition temperature described in JIS K7121, which is determined according to the DSC curve obtained by differential scanning calorimetry (DSC). Specifically, the temperature at the intersection of the following straight line and the curve can be used as the glass transition temperature, wherein the straight line is a straight line obtained by extending the low temperature side baseline in the DSC curve toward the high temperature side and the straight line obtained by extending the high temperature side baseline in the DSC curve toward the low temperature side in the longitudinal direction, and the curve is a curve of the step-like change part of the glass transition. In more detail, it can be determined according to the method described in the embodiment. In addition, "glass transition" refers to a heat flow change accompanying the state change of the polymer as a test piece on the endothermic side of the DSC. This heat flow change is observed in the form of a step-like change shape in the DSC curve. "Step-like change" refers to the portion of the DSC curve where the curve moves from the low-temperature side baseline to the new high-temperature side baseline that is farther away. It should be noted that the portion composed of step-like changes and peaks is also included in the step-like change. In addition, in the step-like change portion, when the upper side is set as the exothermic side, it can also be expressed as a point where the upward convex curve changes to a downward convex curve. "Peak" refers to the portion of the DSC curve where the curve deviates from the low-temperature side baseline until it returns to the same baseline. "Baseline" refers to the DSC curve in the temperature region where the test piece does not undergo phase change and reaction.
[0194] The glass transition temperature (Tg) of the granular polymer is preferably above 20°C and below 110°C, more preferably above 50°C, further preferably above 80°C, and further preferably above 90°C. From the viewpoint of improving the adhesive force after the electrolyte injection, it is particularly preferably greater than 90°C. From the viewpoint of suppressing the adhesion (adhesion) of adjacent separators separated by the covering layer during the storage and transportation of the separators for the storage device and the manufacturing process of the storage device, the Tg of the granular polymer is preferably above 20°C. On the other hand, from the viewpoint of obtaining good adhesion to the electrode, the Tg of the granular polymer is preferably below 110°C. The Tg of the granular polymer can be appropriately adjusted by, for example, changing the type of monomer used in the manufacture of the granular polymer and the blending ratio of each monomer when the granular polymer is a copolymer. That is, the glass transition temperature of each monomer used in the production of the granular polymer can be estimated based on the Tg of its homopolymer generally shown (for example, as described in "A WILEY-INTERSCIENCE PUBLICATION") and the blending ratio of the monomers. For example, the Tg of a copolymer obtained by copolymerizing monomers such as methyl methacrylate, acrylonitrile and methacrylic acid, which provide a homopolymer of about 100°C, at a high ratio becomes high, and the Tg of a copolymer obtained by copolymerizing monomers such as n-butyl acrylate and 2-ethylhexyl acrylate, which provide a homopolymer of about -50°C, at a high ratio becomes low. In addition, the Tg of the copolymer can also be estimated using the FOX formula shown in the following formula (1).
[0195] 1 / Tg=W1 / Tg1+W2 / Tg2+···+W i / Tg i +···W n / Tg n
[0196] Here, in the formula, Tg(K) is the Tg of the copolymer, Tg i (K) is the Tg of the homopolymer of monomer i, W i is the mass fraction of each monomer. i is an integer of 1 to n, and n is the number of types of monomers constituting the copolymer. However, as the glass transition temperature Tg of the particulate polymer in the present embodiment, the value measured by the method using the above-mentioned DSC is adopted.
[0197] From the viewpoint of adhesion between the separator and the electrode and preventing the granular polymer from falling off the covering layer, the average particle size of the granular polymer is preferably 0.5 times or more and 5 times or less, more preferably 1 times or more and 2 times or less, further preferably 1.1 times or more and less than 1.5 times, and particularly preferably 1.2 times or more and 1.4 times or less relative to the thickness of the covering layer. The "average particle size" of the granular polymer refers to the volume average particle size measured by the measurement method described in the examples. The "primary particles" of the granular polymer refer to independent particles that are formed as a whole by means of covalent bonds. On the other hand, the form in which two or more primary particles come into contact to form an aggregate is called a "secondary particle".
[0198] The particle size distribution MV / MN of the granular polymer obtained by dividing the volume average particle size MV of the granular polymer by the number average particle size MN is preferably 1.60 or less, more preferably 1.30 or less, further preferably 1.20 or less, further preferably 1.10 or less, and particularly preferably less than 1.10. From the viewpoints of ensuring the thickness uniformity of the covering layer, improving the cycle characteristics, improving the adhesion to the electrode, reducing the amount of the granular polymer on the small particle size side buried in the covering layer, improving the adhesion to the electrode, improving the heat resistance, and reducing the total thickness of the separator, the particle size distribution of the granular polymer is preferably within the above range. The lower limit of the particle size distribution MV / MN of the granular polymer is not particularly limited, and for example, it can be 1.01 or more or 1.01.
[0199] The granular polymer contained in the covering layer is preferably in the form of primary particles. The average particle size of the primary particles of the granular polymer is preferably 1 μm or more and 10 μm or less, more preferably 1 μm or more and 5 μm or less, and further preferably 2 μm or more and 4 μm or less. The granular polymer is in the form of primary particles means that the granular polymer is uniformly dispersed in the covering layer, thereby improving the 180° peel strength, improving the adhesion to the electrode, suppressing thermal shrinkage, and ensuring the thickness uniformity of the covering layer. If the average particle size of the primary particles is 1 μm or more and 10 μm or less, it is easy to form a structure in which the granular polymer protrudes from the surface of the covering layer, improving the adhesion to the electrode, and suppressing thermal shrinkage.
[0200] Examples of the thermoplastic polymer include (meth)acrylic polymers, conjugated diene polymers, polyvinyl alcohol resins, and fluorine-containing resins.
[0201] From the viewpoint of high adhesion to the electrode and low thermal shrinkage, the thermoplastic polymer more preferably includes a (meth)acrylic polymer. "(Meth)acrylic polymer" refers to a polymer or copolymer containing a (meth)acrylic compound as a monomer. Such a (meth)acrylic compound can be represented by the following general formula.
[0202] CH2=CR Y1 -COO-R Y2
[0203] In the formula, R Y1 Represents a hydrogen atom or a methyl group; R Y2 represents a hydrogen atom or a monovalent hydrocarbon group. Y2 In the case of a monovalent hydrocarbon group, it may have a substituent or a heteroatom. As a monovalent hydrocarbon group, for example, it may be a straight chain or a branched chain, and examples include chain alkyl groups, cycloalkyl groups, and aryl groups. As substituents, for example, hydroxyl groups and phenyl groups may be listed, and as heteroatoms, for example, halogen atoms and oxygen atoms may be listed. The (meth)acrylic acid compound may be used alone or in combination of two or more. As the (meth)acrylic acid compound, examples include (meth)acrylic acid, chain alkyl (meth)acrylates, cycloalkyl (meth)acrylates, (meth)acrylates having a hydroxyl group, and aryl (meth)acrylates.
[0204] More specifically, examples of the chain alkyl (meth)acrylate include chain alkyl groups having 1 to 3 carbon atoms, such as methyl, ethyl, n-propyl, and isopropyl; n-butyl, isobutyl, tert-butyl, n-hexyl, 2-ethylhexyl; and chain alkyl groups having 4 or more carbon atoms, such as lauryl. Examples of the aryl (meth)acrylate include phenyl (meth)acrylate.
[0205] Specific examples of the (meth)acrylate include (meth)acrylates having a chain alkyl group such as methyl acrylate, ethyl acrylate, propyl acrylate, isopropyl acrylate, butyl acrylate, isobutyl acrylate, tert-butyl acrylate, n-hexyl acrylate, 2-ethylhexyl acrylate, lauryl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, n-hexyl methacrylate, 2-ethylhexyl methacrylate, and lauryl methacrylate; and (meth)acrylates having an aromatic ring such as phenyl (meth)acrylate and benzyl (meth)acrylate.
[0206] Conjugated diene polymers are polymers having conjugated diene compounds as monomer units, which are easily compatible with electrodes, so they are preferred. As conjugated diene compounds, for example, 1,3-butadiene, 2-methyl-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-chloro-1,3-butadiene, substituted straight-chain conjugated pentadienes, substituted and side-chain conjugated hexadienes can be listed, and they can be used alone or in combination of two or more. Among these, 1,3-butadiene is particularly preferred. Conjugated diene polymers can contain (meth) acrylic acid compounds or other monomers described later as monomer units. As such monomers, for example, styrene-butadiene copolymers and their hydrides, acrylonitrile-butadiene copolymers and their hydrides, acrylonitrile-butadiene-styrene copolymers and their hydrides can be listed.
[0207] Examples of the polyvinyl alcohol-based resin include polyvinyl alcohol and polyvinyl acetate.
[0208] From the viewpoint of voltage resistance, fluorine-containing resins are preferred, and examples thereof include polyvinylidene fluoride, polytetrafluoroethylene, and copolymers containing fluorine atoms, such as vinylidene fluoride-hexafluoropropylene copolymers, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymers, and ethylene-tetrafluoroethylene copolymers. The fluorine-containing resin is preferably a copolymer containing fluorine atoms.
[0209] Among the thermoplastic polymers listed above, the granular polymer preferably contains at least one selected from the group consisting of a copolymer containing (meth)acrylate as a monomer, a styrene-butadiene copolymer, and a copolymer containing fluorine atoms. Regarding the copolymer containing (meth)acrylate as a monomer, it is more preferred to contain a copolymer containing (meth)acrylic acid, butyl (meth)acrylate, and ethylhexyl (meth)acrylate as monomers. By making the granular polymer contain these specific thermoplastic polymers, it is possible to provide a separator for a storage device with higher adhesion to the electrode and smaller thermal shrinkage.
[0210] The particulate polymer preferably includes a crosslinking monomer. As the crosslinking monomer, there is no particular limitation, and examples thereof include monomers having two or more free radical polymerizable double bonds, monomers having a functional group that provides a self-crosslinking structure during or after polymerization, etc. These can be used alone or in combination of two or more.
[0211] As monomers having more than two free radical polymerizable double bonds, for example, divinylbenzene and multifunctional (meth) acrylates can be listed, preferably multifunctional (meth) acrylates. Multifunctional (meth) acrylates can be at least one selected from the group consisting of difunctional (meth) acrylates, trifunctional (meth) acrylates and tetrafunctional (meth) acrylates. Specifically, for example, polyoxyethylene diacrylate, polyoxyethylene dimethacrylate, polyoxypropylene diacrylate, polyoxypropylene dimethacrylate, neopentyl glycol diacrylate, neopentyl glycol dimethacrylate, butanediol diacrylate, butanediol dimethacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol tetraacrylate and pentaerythritol tetramethacrylate can be listed. They can be used alone or in combination of more than two. Among them, from the same viewpoint as above, it is preferably at least one of trimethylolpropane triacrylate or trimethylolpropane trimethacrylate.
[0212] (resin binder)
[0213] The covering layer preferably includes a resin binder for bonding the inorganic fillers to each other and to the substrate. The type of resin used as the resin binder is not particularly limited, and a resin that does not dissolve in the electrolyte of a storage device such as a lithium ion secondary battery and is electrochemically stable within the use range of the storage device such as a lithium ion secondary battery can be used.
[0214] Specific examples of the resin as the resin binder include polyolefins such as polyethylene and polypropylene; fluorine-containing resins such as polyvinylidene fluoride and polytetrafluoroethylene; fluorine-containing rubbers such as vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymer and ethylene-tetrafluoroethylene copolymer; rubbers such as styrene-butadiene copolymer and its hydrogenated product, acrylonitrile-butadiene copolymer and its hydrogenated product, acrylonitrile-butadiene-styrene copolymer and its hydrogenated product, methacrylate-acrylate copolymer, styrene-acrylate copolymer, acrylonitrile-acrylate copolymer, ethylene-propylene rubber, polyvinyl alcohol, polyvinyl acetate, etc.; cellulose derivatives such as ethyl cellulose, methyl cellulose, hydroxyethyl cellulose, carboxymethyl cellulose, etc.; and resins having a melting point of 180° C. or above such as polyphenylene ether, polysulfone, polyether sulfone, polyphenylene sulfide, polyetherimide, polyamideimide, polyamide and polyester; or resins having no melting point but a decomposition temperature of 200° C. or above. These may be used alone or in combination of two or more.
[0215] The resin binder may include, for example, a resin latex binder. As the resin latex binder, for example, a copolymer of an unsaturated carboxylic acid monomer and other monomers copolymerizable therewith may be used. Here, as aliphatic conjugated diene monomers, for example, butadiene and isoprene may be cited, as unsaturated carboxylic acid monomers, for example, (meth)acrylic acid may be cited, and as other monomers, for example, styrene may be cited. The polymerization method of such a copolymer is not particularly limited, and emulsion polymerization is preferred. As the method for emulsion polymerization, there is no particular limitation, and known methods may be used. There is no particular limitation on the method for adding the monomers and other components, and a simultaneous addition method, a split addition method, and a continuous addition method may all be adopted. As for the polymerization method, one-stage polymerization, two-stage polymerization, or multi-stage polymerization of three or more stages may all be adopted.
[0216] Specific examples of the resin binder include the following (1) to (7).
[0217] (1) Polyolefins, such as polyethylene, polypropylene, ethylene-propylene rubber and their modifications;
[0218] (2) Conjugated diene polymers, such as styrene-butadiene copolymers and their hydrogenates, acrylonitrile-butadiene copolymers and their hydrogenates, acrylonitrile-butadiene-styrene copolymers and their hydrogenates;
[0219] (3) acrylic polymers, such as methacrylate-acrylate copolymers, styrene-acrylate copolymers, and acrylonitrile-acrylate copolymers;
[0220] (4) Polyvinyl alcohol-based resins, such as polyvinyl alcohol and polyvinyl acetate;
[0221] (5) Fluorine-containing resins such as polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymers and ethylene-tetrafluoroethylene copolymers;
[0222] (6) Cellulose derivatives such as ethyl cellulose, methyl cellulose, hydroxyethyl cellulose and carboxymethyl cellulose; and
[0223] (7) Resins having a melting point and / or glass transition temperature of 180°C or higher, or polymers having no melting point and a decomposition temperature of 200°C or higher, such as polyphenylene ether, polysulfone, polyethersulfone, polyphenylene sulfide, polyetherimide, polyamideimide, polyamide, and polyester.
[0224] When the resin binder is a resin latex binder, its volume average particle size (D50) can be, for example, 50 nm to 500 nm, 60 nm to 460 nm, or 80 nm to 250 nm. The volume average particle size of the resin binder can be controlled by, for example, adjusting the polymerization time, polymerization temperature, raw material composition ratio, raw material input sequence, and pH.
[0225] From the viewpoint of improving 180° peel strength, the glass transition temperature of the resin binder is preferably 25° C. or lower, more preferably 10° C. or lower, and further preferably -15° C. or lower. From the viewpoint of permeability, the glass transition temperature of the resin binder is preferably -60° C. or higher.
[0226] From the viewpoint of improving the 180° peel strength, the volume average particle size (D50) of the resin binder is preferably more than 1 times, more preferably more than 2 times, and further preferably more than 2.5 times the average pore size of the polyolefin microporous membrane. By selecting the volume average particle size (D50) of the resin binder in this way, the resin binder can be kept on the surface of the polyolefin microporous membrane, and the 180° peel strength is improved. From the viewpoint of improving the rate characteristics, the volume average particle size (D50) of the resin binder is preferably less than 10 times the average pore size of the polyolefin microporous membrane. The content ratio of the resin binder in the covering layer relative to the total amount of the covering layer can, for example, exceed 0 mass parts and be less than 80 mass parts, more than 1 mass part and less than 20 mass parts, more than 2 mass parts and less than 10 mass parts, or more than 3 mass parts and less than 5 mass parts.
[0227] From the viewpoints of wettability to the substrate, adhesion between the substrate and the granular polymer, adhesion between the covering layer and the granular polymer, adhesion between the substrate and the covering layer, and adhesion to the electrode, the Tg of the resin binder is preferably less than 40°C. From the viewpoint of ion permeability, the Tg of the resin binder is more preferably -100°C or higher, further preferably -50°C or higher, and particularly preferably -40°C or higher. From the viewpoint of adhesion between the substrate and the granular polymer, the Tg of the resin binder is more preferably less than 20°C, further preferably less than 15°C, and particularly preferably less than 0°C.
[0228] (Water-soluble polymer)
[0229] In the covering layer, in addition to the inorganic filler and the particulate polymer, a water-soluble polymer may be further included. The water-soluble polymer may be incompatible with the thermoplastic polymer of the particulate polymer. Generally speaking, the water-soluble polymer functions as a dispersant in the coating liquid for forming the covering layer of the particulate polymer containing the inorganic filler and the thermoplastic polymer, and functions as a dispersant and / or a water-retaining agent when the coating liquid is a water-based coating.
[0230] The content of the water-soluble polymer in the covering layer is preferably 0.04 mass parts or more and less than 2 mass parts relative to 100 mass parts of inorganic filler, more preferably 0.04 mass parts or more and 1.5 mass parts or less, and further preferably 0.1 mass parts or more and 1 mass parts or less. By making the content of the water-soluble polymer more than 0.04 mass parts, the adhesion of the inorganic components to each other is improved, and thermal shrinkage can be further suppressed. In addition, the component sedimentation when making the slurry of the covering layer can be suppressed, and it can be stably dispersed. By making the content of the water-soluble polymer less than 5 mass parts, the stripes and unevenness when forming the covering layer can be suppressed.
[0231] The water-soluble polymer also contributes to the bonding between the inorganic fillers in the coating layer. From the viewpoint of suppressing thermal shrinkage of the separator, the water-soluble polymer preferably has a weight loss rate of less than 10% at 150°C when the weight at 50°C in thermogravimetric measurement is 100%.
[0232] The water-soluble polymer may be a polymer derived from natural materials, a synthetic product, a semi-synthetic product, etc. From the viewpoint of coating of inorganic and organic components, especially water-based coating, anionic, cationic, amphoteric or nonionic polymers are preferred, and anionic, cationic or amphoteric polymers are more preferred.
[0233] Examples of anionic polymers include modified starches such as carboxymethyl starch and starch phosphate; anionic cellulose derivatives such as carboxymethyl cellulose; ammonium salts or alkali metal salts of polyacrylic acid; gum arabic; carrageenan; sodium chondroitin sulfate; sulfonic acid compounds such as sodium polystyrene sulfonate, sodium polyisobutylene sulfonate, and naphthalenesulfonic acid condensate salts; and polyethyleneimine xanthate. Among these, in terms of the battery device, from the viewpoint of showing an appropriate balance between rigidity, rate characteristics, and cycle characteristics, anionic polymers preferably contain metal salts as counter cations, and anionic cellulose derivatives and ammonium salts or alkali metal salts of polyacrylic acid are also preferred. From the viewpoint of the balance between heat resistance and rate characteristics, alkali metal salts of polyacrylic acid are further preferred, and sodium polyacrylate is further preferred.
[0234] The ammonium salt or alkali metal salt of polyacrylic acid refers to: -COO derived from multiple carboxylic acid groups - A polymer in which at least one of the moieties forms a salt with an ammonium ion or an alkali metal ion. Examples of the alkali metal ion include sodium ions (Na + ), potassium ion (K + )wait.
[0235] The ammonium salt or alkali metal salt of polyacrylic acid may be at least one of the following (I) to (III):
[0236] (I) A monomer having an ammonium salt or an alkali metal salt of a carboxylic acid (C i ) homopolymer or multiple monomers (C i ) and other monomers;
[0237] (II) A monomer having an ammonium salt or an alkali metal salt of a plurality of carboxylic acids (C ii ) homopolymer or monomer (C ii ) and other monomers; and
[0238] (III) Ammonium salts or alkali metal salts of polymers or copolymers obtained by polymerizing or copolymerizing monomers having a single or multiple carboxylic acids.
[0239] As a monomer having an ammonium salt or an alkali metal salt of a carboxylic acid (C i ), for example, sodium (meth)acrylate and ammonium (meth)acrylate can be mentioned.
[0240] As a monomer having an ammonium salt or an alkali metal salt of multiple carboxylic acids (C ii ), for example, ammonium salts or sodium salts of 11-(methacryloyloxy)undecane-1,1-dicarboxylic acid; ammonium salts, monosodium salts or disodium salts of ethylenically unsaturated dicarboxylic acids such as fumaric acid, maleic acid, itaconic acid and citraconic acid; and alicyclic polycarboxylic acids having a (meth)acryloyl group.
[0241] As a monomer (C i ) or monomer (C ii ) can be copolymerized with (meth)acrylamide; ethylenically unsaturated dicarboxylic acids such as fumaric acid, maleic acid, itaconic acid and citraconic acid; and ethylenically unsaturated dicarboxylic anhydrides such as maleic anhydride, itaconic anhydride and citraconic anhydride.
[0242] Examples of the ammonium salt or alkali metal salt of a polymer or copolymer obtained by polymerizing or copolymerizing a monomer having a single or multiple carboxylic acids include sodium polyacrylate and ammonium polyacrylate.
[0243] The structures of the ammonium salt or alkali metal salt of polyacrylic acid described in (I) to (III) above may be repeated. It is desirable that when the ammonium salt or alkali metal salt of polyacrylic acid described in (I) to (III) above is dissolved in water, the content of polyvalent cations is small. Examples of polyvalent cations include magnesium ions, calcium ions, and iron ions. By reducing the content of these ions, the dispersibility of the granular polymer in the mixed slurry with the granular polymer is stabilized.
[0244] Examples of cationic polymers include cationic starch, chitosan, gelatin, homopolymers or copolymers of dimethylaminoethyl (meth)acrylate quaternary salt, homopolymers or copolymers of dimethylallylammonium chloride, polyamidine and copolymers thereof, polyvinyl imidazoline, dicyandiamide condensates, epichlorohydrin-dimethylamine condensates, and polyethyleneimine.
[0245] Examples of the amphoteric polymer include a (meth)acrylate dimethylaminoethyl quaternary salt-acrylic acid copolymer and a Hofmann degradation product of polyacrylamide.
[0246] Examples of nonionic polymers include starch and its derivatives; cellulose derivatives such as methyl cellulose, hydroxyethyl cellulose, and hydroxypropyl cellulose, and their ammonium salts or alkali metal salts; rubbers such as guar gum and their modifications; and synthetic polymers such as polyvinyl alcohol, polyacrylamide, polyethylene glycol, polymethyl vinyl ether, polyisopropylacrylamide, and copolymers of vinyl alcohol and other monomers, and their modifications.
[0247] The water-soluble polymer may or may not have a cyclic structure containing an amide bond. The water-soluble polymer having a cyclic structure containing an amide bond refers to a homopolymer or copolymer comprising a group having a cyclic structure containing an amide bond and a skeleton derived from a polymerizable double bond. The water-soluble polymer having a cyclic structure containing an amide bond may have a single or multiple cyclic structures containing an amide bond.
[0248] Examples of the group having a cyclic structure containing an amide bond include a group represented by the following formula (2).
[0249]
[0250] Specific examples of water-soluble polymers having a cyclic structure containing an amide bond include homopolymers of N-vinylcaprolactam, i.e., poly(N-vinylcaprolactam), homopolymers of vinylpyrrolidone, i.e., polyvinylpyrrolidone (PVP), and the like, which contain a group having a cyclic structure containing an amide bond and a polymerizable double bond; copolymers containing two or more monomers having a group having a cyclic structure containing an amide bond and a polymerizable double bond (N-vinylcaprolactam, vinylpyrrolidone, etc.); and copolymers formed by one or more monomers having a group having a cyclic structure containing an amide bond and a polymerizable double bond (N-vinylcaprolactam, vinylpyrrolidone, etc.) and one or more other monomers having a polymerizable double bond (monomers other than monomers containing a group having a cyclic structure containing an amide bond and a polymerizable double bond).
[0251] Examples of monomers that can be copolymerized with a monomer containing a group having a cyclic structure containing an amide bond and a polymerizable double bond include vinyl non-cyclic amides; (meth)acrylic acid and its esters; (meth)acrylamide and its derivatives; styrene and its derivatives; vinyl esters such as vinyl acetate; α-olefins; basic unsaturated compounds such as vinylimidazole and vinylpyridine and their derivatives; unsaturated compounds containing a carboxyl group and their anhydrides; vinyl sulfonic acid and its derivatives; vinyl ethylene carbonate and its derivatives; and vinyl ethers.
[0252] (additive)
[0253] The covering layer may be formed only of an inorganic filler, a particulate polymer, and an optional water-soluble polymer, or may further contain additives other than these. Examples of the additives include, for example, a low molecular weight dispersant other than the water-soluble polymer; a thickener; a defoamer; and a pH adjuster such as ammonium hydroxide. Specific examples of the low molecular weight dispersant include monomers (C ii ) and non-polymeric compounds having ammonium salts or alkali metal salts of multiple carboxylic acids (such as sodium alginate and sodium hyaluronate), etc.
[0254] As a specific example of the defoaming agent, a surfactant (acetylene-based surfactant) containing an ethoxylated product of acetylene glycol represented by the following formula (A) is preferably used.
[0255]
[0256] {In the formula, R 5 ~R 8 Each independently represents an alkyl group having 1 to 10 carbon atoms, and n and m independently represent an integer greater than 0, wherein n+m=0 to 40.
[0257] Specific examples of the alkyl group having 1 to 10 carbon atoms may be any of linear, branched, and cyclic groups, and include, for example, methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, and n-decyl.
[0258] Specific examples of the acetylene diol represented by formula (A) include 2,5,8,11-tetramethyl-6-dodecene-5,8-diol, 5,8-dimethyl-6-dodecene-5,8-diol, 2,4,7,9-tetramethyl-5-decene-4,7-diol, 4,7-dimethyl-5-decene-4,7-diol, 2,3,6,7-tetramethyl-4-octyne-3,6-diol, 3,6-dimethyl-4-octyne-3,6-diol, 2,5-dimethyl-3-hexyne-2,5-diol, ethoxylated products of 2,4,7,9-tetramethyl-5-decyne-4,7-diol (number of ethylene oxide added: 1.3), and 2,3,6,7-tetramethyl-4-octyne-3,6-diol. 4,7-diol ethoxylated product (ethylene oxide addition mole number: 4), 3,6-dimethyl-4-octyne-3,6-diol ethoxylated product (ethylene oxide addition mole number: 4), 2,5,8,11-tetramethyl-6-dodecyne-5,8-diol ethoxylated product (ethylene oxide addition mole number: 6), 2,4,7,9-tetramethyl-5-decyne-4,7-diol ethoxylated product (ethylene oxide addition mole number: 10), 2,4,7,9-tetramethyl-5-decyne-4,7-diol ethoxylated product (ethylene oxide addition mole number: 30) and 3,6-dimethyl-4-octyne-3,6-diol ethoxylated product (ethylene oxide addition mole number: 20). The defoaming agent may be used alone or in combination of two or more.
[0259] The acetylene-based surfactant can also be obtained as a commercial product. Examples of such commercial products include OLFINE SPC (manufactured by Nissin Chemical Industry Co., Ltd., 80 parts by mass of active ingredient, light yellow liquid), OLFINE AF-103 (manufactured by Nissin Chemical Industry Co., Ltd., light brown liquid), OLFINE AF-104 (manufactured by Nissin Chemical Industry Co., Ltd., light brown liquid), OLFINE SK-14 (manufactured by Nissin Chemical Industry Co., Ltd., light yellow viscous liquid), OLFINE AK-02 (manufactured by Nissin Chemical Industry Co., Ltd., light yellow viscous liquid), OLFINE AF-201F (manufactured by Nissin Chemical Industry Co., Ltd., light yellow viscous liquid), OLFINE D-10PG (manufactured by Nissin Chemical Industry Co., Ltd., 50 parts by mass of active ingredient, light yellow liquid), OLFINE E-1004 (manufactured by Nissin Chemical Industry Co., Ltd., 100 parts by mass of active ingredient, light yellow liquid), OLFINE OLFINE E-1010 (manufactured by Nissin Chemical Industry Co., Ltd., active ingredient: 100 parts by mass, light yellow liquid), OLFINE E-1020 (manufactured by Nissin Chemical Industry Co., Ltd., active ingredient: 100 parts by mass, light yellow liquid), OLFINE E-1030W (manufactured by Nissin Chemical Industry Co., Ltd., active ingredient: 75 parts by mass, light yellow liquid), SURFYNOL 420 (manufactured by Nissin Chemical Industry Co., Ltd., active ingredient: 100 parts by mass, light yellow viscous body), SURFYNOL 440 (manufactured by Nissin Chemical Industry Co., Ltd., active ingredient: 100 parts by mass, light yellow viscous body) and SURFYNOL 104E (manufactured by Nissin Chemical Industry Co., Ltd., active ingredient: 50 parts by mass, light yellow viscous body), etc.
[0260] As surfactants belonging to additives, polyether surfactants and / or silicone surfactants can also be used in place of acetylene surfactants or together with acetylene surfactants. Representative examples of polyether surfactants include polyethylene glycol, polypropylene glycol, polytetramethylene glycol, polyoxyethylene oleyl ether, polyoxyethylene stearyl ether, polyoxyethylene lauryl ether, polyoxyethylene dodecyl ether, polyoxyethylene nonylphenyl ether, polyoxyethylene octylphenyl ether and polyoxyethylene-polyoxypropylene block copolymers. Among these, polyethylene glycol is particularly preferred. It should be noted that these surfactants can be used alone or in combination of two or more.
[0261] The polyether-based surfactant is also available as a commercial item. Examples of such commercial items include E-D052, E-D054, and E-F010 (manufactured by Sannopco).
[0262] As a silicone-based surfactant, as long as it contains at least a silicone chain, it can be any of linear, branched, and cyclic, and can contain any of a hydrophobic group and a hydrophilic group. Specific examples of hydrophobic groups include alkyl groups such as methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, and n-decyl; cyclic alkyl groups such as cyclohexyl; and aromatic hydrocarbon groups such as phenyl. Specific examples of hydrophilic groups include amino groups, thiol groups, hydroxyl groups, alkoxy groups, carboxylic acids, sulfonic acids, phosphoric acids, nitric acids, and their organic salts, inorganic salts, ester groups, aldehyde groups, glyceryl groups, and heterocyclic groups. Representative examples of silicone-based surfactants include dimethyl silicone, methylphenyl silicone, chlorophenyl silicone, alkyl-modified silicone, fluorine-modified silicone, amino-modified silicone, alcohol-modified silicone, phenol-modified silicone, carboxyl-modified silicone, epoxy-modified silicone, fatty acid ester-modified silicone, and polyether-modified silicone.
[0263] The silicone surfactant can also be obtained as a commercial product. Examples of such commercial products include BYK-300, BYK-301, BYK-302, BYK-306, BYK-307, BYK-310, BYK-313, BYK-320, BYK-333, BYK-341, BYK-345, BYK-346, BYK-347, BYK-348, and BYK-349 (the above trade names, manufactured by BYK-Chemie-Japan); KM-80, KF- -351A, KF-352A, KF-353, KF-354L, KF-355A, KF-615A, KF-945, KF-640, KF-642, KF-643, KF-6020, X-22-4515, KF-6011, KF-6012, KF-6015, KF-6017 (the above trade names, manufactured by Shin-Etsu Chemical Co., Ltd.); SH-28PA, SH8400, SH-190, SF-8428 (the above trade names, manufactured by Dow Corning Toray Co., Ltd.); Polyflow KL-245, Polyflow KL-270, Polyflow KL-100 (the above trade names, manufactured by Kyoeisha Chemical Co., Ltd.); SILFACE SAG002, SILFACE SAG005 and SILFACE SAG0085 (the above trade names, manufactured by Nissin Chemical Industry Co., Ltd.), etc.
[0264] (Amount of covering layer)
[0265] The amount of the covering layer relative to the substrate, that is, the amount of the covering layer per unit area of one surface of the substrate, is preferably 0.5 g / m by weight. 2More preferably 1.0 g / m 2 Above, preferably 0.15 cm by volume 3 / m 2 More preferably 0.30 cm 3 / m 2 The upper limit of the amount of the covering layer is preferably 10.0 g / m 2 Below, more preferably 7.0g / m 2 Below, preferably 3.50 cm in volume 3 / m 2 Below, more preferably 2.50cm 3 / m 2 From the viewpoint of improving the adhesion between the covering layer and the electrode and suppressing thermal shrinkage, the amount of the covering layer is preferably greater than the above lower limit. From the viewpoint of suppressing a decrease in ion permeability, the amount of the covering layer is preferably less than the above upper limit.
[0266] (Thickness of the covering layer)
[0267] The thickness of any one of the covering layers disposed on at least one side of the substrate (the thickness of the inorganic filler portion of the covering layer) is preferably 0.3 μm or more and 5.0 μm or less, more preferably 0.5 μm or more and 2.5 μm or less, and further preferably 0.7 μm or more and 1.3 μm or less. If the thickness of the covering layer is 0.3 μm or more, the thermal shrinkage rate can be further suppressed, and the adhesion between the electrode and the substrate can be easily made uniform, and as a result, the characteristics of the storage device can be improved. If the thickness of the covering layer is 1.3 μm or less, the reduction in ion permeability can be suppressed, and a separator for storage devices of thin films can be obtained, which is preferred from this point of view. That is, a storage device with a large capacity per unit volume can be manufactured by thinning the thickness of the separator. On the other hand, from the viewpoint of preventing the granular polymer from slipping off the covering layer, it is preferably 1.6 μm or more or 2.1 μm or more. The thickness of the covering layer can be adjusted by, for example, changing the type or concentration of the granular polymer in the coating liquid applied to the substrate, the coating amount of the coating liquid, the coating method and the coating conditions. However, the method of adjusting the thickness of the cover layer is not limited to these.
[0268] Figure 1 Schematic diagram of the surface of the cover layer of the separator for the electrical storage device of the present embodiment. Figure 1 As schematically shown in FIG. 1 , an inorganic filler (1) and a granular polymer (2) of a thermoplastic polymer protruding from the covering layer are present on the surface of the covering layer (10). Figure 1 In the process, the particulate polymer does not aggregate with other particulate polymers but exists in the state of primary particles.
[0269] Figure 2 yes Figure 1 AA cross-sectional view of a separator for a power storage device. Figure 2 As schematically shown in FIG. 1 , the covering layer (20) is formed in an inclined shape in such a manner that the thickness increases continuously as the inorganic filler portion, which is 1.5D or more away from the volume center of each granular polymer in the horizontal direction (the surface direction of the covering layer), approaches the protruding granular polymer (2). The slope of the inclined covering layer is gentler as it is away from the protruding granular polymer, and steeper as it is closer to the protruding granular polymer. The inorganic filler (1) exists along the contour of the granular polymer and covers a portion of the periphery of the protruding portion, and the vicinity of the center of the protruding portion is exposed to the surface of the covering layer.
[0270] 《Method for manufacturing separator for electric storage device》
[0271] <Method for producing substrate>
[0272] (Method for producing polyolefin microporous membrane)
[0273] The method for manufacturing the substrate is not particularly limited, and a known manufacturing method can be used, such as a wet porosification method or a dry porosification method. If examples based on the wet porosification method are listed, for example, in the case where the substrate is a polyolefin microporous membrane, the following examples can be listed: a polyolefin resin composition and a plasticizer are melt-kneaded to form a sheet, stretched according to the situation, and then the plasticizer is extracted to make it porous; a polyolefin resin composition containing a polyolefin resin as a main component is melt-kneaded, extruded at a high stretch ratio, and then the polyolefin crystal interface is peeled off by heat treatment and stretching, thereby making it porous; a polyolefin resin composition and an inorganic filler are melt-kneaded to form a sheet, and then the interface between the polyolefin and the inorganic filler is peeled off by stretching, thereby making it porous; and a method of dissolving the polyolefin resin composition, immersing it in a poor solvent for polyolefin to solidify the polyolefin, and removing the solvent at the same time, thereby making it porous.
[0274] The method for producing the polyolefin microporous membrane described in the present application is not particularly limited, and as an example, a method including the following steps can be cited:
[0275] (A) a step of extruding a polyolefin composition comprising a polyolefin resin and a pore-forming material to form a gel-like sheet;
[0276] (B) a step of biaxially stretching the gel-like sheet to form a stretched sheet;
[0277] (C) a step of extracting a pore-forming material from the stretched sheet to form a porous membrane; and
[0278] (D) A step of thermally fixing the porous film.
[0279] The production process and preferred embodiments of the polyolefin microporous membrane are described below.
[0280] Extrusion process (A):
[0281] In step (A), the polyolefin composition is extruded to form a gel-like sheet. The polyolefin composition may include a polyolefin resin, a pore-forming agent, etc. When the resin contained in the polyolefin composition does not contain non-resin components such as microparticles or a high heat-resistant resin with a significantly different melting point but is composed only of polyolefin, it is preferred from the viewpoint of uniformizing the tensile stress and making the air permeability and air permeability distribution of the obtained film good. The gel-like sheet can be obtained by melt-kneading the polyolefin resin and the pore-forming material and molding them into a sheet.
[0282] First, the polyolefin resin and the pore-forming material are melt-kneaded. As a melt-kneading method, for example, the following method can be cited: the polyolefin resin and other additives as needed are put into a resin kneading device such as an extruder, a kneader, a laboplastic mill, a mixing roll, a Banbury mixer, etc., and the pore-forming material is introduced at an arbitrary ratio while the resin component is heated and melted, and kneaded.
[0283] The polyolefin resin contained in the polyolefin composition can be determined according to the predetermined resin raw material of the obtained polyolefin microporous membrane. Specifically, the polyolefin resin used in the extrusion step (A) may be the polyolefin resin described as a constituent element of the polyolefin microporous membrane.
[0284] The content of the plasticizer in the resin composition is preferably 66% to 90% by mass, more preferably 68% to 88% by mass, and further preferably 70% to 80% by mass. By adjusting the content of the plasticizer to 66% by mass or more, the melt viscosity of the resin composition is reduced, and melt cracking is suppressed, so there is a tendency for the film forming property to be improved during extrusion. On the other hand, by adjusting the content of the plasticizer to 90% by mass or less, the elongation of the original material in the film forming process can sometimes be suppressed.
[0285] From the viewpoint of uniformly applying tensile stress by uniformly dispersing the high molecular weight resin and making the ion permeability and air permeability distribution of the obtained membrane good, the proportion of the polymer component of the resin composition (hereinafter also referred to as "PC") is preferably 20% by mass to 40% by mass, more preferably 22% by mass to 37% by mass, and further preferably 24% by mass to 33% by mass, based on the total mass of the resin composition.
[0286] Regarding the high molecular weight raw material contained in the polyolefin composition, from the viewpoint of adjusting the molecular weight, MI, puncture strength, puncture strength converted to unit weight, the difference R between the maximum and minimum values of the air permeability at the TD3 point, the air permeability and porosity before compression, and the heat shrinkage of the obtained microporous membrane within the numerical range described above, the lower limit of Mv of at least one of the raw materials is preferably 700,000 or more, and the upper limit may be, for example, 2,000,000 or less. From the same viewpoint, among the resins contained in the polyolefin composition, the proportion of the high molecular weight raw material having an Mv of 700,000 or more is preferably 30% by mass or more, more preferably 40% by mass or more, further preferably 50% by mass or more, and may be 100% by mass.
[0287] In the case where the polyolefin composition contains polyethylene as the main component, from the viewpoint of adjusting the porosity after compression, the long crystal period or the crystallite size of the obtained microporous membrane to the numerical range described above, the lower limit of the Mv of the polyethylene is preferably 600,000 or more, more preferably 700,000 or more, and the upper limit may be, for example, 2,000,000 or less. From the same viewpoint, among the polyolefin resins constituting the polyolefin composition, the proportion of polyethylene having an Mv of 700,000 or more is preferably 50% by mass or more, more preferably 60% by mass or more, further preferably 70% by mass or more, and may be 100% by mass.
[0288] In the case where the polyolefin composition contains polyethylene as a main component, from the viewpoint of adjusting the molecular weight, MI, puncture strength, puncture strength converted to unit weight, the difference R between the maximum and minimum values of the air permeability at the TD3 point, the air permeability and porosity before compression, and the heat shrinkage of the obtained microporous membrane within the numerical range described above, the Mv of the polyethylene is preferably 700,000 or more for at least one of the raw materials, and the upper limit value may be, for example, 2,000,000 or less. From the same viewpoint, among the polyolefin resins constituting the polyolefin composition, the proportion of polyethylene having an Mv of 700,000 or more is preferably 30% by mass or more, more preferably 40% by mass or more, further preferably 50% by mass or more, and may be 100% by mass.
[0289] From the viewpoint of heat resistance of the obtained microporous film, polypropylene can be mixed into the polyolefin composition. In this case, from the viewpoint of strength and compression resistance of the film, the ratio of polypropylene in the polyolefin composition to the total mass of the polyolefin resin is preferably 1% by mass or more and 20% by mass or less, more preferably 2% by mass or more and 15% by mass or less, and further preferably 2% by mass or more and 10% by mass or less. In addition, from the viewpoint of improving moldability, the ratio of polypropylene in the polyolefin composition to the total mass of the polyolefin resin is preferably 3% by mass or more and 10% by mass or less, more preferably 5% by mass or more and 9% by mass or less.
[0290] As pore-forming materials, plasticizers, inorganic materials or combinations thereof can be cited. As plasticizers, there are no particular limitations, and it is preferred to use non-volatile solvents that can form a uniform solution above the melting point of polyolefin. Specific examples of non-volatile solvents include hydrocarbons such as liquid paraffin and paraffin wax; esters such as dioctyl phthalate and dibutyl phthalate; higher alcohols such as oleyl alcohol and stearyl alcohol, etc. It should be noted that these plasticizers can be recovered and reused by operations such as distillation after extraction.
[0291] Among plasticizers, when the polyolefin resin is polyethylene or polypropylene, liquid paraffin is preferred because it has high compatibility with these and tends to be less likely to cause interfacial separation between the resin and the plasticizer even when the melt-kneaded product is stretched, thereby facilitating uniform stretching.
[0292] As inorganic materials, there are no particular limitations, and examples thereof include oxide ceramics such as aluminum oxide, silicon dioxide (silicon oxide), titanium dioxide, zirconium oxide, magnesium oxide, cerium dioxide, yttrium oxide, zinc oxide, and iron oxide; nitride ceramics such as silicon nitride, titanium nitride, and boron nitride; ceramics such as silicon carbide, calcium carbonate, aluminum sulfate, aluminum hydroxide, potassium titanate, talc, kaolin, clay, kaolinite, halloysite, pyrophyllite, montmorillonite, sericite, mica, magnesia chlorite, bentonite, asbestos, zeolite, calcium silicate, magnesium silicate, diatomaceous earth, and silica sand; and glass fiber. They can be used alone or in combination of two or more. Among these, silicon dioxide is particularly preferred from the viewpoint of easy extraction.
[0293] From the viewpoint of obtaining good isolation between the polyolefin resin composition and the inorganic material, the mass of the inorganic material relative to their total mass is preferably 3 mass % or more, more preferably 10 mass % or more, and from the viewpoint of ensuring high strength, it is preferably 60 mass % or less, more preferably 50 mass % or less.
[0294] Next, the melt-kneaded product is formed into a sheet to obtain a gel-like sheet. When melt-kneading is performed using an extruder, the extrusion rate of the polyolefin composition, that is, the ratio of the discharge amount Q (kg / hour) of the extruder to the screw speed N (rpm) of the extruder (Q / N, unit: kg / (h·rpm) is preferably 0.1 or more and 7.0 or less, more preferably 0.5 or more and 6.0 or less, and further preferably 1.0 or more and 5.0 or less. If melt-kneading is performed under the condition that Q / N is 0.1 or more and less than 7.0, the liquid paraffin that has undergone phase separation from the resin is more easily dispersed, and therefore, there is a tendency that the pore structure becomes dense and the strength can be increased.
[0295] As a method for manufacturing a sheet-like molded body, for example, the following method can be cited: the molten kneaded product is extruded into a sheet by means of a T-die, etc., and it is cooled to a temperature sufficiently lower than the crystallization temperature of the resin component by contacting a heat conductor, and solidified. As a heat conductor for cooling and solidification, metals, water, air, plasticizers, etc. can be cited. Among these, since the heat conduction efficiency is high, it is preferred to use a metal roller. When the extruded gel-like sheet is contacted with a metal roller, there is a tendency that the heat conduction efficiency is further improved and the sheet is oriented, the film strength is increased, and the surface smoothness of the sheet is also improved by clamping between the rollers, so it is more preferred.
[0296] The casting gap when the molten kneaded product is extruded from the T die into a sheet can be controlled to adjust the average film thickness of the obtained microporous film before compression to the numerical range described above. From this point of view, in the case of, for example, a casting roll, the distance between the rolls is preferably 200 μm or more and 3,000 μm or less, more preferably 500 μm or more and 2,500 μm or less. If the distance between the rolls of the casting roll is 200 μm or more, the risk of film breakage can be reduced in the subsequent stretching process. If the distance between the rolls is 3,000 μm or less, the cooling rate is fast and uneven cooling is prevented. In addition, from the viewpoint of obtaining a thin film and improving the plane orientation and crystallinity and achieving the stretching ratio required to improve compressibility, the casting thickness is preferably 500 μm to 2200 μm, more preferably 700 μm to 2000 μm.
[0297] The extruded sheet-like molded body or gel-like sheet can be calendered. Calendering can be implemented by methods such as using rollers. By implementing calendering, the orientation of the surface layer can be particularly increased. The calendering surface ratio is preferably more than 1 times and less than 3 times, more preferably more than 1 times and less than 2 times. If the calendering ratio exceeds 1 times, there is a tendency that the surface orientation increases and the film strength of the porous film finally obtained increases. If the calendering ratio is less than 3 times, there is a tendency that the orientation difference between the surface layer and the center is small, and a uniform porous structure can be formed in the thickness direction of the film.
[0298] Biaxial stretching process (B):
[0299] In step (B), the gel-like sheet obtained in step (A) is stretched. Step (B) is performed before step (C) of extracting the pore-forming material from the sheet. In step (B), the gel-like sheet is stretched at least once in each of the longitudinal direction and the width direction (i.e., by biaxial stretching) from the viewpoint of controlling the bending rigidity of the polyolefin microporous membrane.
[0300] As a stretching method, for example, methods such as simultaneous biaxial stretching, successive biaxial stretching, multistage stretching, and multiple stretching can be listed. Among them, from the viewpoint of improving film strength and stretching uniformity, and the main structure is easily isotropic in the plane, and the safety of the nail puncture test is good due to the isotropic dispersion of stress during the nail puncture test, it is preferably simultaneous biaxial stretching. Simultaneous biaxial stretching refers to a stretching method that simultaneously implements MD stretching and TD stretching, and the stretching ratio in each direction can be different. Successive biaxial stretching refers to a stretching method that independently implements MD and TD stretching. When stretching is performed along MD or TD, the other directions are set to a non-constrained state or fixed to a constant length.
[0301] In step (B), from the viewpoint of adjusting the porosity after compression, the long crystal period or the crystallite size of the obtained microporous membrane to the numerical range described above, it is preferred to preheat the gel-like sheet before stretching in the stretching furnace, and it is more preferred to increase the preheating coefficient. The preheating coefficient is a value obtained by multiplying the preheating temperature by the preheating wind speed and the preheating time, and is preferably 130000℃·m~300000℃·m, more preferably 150000℃·m~300000℃·m, and further preferably 180000℃·m~300000℃·m. When the preheating furnace is divided into a plurality of chambers with different wind speeds, it is calculated in the form of the wind speed of the preheating furnace as a whole according to the sum of "wind speed of each chamber × furnace length of each chamber / furnace length of the preheating furnace as a whole".
[0302] In the MD stretching of step (B), the MD stretching ratio is preferably adjusted from the viewpoint of adjusting the post-compression porosity, crystal long period or crystallite size of the obtained microporous film to the numerical range of the above description, the viewpoint of orienting the polyethylene as the main component to form a high rigidity backbone, and the viewpoint of improving the compressibility by improving the crystallinity on the basis of achieving high strength of the film by stretching orientation. The MD stretching ratio is preferably more than 5 times, more preferably more than 5 times and less than 10 times, further preferably more than 5 times and less than 9 times, more preferably more than 6 times and less than 10 times, and particularly preferably more than 6 times and less than 8 times. The MD stretching ratio can be adjusted according to, for example, MD stretching temperature, MD stretching wind speed, MD stretching time and MD stretching coefficient.
[0303] From the same viewpoint as above and the viewpoint that even a high molecular weight resin will uniformly apply stress and make the permeability and air permeability distribution of the obtained film good, the lower limit of the MD stretching temperature is preferably 122.0°C or more, more preferably 123.0°C or more, further preferably 124.0°C or more, further preferably 125.0°C or more, particularly preferably 126.0°C or more, and most preferably 127.0°C or more. The upper limit of the MD stretching temperature is preferably 145.0°C or less, more preferably 140.0°C or less, and further preferably 131.0°C or less. It can be inferred that if the MD stretching temperature is from the melting point of the main component -12°C to the melting point, stress is appropriately applied to the film, which is preferred in terms of stretching molding. The MD stretching temperature is more preferably from the melting point of the main component -10°C to the melting point, and further preferably from the melting point of the main component -8°C to the melting point. The MD stretching temperature can be adjusted according to, for example, the MD stretching ratio, the MD stretching wind speed, the MD stretching time, and the MD stretching coefficient.
[0304] In the TD stretching of process (B), the TD stretching ratio is preferably adjusted from the viewpoint of adjusting the post-compression porosity, crystal long period or crystallite size of the obtained microporous film to the numerical range of the above description, the viewpoint of orienting the polyethylene as the main component to form a high rigidity backbone, and the viewpoint of being able to improve compressibility by improving crystallinity on the basis of achieving high strength of the film by stretching orientation. The TD stretching ratio is preferably more than 5 times, more preferably more than 5 times and less than 10 times, further preferably more than 5 times and less than 9 times, more preferably more than 6 times and less than 10 times, particularly preferably more than 6 times and less than 8 times. The TD stretching ratio can be adjusted according to, for example, TD stretching temperature, TD stretching wind speed, TD stretching time and TD stretching coefficient.
[0305] Even when the polyolefin composition provided to step (A) has a high molecular weight composition, it is preferred to adjust the TD stretching temperature of step (B) from the viewpoint of facilitating uniform TD stretching in step (B), improving the cycle characteristics of the non-aqueous secondary battery having the obtained microporous membrane, and even if the resin has a high molecular weight, uniform stress is applied, and the permeability and air permeability distribution of the obtained membrane are good. The lower limit of the TD stretching temperature is preferably 122.0°C or more, more preferably 123.0°C or more, further preferably 124.0°C or more, further preferably 125.0°C or more, particularly preferably 126.0°C or more, and particularly preferably 127.0°C or more, and the upper limit is preferably 145.0°C or less, more preferably 140.0°C or less, and further preferably 131.0°C or less. The TD stretching temperature can be adjusted according to, for example, the TD stretching ratio, the TD stretching wind speed, the TD stretching time, and the TD stretching coefficient.
[0306] In step (B), from the viewpoint of adjusting the porosity, long crystal period or crystallite size of the obtained microporous membrane after compression to the numerical range described above, the ratio of the preheating coefficient to the stretching coefficient (preheating coefficient / stretching coefficient) is preferably adjusted to 5.7 or more and 7.0 or less, more preferably 5.8 or more and 7.0 or less. If the ratio is adjusted to 5.7 or more, heat is further applied in the preheating immediately before stretching, so that there is a tendency that the sheet is easily stretched, and it is easy to present a uniform structure, and the cycle characteristics of the non-aqueous secondary battery with the microporous membrane obtained in the end are improved. If the ratio is adjusted to 7.0 or more, there is a tendency that uneven stretching occurs and an uneven membrane structure is easily formed, and the cycle characteristics of the non-aqueous secondary battery with the microporous membrane obtained in the end are reduced. The stretching coefficient is a value obtained by multiplying the stretching temperature by the stretching wind speed and the residence time of the membrane in the stretching process, preferably 20000℃·m~50000℃·m, more preferably 30000℃·m~50000℃·m. When the stretching furnace is divided into multiple chambers with different wind speeds, the wind speed of the stretching furnace as a whole is calculated based on the sum of "wind speed of each chamber × furnace length of each chamber / furnace length of the stretching furnace as a whole". In addition, the residence time in the stretching furnace is calculated based on "furnace length of the stretching furnace as a whole / average speed of the stretching furnace as a whole".
[0307] In step (B), the biaxial stretching ratio is preferably adjusted from the viewpoint of adjusting the puncture strength of the obtained microporous membrane, the puncture strength converted by weight per unit area, the difference R between the maximum and minimum values of the air permeability at TD3 point, the air permeability and porosity before compression, the heat shrinkage rate, and the ratio of the tensile strength at break to the MD / TD tensile strength at break to the numerical range described above. The biaxial stretching ratio is preferably 5 times × 5 times or more, more preferably 5 × 5 times or more and 10 × 10 times or less, and further preferably 6 × 6 times or more and 10 × 10 times or less. From the same viewpoint, the biaxial stretching ratio is preferably a simultaneous biaxial stretching ratio.
[0308] In step (B), the biaxial stretching temperature is preferably adjusted from the viewpoint of adjusting the puncture strength and puncture strength converted to unit area weight of the obtained microporous membrane, the difference R between the maximum and minimum values of the air permeability at the TD3 point, the air permeability and porosity before compression, the heat shrinkage rate, and the ratio of the tensile strength at break to the MD / TD tensile strength at break to the numerical range described above. The biaxial stretching temperature is preferably 122°C to 147°C, more preferably 123°C to 146°C, further preferably 124°C to 145°C, and further preferably 127°C to 140°C.
[0309] From the viewpoint of increasing the amount of heat applied per unit of resin, making the tensile stress uniform, and improving the distribution of permeability of the resulting film, the PC of the gel-like sheet to be used in step (B) is preferably 22% to 30%, more preferably 25% to 32%.
[0310] In step (B), from the viewpoint of adjusting the puncture strength, puncture strength converted to unit weight, the difference R between the maximum and minimum values of the air permeability at the TD3 point, the air permeability and porosity before compression, and the thermal shrinkage of the obtained microporous membrane within the numerical range described above, it is preferred to adjust the heating coefficient per unit resin. The heating coefficient per unit resin is a value expressed by the following mathematical formula (I), and is preferably 0.26°C / % or more.
[0311] Heating coefficient per unit resin = (biaxial stretching temperature - 115°C) ÷ PC···(I)
[0312] From the viewpoint of increasing the amount of heat applied to each unit of resin, making the tensile stress uniform, and improving the distribution of the permeability of the obtained film, this value is more preferably 0.26°C / % to 1.2°C / %, further preferably 0.34°C / % to 1.0°C / %, further preferably 0.37°C / % to 0.98°C / %, and particularly preferably 0.40°C / % to 0.95°C / %. However, in the case of a dry method in which the film is produced and made porous without the presence of a liquid, since plasticization is not performed, more heat is required to make the tensile stress uniform, and therefore, it is excluded from the value calculated by the above formula.
[0313] Extraction process (C):
[0314] In step (C), the pore-forming material is removed from the sheet-like molded body to obtain a porous membrane. As a method for removing the pore-forming material, for example, a method of immersing the sheet-like molded body in an extraction solvent to extract the pore-forming material and fully drying it can be cited. The method of extracting the pore-forming material can be any of an intermittent method and a continuous method. In order to suppress the shrinkage of the porous membrane, it is preferred that the ends of the sheet-like molded body are restrained in a series of steps of immersion and drying. The residual amount of the pore-forming material in the porous membrane is preferably less than 1% by mass relative to the overall mass of the porous membrane.
[0315] As the extraction solvent used when extracting the pore-forming material, it is preferred to use a solvent that is a poor solvent for the polyolefin resin and a good solvent for the pore-forming material, and whose boiling point is lower than the melting point of the polyolefin resin. Examples of such extraction solvents include hydrocarbons such as n-hexane and cyclohexane; halogenated hydrocarbons such as dichloromethane and 1,1,1-trichloroethane; non-chlorine halogenated solvents such as hydrofluoroethers and hydrofluorocarbons; alcohols such as ethanol and isopropanol; ethers such as diethyl ether and tetrahydrofuran; and ketones such as acetone and methyl ethyl ketone. These extraction solvents can be recovered and reused by operations such as distillation. When an inorganic material is used as the pore-forming material, an aqueous solution of sodium hydroxide, potassium hydroxide, or the like can be used as an extraction solvent.
[0316] Heat fixing process (D):
[0317] In the heat fixing process (D), in order to suppress the shrinkage of the polyolefin microporous film, after the plasticizer extraction of the process (C), the microporous film is heat treated for the purpose of heat fixing (HS). As the heat treatment of the porous film, for the purpose of adjusting the physical properties, a stretching operation performed under an atmosphere of a specified temperature and a specified stretch ratio can be listed, and / or, for the purpose of reducing tensile stress, a relaxation operation performed under an atmosphere of a specified temperature and a specified relaxation rate can be listed. The relaxation operation is a film shrinking operation after the stretching operation. These heat treatments can be performed using a tenter or a roller stretching machine. It should be noted that the heat fixing including stretching and relaxation operations after the plasticizer extraction is preferably performed along TD.
[0318] In step (D), from the viewpoint of adjusting the porosity, crystal long period or crystallite size of the obtained microporous membrane after compression to the numerical range described above, it is preferred to preheat the microporous membrane immediately before stretching. The preheating in step (D) can be controlled by, for example, the preheating temperature.
[0319] The TD stretching temperature in the TD stretching operation of step (D) is preferably 130° C. to 150° C., more preferably 132° C. to 145° C., and even more preferably 133° C. to 140° C. This can reduce the TD heat shrinkage of the obtained film at a temperature of 120° C., and can improve the safety of the non-aqueous secondary battery in a nail penetration test.
[0320] The TD stretching ratio in the TD stretching operation of step (D) is preferably 1.1 times or more, more preferably 1.4 times or more, and further preferably 1.5 times or more. The TD stretching ratio of step (D) is preferably 3 times or less, more preferably 2.5 times or less. By adjusting the TD stretching ratio of step (D) to the above numerical range, the stretching orientation can make the film high-strength, and the porosity can be controlled to optimize the balance between compressibility and permeability, and the stress inside the film can be relaxed to suppress thermal shrinkage. Specifically, the TD thermal shrinkage at a temperature of 120°C can be reduced, and the safety in the nail penetration test can be improved.
[0321] From the viewpoint of crystallizing the polyethylene as the main component of the microporous film and forming a rigid backbone, and adjusting the average film thickness before compression of the obtained microporous film, the puncture strength and the puncture strength converted to unit area weight, the maximum and minimum difference R of the air permeability at TD3 points, the air permeability and porosity before compression, the heat shrinkage rate, and the ratio of the tensile strength to the MD / TD tensile strength to the numerical range described above, the thermal fixation ratio of the process (D), i.e., the relaxation ratio, can be adjusted. The relaxation ratio of the process (D) is preferably 1.4 times or more, more preferably 1.5 times or more, and further preferably 1.5 times or more and 3 times or less. Thus, stretching orientation can make the film high-strength, and the porosity can be controlled to optimize the balance between compressibility and permeability, and the stress inside the film can be relaxed, and the TD thermal shrinkage at a temperature of 120 ° C can be reduced, which can improve the safety of non-aqueous secondary batteries in nail penetration tests.
[0322] From the viewpoint of adjusting the average film thickness of the obtained microporous film before compression to the numerical range described above, reducing the TD heat shrinkage of the obtained microporous film at a temperature of 120°C, and improving the safety of the non-aqueous secondary battery in the nail penetration test, the thermal fixation temperature, i.e., the relaxation temperature, of step (D) can be adjusted. The relaxation temperature of step (D) is preferably 130°C to 150°C, more preferably 132°C to 145°C, further preferably 133°C to 140°C, and even more preferably 135°C to 140°C.
[0323] The polyolefin microporous membrane can be obtained by the manufacturing method including steps (A) to (D). In order to crystallize the polyethylene as the main component of the microporous membrane and form a rigid backbone, the total stretching ratio of the polyolefin microporous membrane finally obtained is preferably 60 times or more, more preferably 61 times or more and 81 times or less.
[0324] From the viewpoint of increasing the amount of heat applied to each unit resin, making the tensile stress uniform, and improving the distribution of the permeability of the final membrane obtained through steps (A) to (D), the PC of the resin composition, gel sheet or porous membrane is preferably 22% to 30% by mass, and more preferably 25% to 32% by mass.
[0325] 〈How to configure the cover layer〉
[0326] The coating layer is disposed on at least one surface of the substrate produced as described above. The method for disposing the coating layer is not particularly limited, and examples thereof include a method of applying a coating solution containing an inorganic filler and a particulate polymer to the substrate and removing the medium.
[0327] As the coating liquid, a dispersion obtained by dispersing an inorganic filler and a particulate polymer in a solvent or dispersion medium (hereinafter referred to as "medium") in which the particulate polymer is not dissolved can be used. Preferably, the particulate polymer can be synthesized by emulsion polymerization, and the emulsion obtained by the emulsion polymerization can be directly used as the coating liquid.
[0328] As the medium of the coating liquid, it is preferably a medium that can uniformly and stably disperse or dissolve inorganic fillers, granular polymers and water-soluble polymers as needed, such as N-methylpyrrolidone, N, N-dimethylformamide, N, N-dimethylacetamide, water, ethanol, methanol, toluene, hot xylene, dichloromethane and hexane. As the medium of the coating liquid, it is preferably water or a mixed medium comprising water and a water-soluble organic medium. As a water-soluble organic medium, it is not particularly limited, and for example ethanol and methanol can be cited. Among these, water is more preferably used. When the coating liquid is applied to the substrate, if the coating liquid enters the interior of the substrate, the granular polymer containing the polymer will block the surface and interior of the hole of the substrate, and the permeability is easily reduced. In this respect, in the case of using water as an aqueous dispersion of the coating liquid medium, the coating liquid is difficult to enter the interior of the substrate, and the granular polymer containing the polymer is likely to be mainly present on the outer surface of the substrate, therefore, it is more effective to suppress the reduction of permeability, so it is preferred.
[0329] The coating liquid may contain any additives. Examples of the additives of the coating liquid include dispersants such as surfactants, thickeners, wetting agents, defoamers, and pH adjusters including acids and alkalis.
[0330] Examples of methods for dispersing or dissolving the inorganic filler, particulate polymer and, if necessary, water-soluble polymer in the medium of the coating liquid include mechanical stirring using a ball mill, a bead mill, a planetary ball mill, a vibration ball mill, a sand mill, a colloid mill, an attritor, a roller mill, a high-speed impeller dispersion, a distributor, a homogenizer, a high-speed impact mill, an ultrasonic dispersion and a stirring blade.
[0331] As a step for preparing the coating liquid, it is preferred that: first, a water-soluble polymer is added to the coating liquid in which the inorganic filler is dispersed, and then a resin binder and a granular polymer are added. By preparing the coating liquid in this order, the water-soluble polymer can adsorb and protect the metal ions contained in the inorganic filler, and the aggregation of the resin binder and the granular polymer can be prevented.
[0332] From the viewpoint of adjusting the inclination rate of the coating layer and the contact ratio of the granular polymer to the substrate surface, the viscosity of the coating liquid is preferably 20 mPa s or more and 80 mPa s or less, more preferably 60 mPa s or less, and further preferably 40 mPa s or less. From the viewpoint that the sedimentation of the granular polymer in the process of removing the solvent from the coating film to form the coating layer after coating becomes faster, the inclination rate of the coating layer is improved, and the contact ratio of the granular polymer to the substrate surface is improved, the viscosity of the coating liquid is preferably 20 mPa s or more and 80 mPa s or less. As a means of controlling the viscosity of the coating liquid, the aspect ratio of the inorganic filler, the coefficient of variation of the particle size distribution of the inorganic filler, and the type of thickener can be listed. Using these means, the viscosity of the coating liquid can be reduced during the inertization of the coating liquid (forming the coating layer by drying), and the meniscus of the coating liquid for the granular polymer can be increased (improving wettability), as a result, the inclination rate of the coating layer can be increased, and the adhesion to the electrode can be increased.
[0333] Before coating, the substrate can be surface treated. If surface treatment is implemented, the coating solution is easily applied, and the adhesion of the substrate to the thermoplastic polymer is improved, and the 180 ° peel strength is easily controlled to more than 200gf / cm, so it is preferred. As the method for surface treatment, for example, corona discharge treatment, plasma treatment, mechanical roughening, solvent treatment, acid treatment and ultraviolet oxidation can be listed. As surface treatment, corona discharge treatment can be listed.
[0334] The method of coating the coating liquid on the substrate is not particularly limited as long as the method that can realize the desired coating pattern, coating film thickness and coating area. As coating method, for example, gravure coating method, small diameter gravure coating method, reverse roll coater method, transfer roll coater method, kiss coating method, dip coating method, knife coating method, air knife coating method, scraper coating method, rod coating method, extrusion coating method, cast coating method, die coating method, screen printing method, spray coating method and inkjet coating method etc. can be listed. Among these, from the viewpoint that the degree of freedom of the coating shape of granular polymer is high and the preferred area ratio is easily obtained, preferably gravure coating method or spray coating method.
[0335] In the coating method, it is preferred to coat at a high shear rate by a method such as a gravure coating method, and the shear rate is preferably 40,000 sec. -1More than 120,000 seconds -1 When the shear rate is within this range, the dispersion of the particulate polymer as primary particles becomes favorable, and it becomes easier to control the 180° peel strength to 200 gf / cm or more.
[0336] There are no particular limitations on the method of removing the medium from the coating film after coating, as long as it does not adversely affect the substrate and the coating layer. Examples include a method of drying at a temperature below the melting point while fixing the substrate; a method of drying under reduced pressure at a low temperature; a method of immersing the polymer in a medium that is a poor solvent for the granular polymer and extracting the medium while solidifying the granular polymer into granules.
[0337] <Production of wound body of separator>
[0338] The obtained separator for an electrical storage device is preferably in the form of a wound body. By making the separator into a wound body, it can be easily pulled out at high speed, and the productivity in the production process of the electrical storage device can be improved.
[0339] 《Electrical Storage Equipment》
[0340] The power storage device of the present embodiment includes a separator for power storage device of the present embodiment. As the power storage device, there is no particular limitation, and batteries such as non-aqueous electrolyte secondary batteries, capacitors (condenser) and capacitors (capacitor) can be listed. Among these, in order to make use of the advantages of the separator for power storage device of the present embodiment, it is preferably a battery, more preferably a non-aqueous electrolyte secondary battery, and further preferably a lithium-ion secondary battery. The lithium-ion secondary battery has a positive electrode, a negative electrode, a separator for power storage device of the present embodiment arranged between the positive electrode and the negative electrode, and a non-aqueous electrolyte. The power storage device of the present embodiment has excellent characteristics such as power storage performance by including a separator for power storage device. In the case of a lithium-ion secondary battery, the battery characteristics are excellent.
[0341] In the case where the power storage device of the present embodiment is a lithium ion secondary battery, the positive electrode, the negative electrode and the non-aqueous electrolyte are not limited, and known substances can be used respectively. As the positive electrode, a positive electrode having a positive electrode active material layer containing a positive electrode active material on a positive electrode collector can be suitably used. As the positive electrode collector, for example, aluminum foil can be listed. As the positive electrode active material, lithium-containing composite oxides such as LiCoO2, LiNiO2, spinel-type LiMnO4 and olivine-type LiFePO4 can be listed. In addition to the positive electrode active material, the positive electrode active material layer may also appropriately contain a binder, a conductive material, etc.
[0342] As the negative electrode, a negative electrode having a negative electrode active material layer containing a negative electrode active material on a negative electrode current collector can be appropriately used. As the negative electrode current collector, for example, copper foil can be cited. As the negative electrode active material, for example, carbon materials such as graphite, non-graphitizable carbon, easily graphitizable carbon, and composite carbon can be cited; as well as silicon, tin, metallic lithium, and various alloy materials.
[0343] As the non-aqueous electrolyte, there is no particular limitation, and an electrolyte obtained by dissolving an electrolyte in an organic solvent can be used. As the organic solvent, for example, propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate can be listed. As the electrolyte, for example, lithium salts such as LiClO4, LiBF4 and LiPF6 can be listed.
[0344] 《Manufacturing method of electric storage device》
[0345] The method for manufacturing an electrical storage device using the separator of the present embodiment is not particularly limited. The following method can be exemplified. First, the separator of the present embodiment is manufactured using the above method. The size and shape of the separator can be, for example, a longitudinal shape with a width of 10 to 500 mm, preferably 80 to 500 mm, and a length of 200 to 10,000 m, preferably 1,000 to 6,000 m. Next, the positive electrode-separator-negative electrode-separator or negative electrode-separator-positive electrode-separator are stacked in the order of positive electrode-separator-negative electrode-separator, and wound into a circular or flat spiral shape to obtain a wound body. The wound body can be manufactured by placing the wound body in a device can (such as a battery can) and then injecting an electrolyte. Alternatively, it can be manufactured by folding the electrode and the separator to form a wound body, putting it into a device container (such as an aluminum film) and injecting an electrolyte.
[0346] Specifically, a method in which a separator and an electrode including a current collector and an active material layer formed on at least one surface of the current collector are overlapped so that the covering layer faces the active material layer and then pressurized can be exemplified.
[0347] The pressing temperature is preferably at a temperature at which the adhesiveness can be effectively exhibited. 1.00 It should be noted that T 1.00 It refers to the temperature showing the minimum value of DDSC from 0°C to 150°C when the value obtained by differentiating the heat flow difference per unit time measured by DSC (differential scanning calorimetry) with temperature is defined as DDSC. 1.00Pressing is performed at a temperature above 35°C, so that the covering layer is fully deformed and good adhesion can be obtained. For example, it is preferably above 35°C. From the viewpoint of suppressing the clogging or thermal shrinkage of the holes in the separator caused by hot pressing, the pressing temperature is preferably lower than the melting point of the material contained in the substrate, and more preferably below 130°C. From the viewpoint of suppressing the clogging of the holes in the separator, the pressing pressure is preferably below 20MPa. In the case of roller pressurization, the pressing time can be less than 1 second, and in the case of surface pressurization, the pressing time can be several hours. From the viewpoint of productivity, the pressing time is preferably less than 2 hours. If the separator for storage device of the present embodiment is used and undergoes the above-mentioned manufacturing process, the press unwinding (press back) when the winding body containing the electrode and the separator is pressurized can be suppressed. Therefore, the reduction in the yield in the equipment assembly process can be suppressed, and the production process time can be shortened.
[0348] Adhesion can be imparted to the wound body without applying pressure. Specifically, the following method can be exemplified: the wound body is stored in a device can and an electrolyte is injected, and adhesion is imparted between the electrodes facing the covering layer of the separator by utilizing the pressure generated in the device can when the power storage device is manufactured or utilizing the pressure associated with expansion and contraction of the electrodes caused by charging and discharging of the power storage device.
[0349] The power storage device manufactured as described above, especially the lithium ion secondary battery, includes the separator of this embodiment having high adhesion to the electrode and low thermal shrinkage, and therefore has excellent battery characteristics (rate characteristics) and excellent resistance to long-term continuous operation (cycle characteristics).
[0350] Example
[0351] Hereinafter, the embodiments of the present application will be described in detail by way of examples and comparative examples, but the present application is not limited to these examples and comparative examples.
[0352] 《Measurement and evaluation methods》
[0353] 〈Thickness of the covering layer and protrusion amount of the granular polymer〉
[0354] The separator was frozen and cut, and its cross section was confirmed using SEM (model: S-4800, manufactured by HITACHI). The thickness of the layer containing the thermoplastic polymer was measured from the obtained field of view. Specifically, the sample of the separator was cut into pieces of about 1.5 mm × 2.0 mm and stained with ruthenium. The dyed sample and ethanol were put into a gelatin capsule, and after freezing it with liquid nitrogen, the sample was cut with a hammer. The cut sample was subjected to osmium vapor deposition and observed under the conditions of an acceleration voltage of 1.0 kV and 30,000 times. In the SEM image, the distance from the boundary line between the substrate and the covering layer to the outer surface of the covering layer of the inorganic filler part in the covering layer was measured as the thickness (μm) of the covering layer. It should be noted that the "inorganic filler part" refers to: the diameter of each protruding granular polymer is set to D, and the part that deviates from each protruding granular polymer by more than 1.5D. The "diameter of each protruding granular polymer" measures the area circle equivalent diameter. The thickness of the covering layer was measured at 20 locations, and the average value was calculated. The maximum distance (μm) from the boundary line between the substrate and the covering layer to the outline of the granular polymer of the protruding part of the granular polymer in the covering layer was measured. The maximum distance to the outline of the granular polymer was measured at 20 locations, and the average value was calculated. The protruding amount (μm) of the granular polymer was calculated by subtracting the thickness of the inorganic filler part of the covering layer from the maximum distance to the outline of the granular polymer, and the ratio of the protruding amount of the granular polymer of the covering layer to the thickness of the inorganic filler part was calculated.
[0355] 〈180° peel strength〉
[0356] Use double-sided tape to stick the surface of the separator cut into 2mm×7mm on the opposite side of the covering layer to be measured on the glass plate, and stick a tape (product name "Mending Tape MP-12", manufactured by 3M) on the covering layer. Peel off the front end of the tape by 5mm, and use a tensile testing machine (model: AG-IS, SLBL-1kN, manufactured by Shimadzu Corporation) to clamp the front end of the tape with a clamp in such a way that the tape is peeled off at an angle of 180° relative to the surface direction of the separator. Set the tensile speed to 50mm / sec, the temperature to 25 degrees, and the relative humidity to 40% to perform the tensile test and measure the tensile strength (N / m). It should be noted that 1gf / cm can be converted to 0.98N / m.
[0357] 〈Slope of the overburden layer〉
[0358] The separator was frozen and cut, and its cross section was confirmed using SEM (model: S-4800, manufactured by HITACHI). The thickness of the layer containing the thermoplastic polymer was measured from the obtained field of view. Specifically, the separator sample was cut into pieces of about 1.5 mm × 2.0 mm and stained with ruthenium. The stained sample and ethanol were placed in a gelatin capsule, and after freezing it with liquid nitrogen, the sample was cut with a hammer. Osmium was vapor-deposited on the cut sample, and it was observed under the conditions of an acceleration voltage of 1.0 kV and 30,000 times. Figure 2 As schematically shown in , in the SEM image of the cut sample cross section, the distance from the boundary line between the substrate and the covering layer to the outer surface of the covering layer is measured as the thickness L1 (μm) of the inorganic filler part of the covering layer. It should be noted that the "inorganic filler part" refers to: the volume average particle size of the protruding granular polymer is set to D, and the part that deviates from each protruding granular polymer by more than 1.5D. In addition, the maximum distance L2 (μm) from the boundary line between the substrate and the covering layer to the outer surface of the inorganic filler of the inclined covering layer and the maximum distance L3 (μm) to the contour of the protruding granular polymer are measured, and the inclination L2 / L1 of the covering layer and the coverage (L2-L1) / (L3-L1) of the protruding part are calculated. The inclination L2 / L1 of the covering layer and the coverage (L2-L1) / (L3-L1) of the protruding part are measured at 200 locations, and the average value is calculated.
[0359] 〈Contact ratio of protruding particle-shaped polymer to substrate〉
[0360] The separator was frozen and cut, and its cross section was confirmed using SEM (model: S-4800, manufactured by HITACHI). The thickness of the layer containing the thermoplastic polymer was measured from the obtained field of view. In detail, the sample of the separator was cut into pieces of about 1.5 mm × 2.0 mm and stained with ruthenium. The stained sample and ethanol were put into a gelatin capsule, and after freezing it with liquid nitrogen, the sample was cut with a hammer. Osmium was evaporated on the cut sample and observed under the conditions of an acceleration voltage of 1.0 kV and 30,000 times. In the SEM image, for 200 granular polymers with cut surfaces protruding from the thickness of the inorganic filler part of the covering layer, the number of particles in contact with the substrate was measured as the contact ratio between the protruding granular polymer and the substrate.
[0361] <Ratio of the number of particulate polymers protruding from the thickness of the inorganic filler portion of the covering layer>
[0362] The separator was frozen and cut, and its cross section was confirmed using SEM (model: S-4800, manufactured by HITACHI Corporation). The thickness of the layer containing the thermoplastic polymer was measured from the obtained field of view. In detail, the sample of the separator was cut into pieces of about 1.5 mm × 2.0 mm and stained with ruthenium. The stained sample and ethanol were put into a gelatin capsule, and after freezing it with liquid nitrogen, the sample was cut with a hammer. Osmium was evaporated on the cut sample and observed under the conditions of an acceleration voltage of 1.0 kV and 30,000 times. In the SEM image, 200 granular polymers present on the cut surface were observed, and the number of granular polymers protruding from the thickness of the inorganic filler part of the covering layer was measured as the ratio of the number of granular polymers protruding from the thickness of the inorganic filler part of the covering layer.
[0363] <Average number of adjacent particulate polymers>
[0364] For the surface of the separator for storage devices deposited with osmium, a scanning electron microscope (SEM) (model: "SU-8220", manufactured by HITACHI) and an energy dispersive X-ray spectrometer (EDX) (model: ULTIM EXTREME, manufactured by Oxford) were used to perform element mapping. At this time, the SEM detector selected secondary electrons, set the acceleration voltage to 3 kV, set the mapping accumulation number to 20 times, and implemented the mapping measurement of carbon atoms at a magnification of 10,000 times. In the mapping of carbon atoms, the portion visually identified as a circle is regarded as one granular polymer, and for all granular polymers in one field of view, the number of particles whose outer edges are less than 0.2 μm apart is measured. The measurement is performed in three fields of view, and the average value of all the measured values is taken as the average number of adjacent granular polymers.
[0365] <Ratio of the average particle size of the protruding particulate polymer to the average particle size of the inorganic filler>
[0366] The cross section of the separator for storage devices deposited with osmium was observed using a scanning electron microscope (SEM) (model: "S-4800", manufactured by HITACHI) at an accelerating voltage of 1.0 kV and 10,000 times, and the measurement was performed. Specifically, 200 area circle equivalent diameters of any inorganic filler particles were measured, and the volume average particle size MV was calculated based on their values as the average particle size. Similarly, the SEM image of the cross section of the separator for storage devices deposited with osmium was observed, and 200 area circle equivalent diameters of the granular polymer protruding from the thickness of the inorganic filler portion of the covering layer were measured, and the volume average particle size MV was calculated based on their values as the average particle size. According to the average particle size of the inorganic filler or the average particle size of the granular polymer obtained by the above method, the ratio of the average particle size of the protruding granular polymer to the average particle size of the inorganic filler is calculated.
[0367] 〈Number of granular polymers within a radius of 10 μm〉
[0368] For the surface of the separator for storage devices deposited with osmium, a scanning electron microscope (SEM) (model: "SU-8220", manufactured by HITACHI) and an energy dispersive X-ray spectrometer (EDX) (model: ULTIM EXTREME, manufactured by Oxford) were used to perform element mapping. At this time, the SEM detector selected secondary electrons, the acceleration voltage was set to 3 kV, the number of mapping accumulations was set to 20 times, and the mapping measurement of carbon atoms was performed at a magnification of 50 million times. In the mapping of carbon atoms, the portion visually identified as a circle was regarded as one granular polymer, and for all granular polymers in one field of view, the number of granular polymers present within a radius of 10 μm from any granular polymer was measured, and the average value was calculated.
[0369] 〈Dichloromethane soluble components〉
[0370] The following method is used to determine the dichloromethane soluble components in the substrate and separator. The substrate or separator sampled into 100×100 mm is de-electrified and weighed using a precision balance (W0(g)). Next, 200 ml of dichloromethane is added to a sealed container, and the above separator is immersed at room temperature for 15 minutes. Thereafter, the separator is taken out, dried at room temperature for 3 hours, de-electrified in the same manner as above, and weighed using a precision balance (W1(g)). The dichloromethane soluble components are calculated using the following formula.
[0371] Dichloromethane soluble content (%) = {(W1-W0) / W0}×100
[0372] 〈Total amount of metal cations〉
[0373] Take 0.60g of the separator and place it in a pressurized decomposition container made of Teflon (registered trademark), add 10ml of sulfuric acid and seal it, and heat it in an air bath at 200°C for 15 hours. After cooling, the solution in the container is transferred to a 100ml volumetric flask made of resin and fixed to volume as a sample solution. The sample solution is measured by inductively coupled plasma atomic emission analysis (ICP-OES) (model: "ICPE-9000", made by Shimadzu Corporation), and the content of each element is calculated using a standard curve made from a standard solution.
[0374] 〈Heat shrinkage ratio〉
[0375] As a sample, cut the separator into 100 mm in MD and 100 mm in TD, and place it in an oven at 130°C or 150°C for 1 hour. At this time, sandwich the sample between two pieces of paper so that the warm air does not directly contact the sample. After taking the sample out of the oven and cooling it, measure the length (mm) and calculate the thermal shrinkage using the following formula. Measure along MD and TD, and set the larger value as the thermal shrinkage.
[0376] Thermal shrinkage (%) = {(100-length after heating) / 100}×100
[0377] 〈Viscosity average molecular weight〉
[0378] The intrinsic viscosity [η] (dl / g) in a decalin solvent at 135° C. was determined in accordance with ASTM-D4020.
[0379] For polyethylene, the following formula is used for calculation.
[0380] [η] = 6.77 × 10 -4 M v 0.67
[0381] For polypropylene, Mv is calculated using the following formula.
[0382] [η] = 1.10 × 10 -4 M v 0.80
[0383] 〈Weight average molecular weight and number average molecular weight〉
[0384] ALC / GPC 150C (trademark) manufactured by Waters was used to measure standard polystyrene under the following conditions to prepare a calibration curve. In addition, chromatograms were measured for each of the following polymers under the same conditions, and the weight average molecular weight of each polymer was calculated from the calibration curve by the following method.
[0385] Column: 2 GMH6-HT (trademark) + 2 GMH6-HTL (trademark) manufactured by Tosoh Corporation Mobile phase: o-dichlorobenzene
[0386] Detector: Differential Refractometer
[0387] Flow rate: 1.0ml / min
[0388] Column temperature: 140°C
[0389] Sample concentration: 0.1wt%
[0390] 〈Weight average molecular weight and number average molecular weight of polyethylene and polypropylene〉
[0391] By multiplying each molecular weight component in the obtained calibration curve by 0.43 (Q factor of polyethylene / Q factor of polystyrene = 17.7 / 41.3) or 0.64 (Q factor of polypropylene / Q factor of polystyrene = 26.4 / 41.3), a polyethylene-converted or polypropylene-converted molecular weight distribution curve is obtained, and the weight average molecular weight and number average molecular weight are calculated.
[0392] <Weight average molecular weight and number average molecular weight of resin composition or resin microporous membrane>
[0393] The weight average molecular weight and the number average molecular weight were calculated in the same manner as in the case of polyethylene except that the Q factor value of the polyolefin having the largest mass fraction was used.
[0394] 〈Melt Flow Index (MI)〉
[0395] The melt flow index (MI) of the microporous film was measured in accordance with JIS K7210:1999 (Plastics - Melt mass flow rate (MFR) and melt volume flow rate (MVR) of thermoplastics). A load of 21.6 kgf was applied to the film at 190°C, and the amount of resin (g) flowing out from a flow metering hole with a diameter of 2 mm and a length of 10 mm in 10 minutes was measured, and the value obtained by rounding off the first decimal place was used as the MI.
[0396] 〈DSC measurement〉
[0397] DSC (Differential Scanning Calorimetric) was measured using DSC60 manufactured by Shimadzu Corporation. First, the PO microporous membrane was punched into a circle with a diameter of 5 mm and several pieces were overlapped to make 3 mg, which was used as a measurement sample. The sample was laid in an aluminum oven sample pot with a diameter of 5 mm, a compression lid was loaded, and the sample sealer was used to fix it in the aluminum pot. Under a nitrogen atmosphere, the temperature was increased from 30°C to 200°C at a heating rate of 10°C / min (first heating), and after keeping at 200°C for 5 minutes, the temperature was decreased from 200°C to 30°C at a cooling rate of 10°C / min. Then, after keeping at 30°C for 5 minutes, the temperature was increased from 30°C to 200°C at a heating rate of 10°C / min again (second heating). In the melting endothermic curve of the second heating, the temperature reaching the maximum is set to the melting point of the PO microporous membrane. When there are multiple maximum values, the 1st peak is detected as the largest peak. It should be noted that the temperature at which the maximum melting endothermic curve reaches a maximum value can be adopted as the melting point (Tm) of the PO microporous membrane.
[0398] Density (g / cm 3 )〉
[0399] The density of the sample was measured by a density gradient tube method (23° C.) in accordance with JIS K7112:1999.
[0400] 〈Weight per unit area (g / m 2 )〉
[0401] Unit area weight is per unit area (1m 2 ) of the polyolefin microporous membrane. After sampling to 1m×1m, the weight was measured using an electronic balance (AUW120D) manufactured by Shimadzu Corporation. It should be noted that when it is not possible to sample 1m×1m, the appropriate area was cut and the weight was measured, and then converted to per unit area (1m 2 )’s weight (g).
[0402] <Average film thickness of microporous film before compression (μm)>
[0403] The thickness was measured at an ambient temperature of 23±2°C using a micro thickness gauge (KBN type, terminal diameter: Φ5 mm) manufactured by Toyo Seiki Co., Ltd. It should be noted that when measuring the thickness, the microporous membrane was sampled into 10 cm×10 cm, and multiple microporous membranes were overlapped in such a way that the overlap was 15 μm or more, and the thickness at 9 locations was measured and the average value was calculated. The value obtained by dividing the average value by the number of overlapped sheets was set as the thickness of one microporous membrane.
[0404] 〈Porosity before compression (%)〉
[0405] A sample of 3 cm × 3 cm square, 1 cm × 1 cm square, 5 cm × 5 cm square or 10 cm × 10 cm square was cut from the polyolefin microporous membrane, and its volume (cm 3 ) and mass (g). According to their values and density (g / cm 3 ), and the porosity (%) before compression was calculated using the following formula.
[0406] Porosity (%) = (volume-mass / density of mixed composition) / volume×100
[0407] In addition, the density of a mixed composition uses the value calculated from each density and mixing ratio of the polyolefin resin used and other components.
[0408] 〈Porosity after compression (%)〉
[0409] Prepare 2 rubber cushioning materials with a thickness of 0.8 mm, 2 PET films with a thickness of 0.1 mm, and 2 microporous membranes. Stack them in the order of 1 cushioning material, 1 PET film, 2 microporous membranes, 1 PET film, and 1 cushioning material, and place the resulting laminate statically in a press. The cushioning material surfaces on both sides of the laminate are clamped and pressure is applied using a press, thereby performing a compression test. The compression test was performed under conditions of a temperature of 70°C, a pressure of 8 MPa, and a compression time of 3 minutes. The compression rate after pressure relaxation is measured as needed. The compression rate is measured within a period of 2 hours to 24 hours after the pressure relaxation. After the compression test, the pressure is relaxed, the microporous membrane is taken out from the laminate, and the microporous membrane after the compression test is used as a sample, and the porosity (%) after compression is measured using the same method as the above-mentioned "porosity (%) before compression".
[0410] The same compression test as above was carried out at a temperature of 30°C and a compression time of 3 minutes at pressures of 2.5MPa, 5MPa, 7.5MPa and 10MPa. In addition, the microporous membrane was removed from the laminate 1 hour after the pressure was relaxed, and the average membrane thickness after compression (9-point average) and the air permeability after compression were measured. In addition, the porosity after compression was calculated based on the unit area weight and the average membrane thickness after compression. Finally, based on the 4 measurement points compressed under the above 4 pressures, an approximate power was used to make the porosity after compression and the air permeability after compression. Figure 3 That approximate curve. Figure 3 Among them, membrane types A to C are commercially available polyolefin separators.
[0411] 〈Air permeability before compression (seconds / 100cm 3 )〉
[0412] The air permeability was measured using an OGEN air permeability meter "EGO2" manufactured by Asahi Seiko Co., Ltd. The air permeability was measured at three points in the width direction of the film, 5 cm from both ends and one point in the center, and the average value was calculated.
[0413] <Puncture strength and puncture strength converted from unit area weight>
[0414] The microporous membrane was fixed using a hand-held compression tester KES-G5 (trademark) manufactured by KATOTECH, using a sample holder with an opening diameter of 11.3 mm. Next, a puncture test was performed on the central part of the fixed microporous membrane at a curvature radius of 0.5 mm at the tip of the needle, a puncture speed of 2 mm / sec, a room temperature of 23°C, and an atmosphere of 40% humidity, thereby measuring the puncture strength (gf) in the form of the maximum puncture load. The measured value of the puncture test is a total of 3 points measured along the TD of the membrane from two locations at the inner side of 10% of the total width toward the center from both ends and 1 point in the center, and their average value is calculated.
[0415] The puncture strength converted from the weight per unit area was calculated using the following formula.
[0416] Puncture strength converted from unit area weight [gf / (g / m 2 )] = puncture strength [gf] / unit area weight [g / m 2 ]
[0417] Here, regarding the puncture strength and the puncture strength converted per unit area weight of a separator having at least one layer provided on a polyolefin microporous membrane substrate, from the perspective of evaluating the strength of the resin and the strength per unit area weight, the characteristics are evaluated based on the puncture strength and the puncture strength converted per unit area weight of the polyolefin microporous membrane substrate.
[0418] 〈Aperture(nm): Semi-dry〉
[0419] The average pore size (nm) was measured using a Perm Porometer (Porous Materials, Inc.: CFP-1500AE) according to the semi-dry method. The immersion liquid used was a perfluoropolyester (trade name "Galwick", surface tension 15.6 dyn / cm) manufactured by the same company. The applied pressure and air permeation were measured for the dry curve and the wet curve, and the average pore size dHD (nm) was calculated using the following formula based on the pressure PHD (Pa) at which the half of the dry curve intersected the wet curve.
[0420] dHD=2860×γ / PHD
[0421] 〈Fuse (interruption) temperature〉
[0422] Prepare 2 Ni foils (A, B) with a thickness of 10 μm, a rectangular part of 15 mm long and 10 mm wide is left on one Ni foil A and masked with Teflon (registered trademark) tape, and a separator of the measurement sample is placed on the other Ni foil B, and the two ends of the separator are fixed with Teflon (registered trademark) tape. After the Ni foil B is immersed in a 1 mol / L lithium fluoroborate solution (solvent: propylene carbonate / ethylene carbonate / γ-butyrolactone = a mixed solvent with a volume ratio of 1 / 1 / 2) and the electrolyte is impregnated in the separator, the Ni foils (A, B) are pasted, and two glass plates are used, and both sides are pressed with a clamp. The Ni foil electrode made in this way is put into an oven at 25°C and heated to 200°C at 2°C / min. The impedance change at this time is measured under the conditions of 1V and 1kHz using the resistance measuring device "AG-4311" (made by Ando Electric Co., Ltd.). The temperature at which the impedance value in the measurement reaches 1000Ω is defined as the fuse temperature (°C).
[0423] <Determination of withstand voltage before compression per unit area weight>
[0424] A piece of MD10cm×TD10cm was cut out near the center of the width direction of the polyolefin microporous membrane, and clamped with an aluminum plate of 5mm in diameter. The withstand voltage before compression per unit area weight was measured using a withstand voltage measuring machine (TOS9201) manufactured by Kikusui Electronics Industry Co., Ltd. Regarding the measurement conditions, the DC voltage was started from an initial voltage of 0V, and the voltage was applied at a boost rate of 100V / sec. The voltage value (kV) when the current value was 0.2mA was set as the withstand voltage measurement value of the microporous membrane. It should be noted that a total of 25 points of MD5 points×TD5 points were measured at intervals of 15mm, and the average value was set as the withstand voltage measurement value. Regarding the withstand voltage per unit area weight, the ratio of withstand voltage to unit area weight (withstand voltage / unit area weight) was calculated.
[0425] 〈Crystal structure analysis〉
[0426] The long period of crystals in polyolefin microporous membranes was measured by transmission method small angle X-ray scattering measurement using NANOPIX manufactured by Rigaku Corporation. The sample was irradiated with CuKα rays, and the scattering was detected using a semiconductor detector HyPix-6000. The measurement was performed under the conditions of a sample-detector distance of 1312 mm, an output power of 40 kV, and 30 mA. The optical system used point focusing, and the measurement was performed under the conditions of slit diameters of 1st slit: φ = 0.55 mm, 2nd slit: open, guard slit: φ = 0.35 mm. It should be noted that the sample was set in a manner that the sample surface was perpendicular to the X-ray incident direction.
[0427] The crystallite size of the polyethylene MDND surface (110) in the polyolefin microporous membrane was measured by wide-angle X-ray scattering measurement using a NANOPIX manufactured by Rigaku Corporation. The sample was irradiated with CuKα rays, and the scattering was detected using an imaging plate. The measurement was performed under the conditions of a sample-detector distance of 110 mm, an output power of 40 kV, and 30 mA. The optical system used point focusing, and was performed under the conditions of a slit diameter of 1st slit: φ = 1.2 mm, guard slit: φ = 0.35 mm. It should be noted that the sample was set in such a way that the sample surface presented an angle of 11.0° with the X-ray incident direction. At this time, the X-ray incident direction was made perpendicular to the MD of the sample.
[0428] 〈Crystal long period [nm]〉
[0429] The SAXS curve I(q) was obtained by using the circular average of the X-ray scattering pattern obtained by HyPix-6000. In the Linear-Linear plot of the obtained one-dimensional curve I(q), the -1 <q<0.6nm -1 The baseline of the straight line is drawn within the range of , and the Gaussian function is used for fitting. The position where the maximum intensity is reached is taken as the peak position q originating from the long period of the crystal m , calculate the crystal long period according to the following formula.
[0430] d=2π / q m
[0431] {Where, d (nm): the long period of the crystal
[0432] q m (nm -1 ): peak position originating from lamellae in SAXS curve}
[0433] 〈Crystalline size〉
[0434] The obtained XRD curve is separated into three peaks in the range of 2θ=10.0° to 2θ=30.0°: the orthorhombic (110) diffraction peak, the orthorhombic (200) diffraction peak, and the amorphous peak. The crystallite size is calculated according to the Scherrer formula (Formula 1) based on the half-value full width of the (110) diffraction peak. The (110) diffraction peak and the (200) diffraction peak are approximated by the Voigt function, and the amorphous peak is approximated by the Gaussian function. It should be noted that the peak position of the amorphous peak is 2θ=19.6°, and the half-value full width is fixed at 6.3°. The peak position and half-value full width of the crystalline peak are peak separated and not particularly fixed. The crystallite size is calculated using the Scherrer formula (the following formula) based on the half-value full width of the (110) diffraction peak calculated by peak separation.
[0435] D(110)=Kλ / (βcosθ)
[0436] {Wherein, D(110): crystallite size (nm)
[0437] K: 0.9 (constant)
[0438] λ: wavelength of X-rays (nm)
[0439] β: (β1 2 -β2 2 ) 0.5
[0440] β1: The half-value full width of the (hkl) peak calculated from the peak separation result (rad)
[0441] β2: Full width at half maximum of the expansion of the incident beam (rad)
[0442] θ: Bragg angle}
[0443] It should be noted that the crystal long period and crystallite size based on crystal structure analysis are preferably measured in the substrate state before coating. However, in terms of the principle of X-ray structure analysis, the same results can be obtained whether the measurement is performed using the coated separator or the coating layer is peeled off from the coated separator and then measured.
[0444] 〈Smoothness (sec / 10cm 3 )〉
[0445] In accordance with ISO 8791-5:2020, the smoothness of the polyolefin microporous membrane was measured in an atmosphere of 30°C and 40% humidity using a stainless steel nozzle with an inner diameter of 0.15 mm and a length of 50 mm in an air permeability smoothness meter model EYO-5 manufactured by Asahi Seiko Co., Ltd. The surface smoothness of one surface and the other surface of the polyolefin microporous membrane were measured, and the average value of the smoothness of one surface and the other surface was also calculated as described above.
[0446] 〈Average pore size of polyolefin microporous membrane〉
[0447] It is known that the fluid inside the capillary is based on Knudsen flow when the mean free path of the fluid is greater than the pore diameter of the capillary, and is based on Poiseuille flow when the mean free path of the fluid is less than the pore diameter of the capillary. Therefore, it is assumed that the air flow in the air permeability measurement of the layer containing the thermoplastic polymer is based on Knudsen flow, and the water flow in the water permeability measurement of the substrate is based on Poiseuille flow.
[0448] The average pore size d (μm) of the polyolefin microporous membrane is calculated based on the air permeation rate constant R gas (m 3 / (m 2 ·sec·Pa)), water permeation rate constant R liq (m 3 / (m 2 ·sec·Pa)), air molecular velocity ν (m / sec), water viscosity η (Pa·sec), standard pressure Ps (=101325Pa), porosity ε (%), and film thickness L (μm), and use the following formula to calculate.
[0449] d=2ν×(R liq / R gas )×(16η / 3Ps)×10 6
[0450] Here, R gas The air permeability (sec) was calculated using the following formula.
[0451] R gas =0.0001 / (air permeability×(6.424×10 -4 )×(0.01276×101325))
[0452] In addition, R liq According to the water permeability (cm 3 / (cm 2 ·sec·Pa)) and use the following formula to calculate it.
[0453] R liq = Water permeability / 100
[0454] It should be noted that the water permeability was determined as follows. A layer containing a thermoplastic polymer pre-immersed in ethanol was placed in a stainless steel permeable dish having a diameter of 41 mm. After the ethanol in the layer was washed with water, water was allowed to pass through at a pressure difference of about 50,000 Pa. The water permeability (cm) after 120 seconds was calculated. 3 ), calculate the water permeability per unit time, unit pressure and unit area, and use it as the water permeability.
[0455] In addition, ν is calculated based on the gas constant R (=8.314), absolute temperature T (K), pi, and the average molecular weight of air M (=2.896×10 -2 kg / mol) and calculated using the following formula.
[0456] ν=((8R×T) / (π×M)) 1 / 2
[0457] 〈Glass transition temperature of thermoplastic polymers〉
[0458] An appropriate amount of an aqueous dispersion containing a thermoplastic polymer (solid content = 38 to 42 parts by mass, pH = 9.0) was measured and placed in an aluminum dish, and allowed to stand at room temperature for 24 hours to obtain a dry film. About 17 mg of the dry film was filled into an aluminum container for measurement, and a DSC curve and a DSC curve under a nitrogen atmosphere were obtained using a DSC measuring device (manufactured by Shimadzu Corporation, model name "DSC6220"). The measurement conditions are as follows.
[0459] The first stage of the heating program: start at 30°C and increase the temperature at a rate of 10°C per minute. After reaching 150°C, maintain it for 5 minutes.
[0460] The second stage of cooling program: start cooling from 110℃ at a rate of 10℃ per minute. After reaching -50℃, maintain for 5 minutes.
[0461] The third stage of temperature increase program: the temperature was increased from -50°C to 150°C at a rate of 10°C per minute. During the third stage of temperature increase, DSC and DDSC data were acquired.
[0462] The glass transition temperature was determined by the method described in JIS-K7121 for the obtained DSC curve. Specifically, the temperature at the intersection of a straight line and a curve, which is equidistant in the longitudinal direction from a straight line obtained by extending the low temperature side baseline in the DSC curve toward the high temperature side and a straight line obtained by extending the high temperature side baseline in the DSC curve toward the low temperature side, was taken as the glass transition temperature (Tg).
[0463] 〈Aspect Ratio of Inorganic Filler in Covering Layer〉
[0464] For the surface of the separator for storage device deposited with osmium, a scanning electron microscope (SEM) (model "S-4800", manufactured by HITACHI) was used to observe under the conditions of an accelerating voltage of 1.0 kV and 10,000 times, thereby measuring. In the SEM image, the inorganic filler in the covering layer is image processed to obtain the aspect ratio. In the case where the inorganic fillers are bonded to each other, a substance that can clearly identify the longitudinal and lateral lengths of the inorganic filler alone is selected, and the aspect ratio is calculated based on them. Specifically, 10 substances that can clearly identify the above-mentioned longitudinal and lateral lengths are selected, and the average value of the value obtained by dividing the major axis of each inorganic filler by the length of the minor axis is used as the aspect ratio. In the case where the material that can clearly identify the longitudinal and lateral lengths is less than 10 in one field of view, 10 are selected from the images of multiple fields of view.
[0465] 〈Particle size distribution of inorganic filler〉
[0466] The particle size distribution of the inorganic filler was measured using a particle size measuring device (made by Nikkiso Co., Ltd., product name "Microtrac UPA150"). The sample solution to be measured used a dispersion before coating, and as the measurement conditions, load index = 0.20, measurement time = 300 seconds, and the value of the standard deviation SD of the volume average particle size in the obtained data was divided by the value of D50 to obtain the particle size distribution (Cv value) of the inorganic filler.
[0467] <Volume average particle size (D50) of the thermoplastic polymer (particulate polymer) in the aqueous dispersion and volume average particle size (D50) of the resin binder>
[0468] The volume average particle size (D50) of the thermoplastic polymer (granular polymer) in the aqueous dispersion and the volume average particle size (D50) of the resin binder were measured using a particle size measuring device (manufactured by Nikkiso Co., Ltd., product name "Microtrac UPA150"). As the measurement conditions, the load index = 0.20, the measurement time = 300 seconds, and the value of the particle size (D50) at which the cumulative volume becomes 50% in the obtained data is recorded as the volume average particle size (D50).
[0469] 〈Particle size distribution of granular polymer〉
[0470] The measurement was performed by observing the cross section of the separator for a storage device on which osmium was deposited using a scanning electron microscope (SEM) (model "S-4800", manufactured by HITACHI Corporation) at an accelerating voltage of 1.0 kV and a magnification of 10,000. Specifically, 200 circle-equivalent diameters of an arbitrary particulate polymer were measured, and the number average particle diameter MN and the volume average particle diameter MV were calculated from these values, and the particle size distribution of the particulate polymer was calculated as MV / MN.
[0471] 〈Rate Characteristics〉
[0472] a. Preparation of positive electrode
[0473] The positive electrode active material is a nickel, manganese, cobalt composite oxide (NMC) (Ni:Mn:Co = 1:1:1 (element ratio), density: 4.70 g / cm 3 ) 90.4 parts by mass, graphite powder (KS6) as a conductive additive (density 2.26 g / cm 3 , number average particle size 6.5 μm) 1.6 parts by mass and acetylene black powder (AB) (density 1.95 g / cm 3 , number average particle size of 48 nm) 3.8 parts by mass, and polyvinylidene fluoride (PVdF) as a binder (density of 1.75 g / cm 3 ) and 4.2 parts by mass, and dispersed them in N-methylpyrrolidone (NMP) to prepare a slurry. The slurry was applied to one side of a 20 μm thick aluminum foil, which became the positive electrode collector, using a die coater, and dried at 130°C for 3 minutes, and then compression-molded using a roll press to produce a positive electrode. The amount of positive electrode active material applied at this time was 109 g / m 2 .
[0474] b. Preparation of negative electrode
[0475] Graphite powder A (density 2.23 g / cm 3 , number average particle size of 12.7 μm) and 87.6 parts by mass of graphite powder B (density of 2.27 g / cm 3 , number average particle size of 6.5μm), 9.7 parts by mass of ammonium salt of carboxymethyl cellulose as a binder (solid content conversion) (solid content concentration of 1.83 parts by mass of aqueous solution) and 1.7 parts by mass of diene rubber latex (solid content conversion) (solid content concentration of 40 parts by mass of aqueous solution) are dispersed in purified water to prepare a slurry. The slurry is applied to one side of a copper foil with a thickness of 12μm, which serves as a negative electrode collector, using a die coater. After drying at 120°C for 3 minutes, compression molding is performed using a roller press to produce a negative electrode. The amount of negative electrode active material applied at this time is 5.2g / m2 .
[0476] c. Preparation of non-aqueous electrolyte
[0477] A non-aqueous electrolyte solution was prepared by dissolving LiPF6 as a solute in a mixed solvent of ethylene carbonate:ethyl methyl carbonate=1:2 (volume ratio) so as to have a concentration of 1.0 mol / L.
[0478] d.Battery assembly
[0479] Cut the separator or substrate into 24mmφ, and cut the positive electrode and negative electrode into 16mmφ circles respectively. Overlap the negative electrode, separator or substrate, and positive electrode in sequence in such a way that the active material surfaces of the positive electrode and the negative electrode face each other, and store them in a stainless steel metal container with a lid. The container and the lid are insulated, the container is in contact with the copper foil of the negative electrode, and the lid is in contact with the aluminum foil of the positive electrode. The battery is assembled by injecting 0.4ml of the aforementioned non-aqueous electrolyte into the container and sealing it.
[0480] e. Evaluation of rate characteristics
[0481] The simple battery assembled in d. is charged at 25°C at a current value of 3mA (about 0.5C) to a battery voltage of 4.2V, and then the current value is reduced from 3mA to maintain 4.2V. The above method is used to perform the initial charging after the battery is made for a total of about 6 hours. Thereafter, the battery is discharged at a current value of 3mA to a battery voltage of 3.0V. Next, the battery is charged at a current value of 6mA (about 1.0C) to a battery voltage of 4.2V at 25°C, and then the current value is reduced from 6mA to maintain 4.2V. The above method is used to perform charging for a total of about 3 hours. Thereafter, the discharge capacity when the battery voltage is discharged at a current value of 6mA to 3.0V is taken as the 1C discharge capacity (mAh). Next, the battery is charged at a current value of 6mA (about 1.0C) to a battery voltage of 4.2V at 25°C, and then the current value is reduced from 6mA to maintain 4.2V. The above method is used to perform charging for a total of about 3 hours. Thereafter, the discharge capacity when the battery voltage was discharged at a current value of 12 mA (about 2.0 C) to 3.0 V was defined as the 2C discharge capacity (mAh). Furthermore, the ratio of the 2C discharge capacity to the 1C discharge capacity was calculated and the value was defined as the rate characteristic.
[0482] Rate characteristics (%) = (2C discharge capacity / 1C discharge capacity) × 100
[0483] Evaluation criteria of rate characteristics (%)
[0484] A (good): rate characteristics exceeding 85%
[0485] B (pass): rate characteristic is more than 80% and less than 85%
[0486] C (poor): rate characteristics are 80% or less
[0487] <Adhesion strength to the electrode (before electrolyte injection)>
[0488] The separator was cut into a rectangular shape of 20 mm wide x 70 mm long and superposed on the positive electrode cut into a size of 15 mm x 60 mm to prepare a laminate of the separator and the electrode. The laminate was pressurized under the following conditions.
[0489] Temperature: 90℃
[0490] Pressurization pressure: 1MPa
[0491] Pressurization time: 5 seconds
[0492] The peel strength between the separator and the electrode after pressurization was measured by performing a 90° peel test at a peeling speed of 50 mm / min using a dynamometer ZP5N and MX2-500N (product name) manufactured by IMADA. At this time, the average value of the peel strength in the peel test of 40 mm in length conducted under the above conditions was used as the peel strength.
[0493] Adhesion evaluation criteria
[0494] A (good): peel strength is 5 N / m or more
[0495] B (pass): peel strength is 2 N / m or more and less than 5 N / m
[0496] C (poor): peel strength is 1 N / m or more and less than 2 N / m
[0497] D (unqualified): peel strength is less than 1N / m
[0498] <Adhesion to the electrode (after electrolyte injection)>
[0499] The separator was cut into a rectangular shape of 20 mm wide and 70 mm long, and overlapped with the positive electrode cut into a size of 15 mm × 60 mm to make a laminate of the separator and the electrode. The laminate was inserted into an aluminum laminate film, and 0.4 ml of an electrolyte (containing 1 mol / L of LiPF6 and a mixture of EC / DEC=1 / 2) was added. After sealing, it was left to stand for 12 hours and pressurized under the following conditions.
[0500] Temperature: 90℃
[0501] Pressurization pressure: 1MPa
[0502] Pressurization time: 1 minute
[0503] The peel strength between the separator and the electrode after pressurization was measured by performing a 90° peel test at a peeling speed of 50 mm / min using a dynamometer ZP5N and MX2-500N (product name) manufactured by IMADA. At this time, the average value of the peel strength in the peel test of 40 mm in length conducted under the above conditions was used as the peel strength.
[0504] Adhesion evaluation criteria
[0505] A (good): peel strength is 5 N / m or more
[0506] B (pass): peel strength is 2 N / m or more and less than 5 N / m
[0507] C (poor): peel strength is 1 N / m or more and less than 2 N / m
[0508] D (unqualified): peel strength is less than 1N / m
[0509] 〈Powder shedding〉
[0510] A tape (manufactured by 3M) with a width of 12 mm and a length of 100 mm was pasted on the base polymer coating layer of the separator. The force when the tape was peeled off from the sample at a speed of 50 mm / min was measured using a 90° peel strength tester (manufactured by IMADA, product name IP-5N). Based on the obtained measurement results, the adhesive strength was evaluated according to the following evaluation criteria.
[0511] A (good): 59N / m (6gf / mm) or more
[0512] B (acceptance): 40N / m or more and less than 59N / m
[0513] C (bad): less than 40N / m
[0514] <Cycling Characteristics and Deformation of Electrode-Separator Wound Body>
[0515] a. Preparation of positive electrode
[0516] The positive electrode active material is a nickel, cobalt, aluminum composite oxide (NCA) (Ni:Co:Al=90:5:5 (element ratio), density: 3.50 g / cm 3) 100 parts by mass, acetylene black powder (AB) as a conductive material 1.25 parts by mass, and polyvinylidene fluoride (PVdF) as a binder 1.0 parts by mass are mixed and dispersed in N-methylpyrrolidone (NMP) to prepare slurry. The slurry is applied to both sides of an aluminum foil with a thickness of 15 μm, which serves as a positive electrode collector, using a die coater, and after drying at 130°C for 3 minutes, a roll press is used to perform compression molding to produce a positive electrode. The amount of positive electrode active material applied at this time is 456 g / m 2 .
[0517] b. Preparation of negative electrode
[0518] 86.0 parts by mass of graphite powder and 4.5 parts by mass of silicon oxide (SiO) as negative electrode active materials, as well as 1 part by mass of sodium salt of carboxymethyl cellulose and 1.0 part by mass of styrene-butadiene rubber (SBR) as binders were dispersed in purified water to prepare slurry. The slurry was applied to both sides of a 7.5 μm thick copper foil, which served as a negative electrode collector, using a die coater, and after drying at 120°C for 3 minutes, compression molding was performed using a roller press to produce a negative electrode. The amount of negative electrode active material applied at this time was 266 g / m 2 .
[0519] c. Preparation of non-aqueous electrolyte
[0520] A non-aqueous electrolyte solution was prepared by dissolving LiPF6 as a solute in a mixed solvent of ethylene carbonate:dimethyl carbonate:ethyl methyl carbonate=25:70:5 (weight ratio) to a concentration of 1.4 mol / L.
[0521] d.Battery assembly
[0522] The positive electrode (width 63 mm), the negative electrode (width 64 mm), and the separator (width 67 mm) were stacked and wound into a spiral shape to produce a wound body. The wound body was placed in a cylindrical battery can with an outer diameter of 21 mm and a height of 70 mm, and the non-aqueous electrolyte was further injected and sealed to assemble a battery.
[0523] e. Evaluation of cycle characteristics
[0524] The battery assembled in d. is charged at 25°C at a current value of 3mA (about 0.5C) until the battery voltage is 4.2V, and then charged in a manner to maintain 4.2V until the current value reaches 50mA. Thereafter, discharge at 0.2C until the battery voltage is 2.5V, and the initial capacity is calculated. Next, charge at 0.3C until the battery voltage is 4.2V, and then charge at 4.2V until the current value reaches 50mA, and then discharge at 1C until the battery voltage is 2.5V. This is regarded as 1 cycle and is repeatedly charged and discharged. In addition, the cycle characteristics are evaluated according to the following benchmarks using the retention rate of the capacity after 500 cycles relative to the initial capacity (capacity in the first cycle).
[0525] A: Capacity maintenance rate of more than 80%
[0526] B: Capacity maintenance rate of 75% or more and less than 80%
[0527] C: Capacity maintenance rate less than 75%
[0528] f. Evaluation of the wound body state after cycle characteristics
[0529] After the cycle characteristics test was performed according to e., the battery was disassembled and the deformation of the electrode-separator winding body was confirmed. At this time, the case where deformation occurred was set as yes, and the case where no deformation occurred was set as no. At this time, the case where there was a gap of 0.5 mm or more was judged as deformation, and the case where there was a gap of less than 0.5 mm was judged as no.
[0530] 《Example of manufacturing base material》
[0531] <Manufacturing of polyolefin microporous membrane substrates B1 to B11>
[0532] (1) As shown in Table 1, the ratios of polyethylene with Mv 700,000 or more (PE1: Mv 900,000, PE3: Mv 800,000, PE4: Mv 700,000, PE6: Mv 770,000), polyethylene with Mv 700,000 or less (PE2: Mv 250,000, PE5: Mv 370,000) and polypropylene (PP, Mv 400,000) were adjusted to obtain a raw resin composition. Next, the raw resin composition, a plasticizer (liquid paraffin) and 0.1% by mass of an antioxidant were blended so as to obtain a polyolefin composition so as to obtain a resin content (PC) shown in Table 1. Next, the polyolefin composition was charged into a twin-screw extruder, and the molten polyolefin composition was extruded to form a gel-like sheet, which was cooled and solidified using a casting roll.
[0533] (2) The cooled and solidified sheet was subjected to a biaxial stretching step using a simultaneous biaxial stretching machine under the conditions shown in Table 1 to obtain a stretched sheet.
[0534] (3) Thereafter, the stretched sheet is immersed in dichloromethane to extract and remove the liquid paraffin, and then dried to make it porous.
[0535] (4) The obtained porous product was then thermally fixed using a uniaxial stretching machine under the conditions shown in Table 1 to obtain polyolefin microporous membrane substrates B1 to B11. The obtained polyolefin microporous membranes were evaluated according to the above method. The evaluation results are shown in Table 2.
[0536] [Table 1]
[0537]
[0538] [Table 2]
[0539]
[0540] 《Example of Preparation of Water Dispersion (Particle-Form Polymer)》
[0541] <Preparation of Aqueous Dispersion A1>
[0542] Into a reaction container equipped with a stirrer, a reflux condenser, a dropping tank and a thermometer, 70.4 parts by mass of ion exchange water, 0.5 parts by mass of "Aqualon KH1025" (a registered trademark, a 25% aqueous solution manufactured by Daiichi Kogyo Seiyaku Co., Ltd., described as "KH1025" in the table. The same shall apply hereinafter), and 0.5 parts by mass of "ADEKA REASOAP SR1025" (a registered trademark, a 25% aqueous solution manufactured by ADEKA Corporation, described as "SR1025" in the table. The same shall apply hereinafter), were added, and the internal temperature of the reaction container was raised to 95°C. Thereafter, while maintaining the internal temperature of the container at 95°C, 7.5 parts by mass of ammonium persulfate (2% aqueous solution) (described as "APS(aq)" in the table. The same shall apply hereinafter).
[0543] On the other hand, a mixture of 71.5 parts by mass of methyl methacrylate (MMA), 18.9 parts by mass of n-butyl acrylate (BA), 2 parts by mass of 2-ethylhexyl acrylate (EHA), 0.1 parts by mass of methacrylic acid (MAA), 0.1 parts by mass of acrylic acid (AA), 2 parts by mass of 2-hydroxyethyl methacrylate (HEMA), 5 parts by mass of acrylamide (AM), 0.4 parts by mass of glycidyl methacrylate (GMA), 0.4 parts by mass of trimethylolpropane triacrylate (A-TMPT) (manufactured by Shin-Nakamura Chemical Industry Co., Ltd.), 0.3 parts by mass of γ-methacryloxypropyltrimethoxysilane (AcSi), 3.0 parts by mass of KH1025, 3.0 parts by mass of SR1025, 0.05 parts by mass of sodium p-styrenesulfonate (NaSS), 7.5 parts by mass of ammonium persulfate (2% by mass aqueous solution), and 52 parts by mass of ion-exchanged water was mixed for 5 minutes using a homomixer to prepare an emulsion. The obtained emulsion was added dropwise from the dropping tank to the above reaction vessel. The addition of the ammonium persulfate aqueous solution to the reaction vessel was started 5 minutes after the addition, and the entire amount of the emulsion was added dropwise over 150 minutes. During the addition of the emulsion, the internal temperature of the container was maintained at 80°C. At this time, the stirrer previously placed in the reaction vessel was stirred in a magnetic stirrer.
[0544] After the dropwise addition of the emulsion was completed, the reaction vessel was kept at an internal temperature of 80° C. for 90 minutes, and then cooled to room temperature to obtain an emulsion. The obtained emulsion was adjusted to pH=9.0 using an aqueous ammonium hydroxide solution (25% by mass aqueous solution) to obtain an acrylic copolymer latex (aqueous dispersion A1) having a concentration of 40 parts by mass. The glass transition temperature (Tg) and volume average particle size (D50) of the thermoplastic polymer contained in the obtained aqueous dispersion A1 were evaluated using the above method. The obtained results are shown in Table 3.
[0545] <Preparation of Aqueous Dispersions A2, A3 and A4>
[0546] Aqueous dispersions A2 to A4 were obtained in the same manner as aqueous dispersion A1 except that the composition of the emulsion was changed as shown in Tables 3 and 4, and the physical properties were evaluated. The obtained results are shown in Tables 3 and 4.
[0547] <Preparation of Aqueous Dispersion A1-1>
[0548] A portion of the aqueous dispersion A1 was taken out and used as a seed polymer for multi-stage polymerization to synthesize the aqueous dispersion A1-1. Specifically, first, a mixture of 20 parts by mass of the aqueous dispersion A1 and 70.4 parts by mass of ion exchange water was added to a reaction vessel equipped with a stirrer, a reflux condenser, a dropping tank and a thermometer, and the internal temperature of the reaction vessel was raised to 80°C. Thereafter, 7.5 parts by mass of ammonium persulfate (2% by mass aqueous solution) was added while maintaining the internal temperature of the container at 80°C. The above is the initial feed.
[0549] On the other hand, a mixture of 71.5 parts by mass of methyl methacrylate (MMA), 18.9 parts by mass of n-butyl acrylate (BA), 2 parts by mass of 2-ethylhexyl acrylate (EHA), 0.1 parts by mass of methacrylic acid (MAA), 0.1 parts by mass of acrylic acid (AA), 2 parts by mass of 2-hydroxyethyl methacrylate (HEMA), 5 parts by mass of acrylamide (AM), 0.4 parts by mass of glycidyl methacrylate (GMA), 0.7 parts by mass of trimethylolpropane triacrylate (A-TMPT), 0.3 parts by mass of γ-methacryloxypropyltrimethoxysilane (AcSi), 3 parts by mass of KH1025, 3 parts by mass of SR1025, 0.05 parts by mass of sodium p-styrenesulfonate (NaSS), 7.5 parts by mass of ammonium persulfate (2% by mass aqueous solution), and 52 parts by mass of ion-exchanged water was mixed for 5 minutes using a homogenizer to prepare an emulsion. The obtained emulsion was dropped from a dropping tank into the above reaction container. The ammonium persulfate aqueous solution was added to the reaction vessel and the addition was started 5 minutes later. The entire amount of the emulsion was added over 150 minutes. During the addition of the emulsion, the internal temperature of the vessel was maintained at 80° C. At this time, the stirring bar previously placed in the reaction vessel was kept stirring in the magnetic stirrer.
[0550] After the dropwise addition of the emulsion was completed, the reaction vessel was stirred while maintaining the internal temperature at 80°C for 90 minutes, and then cooled to room temperature to obtain an emulsion. The obtained emulsion was adjusted to pH = 9.0 using an aqueous ammonium hydroxide solution (25% by mass aqueous solution) to obtain an acrylic copolymer latex (aqueous dispersion A1-1) having a concentration of 40 parts by mass. The obtained aqueous dispersion A1-1 was evaluated using the above method. The results are shown in Table 3.
[0551] <Preparation of Aqueous Dispersions A1-2 to A1-4>
[0552] The copolymer latex (water dispersions A1-2 to A1-4) was obtained by adjusting the number of multi-stage polymerizations. The obtained water dispersions were evaluated by the above-mentioned methods. The obtained results are shown in Table 3.
[0553] <Preparation of Aqueous Dispersions A2-1, A3-1 to A3-4 and A4-1>
[0554] The same operation as aqueous dispersion A1-1 was performed except that the composition of seed polymer, monomer, other raw materials, the number of multi-stage polymerization and polymerization conditions were changed as described in Table 2 to obtain copolymer latex (aqueous dispersion A2-1, A3-1 to A3-4 and A4-1). The obtained aqueous dispersions were evaluated by the above-mentioned methods. The obtained results are shown in Tables 3 and 4.
[0555] 〈Aqueous dispersions A5-A6〉
[0556] SB latex (Tg: 33°C, particle size: 300 nm, toluene insoluble content: 95%, swelling degree: 1.4 times) was used as water dispersion A5. PVdF-HFP (product name LBG, Arkema) in which primary particles with a primary particle size of 200 nm were aggregated to form secondary particles with a size of 2030 nm was used as water dispersion A6.
[0557] [Table 3]
[0558] Table 3. Aqueous dispersion (granular polymer)
[0559]
[0560] [Table 4]
[0561] Table 4. Aqueous dispersion (granular polymer)
[0562]
[0563] Emulsifier
[0564] KH1025: "Aqualon KH1025" registered trademark, manufactured by Daiichi Kogyo Seiyaku Co., Ltd., 25 mass % aqueous solution
[0565] SR1025: "ADEKA REASOAP SR1025" registered trademark, manufactured by ADEKA, 25 mass % aqueous solution
[0566] NaSS: Sodium p-styrene sulfonate
[0567] Initiator
[0568] APS(aq): ammonium persulfate (2 mass % aqueous solution)
[0569] ·monomer
[0570] MAA: Methacrylic acid
[0571] AA: Acrylic acid
[0572] MMA: Methyl Methacrylate
[0573] BA: n-butyl acrylate
[0574] BMA: n-butyl methacrylate
[0575] EHA: 2-Ethylhexyl Acrylate
[0576] CHMA: Cyclohexyl methacrylate
[0577] St:Styrene
[0578] AN: Acrylonitrile
[0579] HEMA: 2-Hydroxyethyl Methacrylate
[0580] AM: Acrylamide
[0581] GMA: Glycidyl Methacrylate
[0582] A-TMPT: Trimethylolpropane triacrylate
[0583] AcSi: γ-methacryloxypropyltrimethoxysilane
[0584] 《Example of manufacturing separator》
[0585] <Example 1>
[0586] 0.3 parts by mass of an aqueous solution of ammonium polycarboxylate (SN Dispersant 5468 manufactured by SANNOPCO) and 100 parts by mass of aluminum hydroxide (boehmite) as an inorganic filler were mixed with 100 parts by mass of water, and the mixture was treated with a bead mill to obtain a pre-coating dispersion. In the pre-coating dispersion, 1 part by mass of carboxymethyl cellulose (CMC) as a water-soluble polymer component was mixed with 100 parts by mass of the inorganic filler, and then 4 parts by mass of an acrylic latex suspension (solid content concentration of 40% by mass, volume average particle size of 150 nm, glass transition temperature of -40°C) as a resin binder was further mixed with 20 parts by mass of aqueous dispersion A1-3 (granular polymer) in terms of solid content, and the mixture was uniformly dispersed to prepare a coating liquid (solid content of 40 parts by mass) containing a thermoplastic polymer.
[0587] The two surfaces of the polyolefin microporous membrane B1 were surface treated by corona discharge treatment. Then, the coating liquid was applied to one surface (surface (A)) of the polyolefin microporous membrane B1 using a gravure coater. The shear rate of the gravure coater was 80,000 sec. -1. At this time, the coverage ratio of the covering layer to the polyolefin microporous membrane is 100%. Thereafter, the applied coating liquid is dried at 60°C to remove water. Furthermore, the coating liquid is also applied to the surface (surface (B)) of the polyolefin microporous membrane B1 opposite to the surface (A), and the same operation is performed again to dry it. In this way, a separator having a covering layer formed on both surfaces of the polyolefin microporous membrane B1 is obtained.
[0588] <Examples 2 to 27>
[0589] Separators of Examples 2 to 27 were obtained in the same manner as in Example 1 except that the polyolefin microporous membrane, the composition of the coating liquid, the coating conditions, etc. were changed as described in Tables 5 to 11. In the separator of Comparative Example 5, the particulate polymer was dispersed in the form of secondary particles. Alumina "AKP3000" manufactured by Sumitomo Chemical Co., Ltd. was used.
[0590] <Example 28>
[0591] The same operation as in Example 1 was performed to obtain a separator of Example 28. For the obtained separator, the coating layer was peeled off by the following method to prepare a substrate sample for measurement. First, the cut separator was placed on a paper base, and the four sides of the separator were fixed with an adhesive tape (OPP tape for packaging). For the portion not covered with the tape, the adhesive tape was similarly affixed. After applying pressure from the tape with a roller, the tape was peeled off to remove the coating layer attached to the tape. Then, the opposite side was treated in the same way to obtain a substrate sample without a coating layer. The results obtained by measuring the physical properties of the substrate using it are shown in Table 2.
[0592] <Comparative Examples 1 to 7>
[0593] Separators of Comparative Examples 1 to 7 were obtained in the same manner as in Example 1 except that the polyolefin microporous membrane, the composition of the coating liquid, the coating conditions, etc. were changed as described in Tables 5 to 10, respectively.
[0594] [Table 5]
[0595] Table 5. Separators
[0596]
[0597] [Table 6]
[0598] Table 6. Separators
[0599]
[0600] [Table 7]
[0601] Table 7. Separators
[0602]
[0603] [Table 8]
[0604] Table 8. Separators
[0605]
[0606] [Table 9]
[0607] Table 9. Separators
[0608]
[0609] [Table 10]
[0610] Table 10. Separators
[0611]
[0612] [Table 11]
[0613] Table 11. Separators
[0614]
[0615] Industrial Applicability
[0616] The electric storage device separator of the present application can be suitably used in various electric storage devices, and is preferably suitably used in lithium ion secondary batteries.
[0617] Description of Reference Numerals
[0618] 1 Inorganic filler
[0619] 2 Granular polymer
[0620] 10. Substrate
[0621] 20 Overlay
Claims
1. A power storage device separator, comprising a substrate and a covering layer, wherein the substrate is a polyolefin microporous membrane containing polyolefin as a main component, and the covering layer is disposed on at least one surface of the substrate. The film thickness of the substrate is 1 μm to 30 μm, and the air permeability is 500 sec / 100 cm 3 The following, and the porosity after compression measured after the substrate is compressed under the conditions of a temperature of 70° C., a pressure of 8 MPa and a compression time of 3 minutes is 30% or more, The cover layer comprises a particulate polymer of a thermoplastic polymer and an inorganic filler, The particulate polymer includes protruding particulate polymer, the protruding particulate polymer protruding from the cover layer by 0.1 times or more of the thickness of the inorganic filler portion of the cover layer.
2. A power storage device separator, comprising a substrate and a covering layer, wherein the substrate is a polyolefin microporous membrane containing polyolefin as a main component, and the covering layer is disposed on at least one surface of the substrate. The polyolefin microporous membrane has a crystal long period of 37.0 nm or more as measured by a small angle X-ray scattering (SAXS) method, The cover layer comprises a particulate polymer of a thermoplastic polymer and an inorganic filler, The particulate polymer includes protruding particulate polymer, the protruding particulate polymer protruding from the cover layer by 0.1 times or more of the thickness of the inorganic filler portion of the cover layer.
3. The electric storage device separator according to claim 2, wherein: The film thickness of the substrate is 1 μm to 30 μm, and the air permeability is 500 sec / 100 cm 3 The substrate is compressed under the conditions of a temperature of 70° C., a pressure of 8 MPa, and a compression time of 3 minutes, and the porosity after compression is measured to be 30% or more.
4. The electrical storage device separator according to any one of claims 1 to 3, wherein In the covering layer, the amount of the particulate polymer is 1 part by mass or more and 50 parts by mass or less relative to 100 parts by mass of the inorganic filler contained in the covering layer, The cover layer is formed in an inclined shape so as to become thicker toward the protruding particulate polymer.
5. The electric storage device separator according to claim 4, wherein When the thickness of the inorganic filler portion of the covering layer is L1 and the maximum distance from the boundary line between the substrate and the covering layer to the outer surface of the inorganic filler of the covering layer formed in the inclined shape is L2, the average value of the inclination rate L2 / L1 of the covering layer is greater than 1.
2.
6. The separator for an electrical storage device according to claim 4, wherein When the thickness of the inorganic filler part of the covering layer is set to L1, the maximum distance from the boundary line between the substrate and the covering layer to the outer surface of the inorganic filler of the covering layer formed into the inclined shape is set to L2, and the maximum distance from the boundary line between the substrate and the covering layer to the outline of the protruding granular polymer is set to L3, the average value of the coverage rate of the protruding part of the protruding granular polymer (L2-L1) / (L3-L1) is greater than 0.
4.
7. The electrical storage device separator according to any one of claims 1 to 3, wherein The particulate polymer includes at least one selected from the group consisting of a (meth)acrylic polymer, a styrene butadiene copolymer, and a copolymer containing fluorine atoms.
8. The electrical storage device separator according to any one of claims 1 to 3, wherein The particulate polymer comprises a copolymer containing (meth)acrylic acid, butyl (meth)acrylate and ethylhexyl (meth)acrylate as monomers.
9. The electrical storage device separator according to any one of claims 1 to 3, wherein The particulate polymer comprises a copolymer containing a multifunctional (meth)acrylate as a monomer. 10 . An electrical storage device comprising the electrical storage device separator according to claim 1 .
Citation Information
Patent Citations
Separator for lithium secondary battery and a method of making the same
KR1020160118979A
Olefin resin microporous film, separator for batteries, battery, and method for producing olefin resin microporous film
WO2014175252A1
Stretched polypropylene film
WO2015012324A1
Polyolefin microporous membrane, separator for cell, and cell
WO2015194504A1
Polyolefin microporous film
WO2018164056A1
Cited By
Diaphragm, preparation method thereof and secondary battery
CN122118308A
A separator, a method of manufacturing the same, and a secondary battery
CN122118308B
